La formation du contrat électronique : dispositif légal (répressif) de protection du cyberconsommateur et modes alternatifs de règlement des conflits (M.A.R.C.) - Diallo, Boubacary (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
L’objectif principal de cette étude est de révéler le dispositif légal répressif de protection du cyberconsommateur. Les résultats de cette étude montrent que le législateur malien, communautaire, sous régional et régional y compris, ont misé beaucoup sur la protection des cyberconsommateurs, en adoptant une politique qui s’articule principalement sur la confidentialité, la protection de la vie privée, la protection de la propriété intellectuelle, et le règlement des conflits par les modes alternatifs de règlement des conflits (M.A.R.C.) déclenchés entre les différentes parties de la transaction en ligne.
Keywords: Contrat électronique; Cyberconsommation; E-commerce; MARC; Règlement des conflits

Approche critique du mécanisme de règlement des différends commerciaux devant la CCI - Kesse, Julia Sainte-Colombe (Université de Montréal, 2026)
Cette étude analyse de manière critique le mécanisme de résolution des litiges commerciaux de la Chambre de commerce internationale (CCI) en trois étapes : précontentieux, contentieux et post contentieux. Il examine d’abord l’évolution des méthodes amiables telles que la médiation, la conciliation ou les commissions de règlement des différends mises en œuvre par la CPI pour la prévention des conflits. Ensuite, la validité, les conditions de validité et les conditions applicables de la procédure d'arbitrage sont analysées. Enfin, elle se penche sur la question de la contestation de l'exécution du jugement, notamment par le biais de la Convention de New York. Cet ouvrage met en lumière les apports et les lacunes du système, en insistant sur les différences sectorielles, les résistances culturelles (en Afrique) et les défis de légitimation. L’on a conclu qu’il était nécessaire de renforcer la complémentarité entre le règlement amiable et l’arbitrage afin d’établir une justice commerciale plus efficace, universelle et durable. This thesis critically analyses the International Chamber of Commerce (ICC) mechanism for resolving commercial disputes at three stages: pre-dispute, dispute and post-dispute. First, it examines the development of amicable procedures such as mediation, arbitration or dispute settlement bodies adopted by the ICC to prevent conflicts. It then analyses the effectiveness of arbitration proceedings, the conditions for their entry into force and the elements for their applicability. Finally, it questions the enforcement of arbitration awards, especially under the New York Convention. The study highlights the strengths and weaknesses of the system, underlining sectoral differences, cultural resistance (in Africa and Asia) and legitimacy challenges. It concludes that in order to build a more effective, universal and sustainable commercial justice system, it is necessary to strengthen the complementarity between amicable settlement and arbitration.
Keywords: Alternative; Arbitrage commercial international; Chambre de commerce internationale; Commercial litigation; Contentieux commercial; Convention de New York (1958); Enforcement of arbitral awards; Exécution des sentences arbitrales; International Chamber of Commerce (ICC); International commercial arbitration; International commercial mediation; Médiation commerciale internationale; New York Convention

Arbitration and state sovereignty in commercial disputes resolution within ohada laws - Buma, Roland Sigala; Biya, Fabilou (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Long ago before the creation of the state courts, men had resorted to arbitration for the resolution of diputes. Today, based on the principle of monopoly of the state to render justice, the power to judge is given only to the state. Rendering of justice is one of the areas where the state exeercises its sovereign powers. This has made us to ask the question : is arbitration a violation of the sovereignty of the state in the domain of dispute resolution ? Arbitration is not a violation of the sovereign powers of the state because, it is not all disputes that are resolved via arbitration (for example, crimnal, tax disputes etc can not be settled via arbitration) and the state courts intervene in arbitratin when ever it is necessary. The sate courts intervene in arbitration to grant exequatur, order interim mesaures etc. Nonetheless, since OHADA legislator has not given a complete list of all disputes that can not be resolve via arbitration, we recomend that OHADA should provide a list of all disputes whcih can be settle via arbitration as it is the case with the Arbitration Act of Zimbabw. This article aims at identifying those cases that can not be settled by way of arbitration and those instances in which the state courts intervene in arbitration. Avant la création des tribunaux étatiques, les hommes ont eu recours à l'arbitrage pour la résolution des litiges. Aujourd'hui, sur la base du principe du monopole de l'État à rendre la justice, le pouvoir de juger n'est conféré qu'à l'État. Le fait de rendre la justice est l'un des domaines dans lesquels l'État exerce ses pouvoirs souverains. Cela nous a amenés à poser la question : l'arbitrage constitue-t-il une violation de la souveraineté de l'État dans le domaine du règlement des différends ? L'arbitrage n'est pas une violation des pouvoirs souverains de l'État car, d'une part, tous les litiges ne sont pas résolus par voie d'arbitrage (par exemple, les litiges pénaux, fiscaux, etc. ne peuvent pas être réglés par arbitrage) et, d'autre part, les tribunaux étatiques interviennent dans l'arbitrage chaque fois que cela est nécessaire. Les tribunaux étatiques interviennent dans l'arbitrage pour accorder l'exequatur, ordonner des mesures provisoires, etc. Néanmoins, étant donné que le législateur de l'OHADA n'a pas établi une liste exhaustive de tous les litiges qui ne peuvent pas être résolus par arbitrage, nous recommandons que l'OHADA fournisse une liste de tous les litiges qui peuvent être réglés par voie d'arbitrage, comme c'est le cas dans la loi sur l'arbitrage du Zimbabwe. Cet article vise à identifier les litiges qui ne peuvent pas être réglés par voie d'arbitrage ainsi que les situations dans lesquelles les tribunaux étatiques interviennent dans l'arbitrage.
Keywords: Arbitrage; Arbitrage commerciale; Arbitragem; Arbitraje; Arbitration; Commercial disputes; Droit OHADA; Litiges commerciaux; OHADA law; Souveraineté; Sovereignty

L’impact des clauses d’arbitrage entre investisseurs étrangers et Etats sur la souveraineté : une analyse de l'équilibre entre protection des investisseurs étrangers et la souveraineté - Ahouyanganga Matondo, Dan Salomon (Université de Montréal, 2026)
Ce mémoire analyse l’impact des clauses d’arbitrage entre investisseurs étrangers et États sur la souveraineté étatique, en s’intéressant à l’équilibre entre protection des investisseurs et capacité réglementaire des États. Dans un contexte de mondialisation marqué par les crises sanitaires et les tensions géopolitiques, les États cherchent à attirer les investissements étrangers tout en préservant leur souveraineté économique. Le travail met en lumière le rôle du mécanisme RDIE, permettant aux investisseurs étrangers de contester les mesures étatiques devant des tribunaux arbitraux internationaux, contournant ainsi les juridictions nationales. Bien qu’il sécurise les flux d’investissements et renforce la confiance des investisseurs, le RDIE peut créer des déséquilibres, limitant la marge de manœuvre des États dans des domaines sensibles tels que la santé publique, l’environnement ou les droits sociaux. À travers l’analyse de cas emblématiques et des traités internationaux d’investissement, le mémoire propose des pistes pour concilier la protection juridique des investisseurs et le respect de la souveraineté étatique. Il conclut que le RDIE, tout en étant un outil essentiel de sécurisation des investissements, nécessite des réformes pour garantir un équilibre durable entre intérêts privés et intérêt général. This research study will analyze the impact of arbitration clauses between foreign investors and states on state sovereignty, focusing on the balance between investor protection and the regulatory capacity of states. In a globalized context marked by health crises and geopolitical tensions, states seek to attract foreign investment while preserving their economic sovereignty. The study highlights the role of the ISDS mechanism, which allows foreign investors to challenge state measures before international arbitration tribunals, thus bypassing national courts. Although it ensures investment flows and strengthens investor confidence, the ISDS system can create imbalances, limiting states' room for maneuver in sensitive areas such as public health, the environment, and social rights. Through analysis of historical cases and international investment treaties, the thesis proposes ways to reconcile legal protection for investors with respect for state sovereignty. It concludes that while ISDS remains an essential tool for securing investments, it requires reform to ensure a sustainable balance between private interests and the public good.
Keywords: Arbitration clauses; Clauses d’arbitrage; Foreign investors; ISDS; Investisseurs étrangers; Investment treaties; RDIE; Souveraineté; Sovereignty; States; Traités d’investissement; États

Artifical intelligence and international arbitration law: revolution or evolution - Łągiewska, Magdalena (Routledge research in international commercial law, 2026)
The book asks whether the use of Artificial Intelligence (AI) and Generative AI (GenAI) in international arbitration represents a revolution or an evolution of the international dispute resolution landscape. Critically engaging with the transformative impact of the Fourth Industrial Revolution (4IR), this book focuses on the integration of AI and GenAI into international commercial arbitration. Set against the backdrop of rapid technological advancement, it explores how arbitral tribunals and stakeholders are cautiously yet progressively adopting these innovations in a manner that respects and preserves the foundational principles of arbitration. Through an interdisciplinary and practice-oriented approach, the book examines the evolving role of AI in arbitration. It analyzes how AI is perceived and applied by parties, arbitral institutions, and arbitrators, as well as assesses the legal frameworks in place to govern it. Offering a balanced analysis of both the opportunities and legal and ethical dilemmas posed by emerging technologies, the book asks if a duty of disclosure is relevant in relation to AI use, and what challenges this might entail. It also covers the status of AI-generated arbitral awards under international law, as well as copyright law. This book will be of interest to researchers in the field of international arbitration and commercial law
Keywords: Arbitrage; Artificial Intelligence; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Intelligence artificielle; International commercial arbitration; UNCITRAL Model Law on International Commercial Arbitration (1985)

Réflexion sur la procédure de médiation de l’acte uniforme de l’OHADA relatif à la Médiation (AUM) - Adjita, Shamsidine Akrawati (Revue Internationale de Droit et Science Politique, 2025)
La médiation n’est pas une invention du législateur de l’OHADA. Elle est aussi vieille que le monde. Sa consécration légale à travers l’Acte uniforme relatif à la médiation met en évidence son importance dans la résolution des litiges à l’amiable dans l’ordonnancement juridique de l’OHADA. Cela s’explique car la médiation renvoie à l’idée de justice. Le sentiment de justice n’est pas lié à une époque, il est plutôt inhérent à l’existence humaine et porte en lui-même une exigence, une valeur fondamentale universellement reconnue. Il s’agit du droit à la justice dont le respect permet d’apprécier de façon efficiente les valeurs auxquelles une société est attachée. Toute société a besoin de justice, mais elle ne peut la rendre de façon satisfaisante avec le procédé traditionnel qu’est le jugement. Le juge ne peut pas tout. Le bon sens dicte de l’éviter. Selon un adage populaire, « un mauvais accord vaut mieux qu’un bon procès ». Là où il y a une société, il y a des différends. Là où il y a des différends, il y a des modes de règlement des différends parmi lesquels la médiation occupe une place de choix. Avatar médiatisé de la justice consensuelle, panacée de la déjudiciarisation et de la déjuridicisation, la médiation est parée de toutes les vertus pour éviter le procès. Elle apparaît donc comme une alternative à laquelle peuvent recourir les parties en conflit pour régler leur malentendu à l’amiable tout en préservant leurs relations d’affaires. Elle n’est pas une procédure laissée à l’appréciation du juge, mais plutôt à celle des parties en conflit qui en sont les principales actrices. Cependant elles ne peuvent parvenir à la résolution de leur litige que par l’intermédiaire d’un tiers appelée médiateur et sans lequel la procédure serait incomplète. On a donc, d’un côté, les parties à la médiation qui la considèrent comme étant leur affaire et, de l’autre, le médiateur qui est considéré comme le chef d’orchestre de la procédure. Mediation is not an invention of the OHADA legislator. It is as old as the world itself. Its legal recognition through the Uniform Act on Mediation highlights its importance in the amicable resolution of disputes within the OHADA legal system. This is because mediation refers to the idea of justice. The sense of justice is not tied to a particular era; rather, it is inherent to human existence and carries with it a requirement, a universally recognized fundamental value. It is the right to justice, respect for which allows for the efficient appreciation of the values to which a society is attached. Every society needs justice, but it cannot deliver it satisfactorily through the traditional process of judgment. Judges cannot do everything. Common sense dictates that it should be avoided. According to a popular saying, “a bad agreement is better than a good trial.” Where there is society, there are disputes. Where there are disputes, there are ways of resolving them, among which mediation occupies a prominent place. As the media-friendly face of consensual justice and the panacea for reducing court cases and legal proceedings, mediation is seen as the ideal way to avoid litigation. It therefore appears to be an alternative that parties in conflict can use to settle their differences amicably while preserving their business relationships. It is not a procedure left to the discretion of the judge, but rather to that of the parties in conflict, who are the main actors. However, they can only resolve their dispute through a third party called a mediator, without whom the procedure would be incomplete. On the one hand, therefore, we have the parties to the mediation, who consider it to be their business, and on the other, the mediator, who is considered to be the conductor of the procedure.
Keywords: Acte uniforme; Judge; Juge; Mediation; Mediator; Médiateur; Médiation; Parties en conflit; Parties to the dispute; Uniform Act

La contribution de la technologie vers une modernisation efficace des modes alternatifs de règlement de conflits - Sangare, Abou Bakary (Université de Montréal, 2025)
Les modes alternatifs de règlement de conflits ont révolutionné le monde du règlement de litiges grâce à leurs nombreux avantages. Les coûts moins onéreux en dehors de l’arbitrage, la célérité des procédures, la confidentialité, le dialogue ouvert, l’émergence de solutions créatives profitant plus ou moins à chacune des parties, constituent entre autres les nombreux éléments qui les rendent plus efficaces par rapport à une procédure contentieuse devant une instance judiciaire ordinaire. Cependant, ces modes alternatifs de règlement de conflits font quand même face à bien d’écueils qui les rendent au fil du temps moins efficaces. L’imprévisibilité des situations conflictuelles apportées à la table des instances de résolution, entraîne une inadéquation des solutions envisagées. De plus, le capital humain fait aussi défaut quand on sait que le nombre de ces règlements amiables de litiges de ces dernières années accroît considérablement, acculant ainsi le personnel de gestion de ces conflits qui se retrouve à faire face aux mêmes défis que le personnel des instances judiciaires contentieuses. De plus, l’humain ne pouvant se détacher indéfiniment de ses émotions peut très rapidement tomber dans la partialité quand il s’agit de prendre des décisions. Il est dès lors capital de penser à une modernisation de ces modes alternatifs de règlement de conflits afin de les rendre plus efficaces par le biais de nouveaux moyens technologiques. Certes, la Résolution de litiges en ligne existe depuis quelques années maintenant. Cependant, il est temps d’y apporter de nouveaux ingrédients afin de rendre meilleure la recette. Alternative dispute resolution has revolutionized the world of dispute resolution thanks to its many advantages. Lower costs, faster procedures, confidentiality, open dialogue and the emergence of creative solutions that benefit both parties to a greater or lesser extent - these are just some of the factors that make alternative dispute resolution more effective than litigation in the ordinary courts. However, these alternative dispute resolution methods do face a number of pitfalls that make them less effective over time. The unpredictability of conflict situations brought to the resolution table leads to inadequate solutions. What's more, human capital is also in short supply, as the number of out-of-court settlements in recent years has risen sharply, leaving conflict management staff facing the same challenges as staff in contentious legal proceedings. What's more, since human beings are unable to detach themselves from their emotions indefinitely, they can quickly fall into the trap of bias when it comes to making decisions. It is therefore vital to consider modernizing these alternative dispute resolution methods, in order to make them more effective through new technological means. Online dispute resolution has been around for some years now. However, it's time to add new ingredients to make the recipe even better.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitration; Blockchain; Chatbots; Conciliation; ICT; Internet; Justice; Justice prédictive; MARD; Mediation; Modes alternatifs de règlement de conflits; Médiation; Négociation; ODR; Online dispute resolution; Predictive justice; Règlement de litiges en ligne; TIC; Technologie; Technology; Transaction

L'équilibre de la relation entre investisseur étranger et État hôte dans la jurisprudence arbitrale - Jorland, Maxime (Université Paris-Saclay, 2025)
Le droit des investissements internationaux s'est construit sous l'impulsion des tribunaux arbitraux qui, dans leur rôle d'interprétation du droit international coutumier et des traités d'investissement, ont contribué à enrichir le droit matériel des investissements. La multiplication des sentences rendues a constitué progressivement une véritable jurisprudence, visant à équilibrer la relation entre l'investisseur étranger et l'État hôte. Cependant, l'interprétation des traités par les tribunaux arbitraux s'est souvent faite dans un objectif de protection de l'investisseur face à la puissance publique de l'État, jusqu'à inverser parfois le rapport de force entre les deux opérateurs. De plus, l'absence de principe de précédent en arbitrage d'investissement a contribué à créer un flou notionnel, du fait des interprétations changeantes des dispositions des traités protégeant l'investisseur étranger. 2Cette étude vise donc à faire état du droit positif des investissements internationaux en déterminant un courant doctrinal commun aux sentences arbitrales. Une fois ce travail de compilation réalisé, l'objectif sera alors de déterminer l'état de l'équilibre des forces entre les deux opérateurs et proposer un rééquilibrage du droit des investissements. Ce rééquilibrage passe notamment par une redéfinition des critères jurisprudentiels imprécis ou changeants et une adaptation de la protection de l'investisseur étranger aux enjeux modernes du commerce international, tout en veillant à permettre à l'Etat hôte de conserver ses prérogatives de puissance publique. International investment law has largely been shaped by arbitral tribunals, whose interpretative function with regard to customary international law and investment treaties has contributed significantly to the development of substantive investment law. The proliferation of arbitral awards has progressively given rise to a de facto jurisprudence, aimed at striking a balance between the interests of foreign investors and the sovereign rights of host States. However, treaty interpretation by arbitral tribunals has often been guided by a protective logic in favour of the investor, at times to the extent of inverting the power dynamic between the two actors. Furthermore, the absence of a binding precedent doctrine in investment arbitration has fostered conceptual uncertainty, resulting from fluctuating interpretations of the treaty provisions safeguarding foreign investors.This study seeks to provide an overview of the current state of positive international investment law by identifying a coherent doctrinal trend emerging from arbitral case law. Based on this synthesis, the aim is to evaluate the prevailing balance of power between the investor and the host State, and to propose avenues for rebalancing investment law. Such rebalancing entails, in particular, a clarification of vague or inconsistent jurisprudential standards and an adaptation of investor protection to contemporary challenges of international trade, while ensuring that host States retain their sovereign regulatory authority.
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; CIRDI; Etat hôte; FDI; Host state; ICSID; International; Investissements; Investissements étrangers; Investisseur; Investments; Investor

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

Analyse critique du développement de la médiation en France : les résistances à l'essor de la médiation en droit privé - Prêté, Safya Bayoub (Université Bourgogne Franche-Comté, 2025)
La médiation est une technique de communication faisant intervenir un tiers impartial, neutre et indépendant, pour aider des individus à trouver une issue à leur crise conflictuelle. Par essence, la médiation est un outil de résolution des conflits pacifiant, fondé sur la responsabilisation des parties. Attrayante par sa souplesse, louée pour son coût présenté comme modéré, le législateur en a encouragé l’expansion. Alors que l’article 21 du code de procédure civile confie au juge la mission de concilier les parties, la médiation devient l’un des outils privilégiés par les pouvoirs publics pour permettre la réalisation de cette mission. Ainsi, la loi n°95-125 du 8 février 1995, relative à l’organisation des juridictions et à la procédure civile, pénale et administrative, institue la médiation judiciaire. Elle marque le début d’un ancrage législatif en faveur de ce processus. Ce premier mouvement en faveur de la médiation s’est accéléré en France, à l’initiative de l’Union européenne qui a fait adopter le 21 mai 2008 la Directive 2008/52/CE portant sur la médiation en matière civile et commerciale. Le postulat de départ de ce texte est qu’un « cadre juridique prévisible peut permettre aux citoyens de l’Union européenne (UE) de bénéficier pleinement des avantages de la médiation en tant que mécanisme de résolution des conflits, notamment sur le plan de la rentabilité et de la rapidité ». Puis, la médiation conventionnelle a été encadrée au sein du code de procédure civile. L’intégration de la Directive 2008/52/CE au sein du corpus de normes du droit interne positif a permis de créer une définition légale de la médiation en ces termes : « La médiation régie par le présent chapitre s'entend de tout processus structuré, quelle qu'en soit la dénomination, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l'aide d'un tiers, le médiateur, choisi par elles ou désigné, avec leur accord, par le juge saisi du litige ».Or, le mouvement d’expansion de la médiation semble freiné par un jeu de résistances. Certaines de ces résistances concernent le processus et sont prévisibles. D’autres tiennent à des variables exogènes, résultats de questionnements sur la médiation, le médiateur, l’office du juge, la déjudiciarisation, la déjuridictionnalisation, et l’ordre public. L’étude pose que l’essor de la médiation est contrarié par une méconnaissance de la médiation, ainsi qu’en raison d’une méconnaissance des acteurs de la médiation.Le mouvement d’encouragement des pouvoirs publics à la tentative de médiation, pour prévenir ou traiter des contentieux du droit privé, semble se muer en une politique globale de l’amiable, recentrée sur la mission du juge de concilier les parties. Cette politique de l’amiable persiste à produire des normes tendant, notamment, à encadrer la médiation, à créer un statut pour le médiateur, dans l’optique d’acculturer les justiciables à ce mode amiable.L’objet de la présente thèse est d’analyser les résistances à l’essor de la médiation en droit privé et leurs conséquences sur son développement en France. Il s’agit de saisir ces résistances et leurs enjeux ; et de redonner force au processus de médiation, en offrant à ses prescripteurs un faisceau d’arguments intelligibles. Mediation is a communication technique involving an impartial, neutral and independent third party to help individuals find a way out of their conflict crisis. By nature, mediation is a pacifying conflict resolution tool, based on the accountability of the parties. Attractive for its flexibility, praised for its moderate cost, the legislator encouraged its expansion. While Article 21 of the Code of Civil Procedure entrusts the judge with the task of reconciling the parties, mediation is becoming one of the tools favoured by the public authorities to enable this mission to be carried out. Thus, Law No. 95-125 of February 8, 1995, relating to the organization of the courts and civil, criminal and administrative procedure, establishes judicial mediation. It marks the beginning of a legislative anchoring in favour of this process. This initial movement in favour of mediation has accelerated in France, at the initiative of the European Union, which adopted Directive 2008/52/EC on mediation in civil and commercial matters on May 21, 2008. The premise of this text is that "a predictable legal framework can allow citizens of the European Union (EU) to fully benefit from the advantages of mediation as a dispute resolution mechanism, particularly in terms of cost-effectiveness and speed". Then, conventional mediation was framed in the Code of Civil Procedure. The incorporation of Directive 2008/52/EC into the body of norms of positive domestic law has made it possible to create a legal definition of mediation in the following terms: "Mediation governed by this chapter means any structured process, whatever its name, by which two or more parties attempt to reach an agreement with a view to the amicable resolution of their disputes, with the help of a third party, the mediator, chosen by them or appointed, with their agreement, by the judge hearing the dispute". However, the movement towards the expansion of mediation seems to be slowed down by a game of resistance. Some of these resistances are process-related and predictable. Others relate to exogenous variables, the result of questions about mediation, the mediator, the judge's office, diversion, dejurisdictionalization, and public order. The study posits that the development of mediation is thwarted by a lack of knowledge of mediation, as well as because of a lack of knowledge of the actors involved in mediation. The movement to encourage the public authorities to attempt mediation, to prevent or deal with private law disputes, seems to be turning into a global policy of amicable litigation, refocused on the judge's mission to reconcile the parties. This amicable policy persists in producing standards tending, in particular, to regulate mediation, to create a status for the mediator, with a view to acculturating litigants to this amicable method. The purpose of this thesis is to analyze the resistance to the rise of mediation in private law and their consequences on its development in France. It is a question of grasping these resistances and their stakes; and to give strength to the mediation process, by offering its prescribers a bundle of intelligible arguments.
Keywords: Amiable; Arbitrage (droit); Arbitration; Civil Law; Contract Law; Contrats; Droit civil; Droit des contrats; Droit privé; France; Mediation; Médiation; Private Law; Procedure Law; Procédure civile; Settlment

El arbitraje como justicia alternativa y eficaz - Nieto, Gastón Fabricio Correa (Polo del Conocimiento, 2025)
El presente ensayo surge de la experiencia del ejercicio profesional de la abogacía en la que en el ámbito judicial, extrajudicial, donde se ha observado diferentes vicisitudes en el desarrollo y ejecución de procesos judiciales, generando de esta forma ineficiencia en la administración de justicia; para lo cual como alternativa viable surgen los métodos alternativos de solución de conflictos con la promulgación de la Ley de Arbitraje y Mediación surgen en septiembre de 1997 como una opción ante la deficiente administración de Justicia.Sin embargo, esta ineficiencia procesal representa a su vez un obstáculo real para su ejercicio efectivo de derechos, especialmente obtener “justicia” para los ciudadanos que enfrentan demoras prolongadas y procedimientos burocráticos que terminan por vulnerar sus derechos. Uno de los objetivos del artículo es la de establecer las medidas efectivas que se pueden adoptar en instancia extrajudicial y elementos necesarios alcanzar la tan preciada “Justicia” siendo esta “la constante y perpetua voluntad de dar a cada quien lo que le corresponde” (Ulpiano, 2015).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Deficiencia judicial; Justicia; Negligencia; Retardo

Comercio sostenible y arbitraje internacional: un enlace estratégico para la resolución de conflictos - León, Jorge Guillermo Cedeño; Erazo, Angie Gabriela Sánchez (Polo del Conocimiento, 2025)
El arbitraje internacional ha emergido como una herramienta clave para la resolución de controversias en el comercio sostenible, ofreciendo un marco eficiente y flexible. Este estudio analiza el uso del arbitraje en casos relacionados con comercio y sostenibilidad, evaluando su efectividad en la promoción de prácticas comerciales responsables.
Keywords: Arbitrage international; Arbitraje internacional; Comercio sostenible; Commerce durable; International commercial arbitration; Prácticas responsables; Resolución de controversias; Sostenibilidad

Impacto de las tecnologías emergentes en la confidencialidad y transparencia del arbitraje internacional - Pérez-Pacheco, Yaritza; Lee, Díckar Bonyuet (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
El arbitraje comercial internacional enfrenta el desafío de integrar tecnologías emergentes como la inteligencia artificial, el Big Data y el blockchain, sin comprometer sus principios fundamentales de confidencialidad y transparencia. Este artículo analiza, a partir de una revisión documental y comparativa, cómo el uso de estas tecnologías im-pacta la gestión de casos, el análisis predictivo y la ejecución de laudos, al tiempo que mejora la eficiencia y accesibilidad del arbitraje, pero también genera riesgos en materia de privacidad, ciberseguridad y protección de datos sensibles. Asimismo, se analizan los enfoques regulatorios adoptados en distintas jurisdicciones, incluyendo el Reglamento de la Unión Europea, el modelo flexible de Estados Unidos y las iniciativas tecnológi-cas de países asiáticos como China y Hong Kong. La investigación concluye que, para equilibrar la innovación y la protección de la información, es indispensable implementar protocolos globales y estándares éticos que garanticen un arbitraje confiable y seguro en entornos digitales. International commercial arbitration faces the challenge of integrating technologies such as artificial intelligence, Big Data, and blockchain, without undermining confidentiality and transparency. This article examines how these tools impact case management, predictive analysis, and the enforcement of awards, improving efficiency while also raising concerns about privacy and cybersecurity. Regulatory approaches are explored, from the European Union’s framework to the more flexible model of the United States and technological initiatives in Asia. The research concludes that it is essential to establish global and ethical standards to ensure a secure and reliable arbitration process in the digital era.
Keywords: Arbitrage; Arbitragem; Arbitraje internacional; Arbitral award enforcement; Arbitration; Confidentiality; Confidentialité; Ejecución de laudos arbitrales; Emerging technologies; International arbitration; International dispute resolution; Resolución internacional de disputas; Tecnologías emergentes; Transparence; Transparency

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

La transparencia en el arbitraje internacional: avances y nuevos retos - Pollero, Marianela Bruno (Jurídica Ibero: Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
Este artículo responde a la propuesta académica del Departamento de Derecho de la Uni-versidad Iberoamericana en conmemoración del 10.° aniversario de las normas de trans-parencia de la Comisión de las Naciones Unidas para el Derecho Mercantil (CNUDMI) y complementa la actividad académica realizada por la Universidad Iberoamericana, la Secretaría de Relaciones Exteriores de México y el Centro de Mediación y Arbitraje de la Cámara de Comercio de la Ciudad de México (CANACO), con el apoyo de la Secre-taría de la CNUDMI, en el marco del UNCITRAL LAC DAYS- México 2024. Durante esta actividad se organizaron tres mesas de debate integradas por desta-cados miembros de la comunidad arbitral, de la sociedad civil y del sector privado. La temática de estudio brindó desde México una visión sobre la confidencialidad vs. la transparencia, así como los avances y los retos de la transparencia en el arbitraje inter-nacional.
Keywords: Arbitrage international; Arbitragem Internacional; Arbitraje internacional; Arbitration; Transparence (droit); Transparencia

Reflexiones sobre el régimen de transparencia en el arbitraje comercial internacional - Rendón, Martha Angélica Alvarez (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
From an approach to the concepts of transparency, confidentiality, and privacy, this article examines the tension that may arise between these principles in international commercial arbitration. It also analyzes how arbitration rules address confidentiality and transparency, questioning whether a balance between the two has been achieved. Additionally, it reflects on the impact of public interest in promoting transparency in arbitral proceedings, considering whether the measures adopted are compatible with this type of arbitration. Desde un acercamiento a las nociones de transparencia, confidencialidad y privacidad, en este artículo se valora la tensión que puede existir entre dichos conceptos en el arbi-traje comercial internacional. Asimismo, se alude a algunos reglamentos de arbitraje que abordan la confidencialidad y la transparencia, parar mostrar si se alcanza un equilibrio entre los principios analizados. Además, se llama a reflexionar sobre el impacto del inte-rés público en la búsqueda de la transparencia en los procesos arbitrales, con la finalidad de abrir el debate sobre la compatibilidad de las medidas que se han adoptado en este rubro en el arbitraje comercial.
Keywords: Arbitrage; Arbitragem; Arbitraje comercial internacional; Arbitraje de inversión; Arbitration; Confidencialidad; Confidentiality; International commercial arbitration; Interés público; Investment arbitration; Privacidad; Privacy; Public interest; Transparence; Transparencia; Transparency

Libres propos sur la volonté des parties dans l’arbitrage OHADA - Waham Mayegle, Joseph Laurent (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
L’arbitrage est une réalité en Afrique depuis longtemps déjà. C’est avec l’avènement de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires que ce domaine a pu avoir un dispositif bien structuré. Etant un mode alternatif de règlement des différends, l’arbitrage a pour fondement prépondérant la volonté des parties qui y font recours. Il s’est donc posé en filigrane la question de la portée de la volonté des parties à l’arbitrage OHADA. Le constat est que tout comme en matière contractuelle, elle est un élément indispensable à l’efficacité de ce mode de résolution des litiges. C’est la raison pour laquelle sa portée est traduite par une prégnance avérée, et un recul tout de même constaté.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Volonté des parties

La seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario - Muñoz, Nohely Alejandra Zambrano; Pacheco, Marco Antonio Acosta; Reyes, Eloísa Carolina Solís; Parra, José Antonio Velez (Polo del Conocimiento, 2025)
El estudio de la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario tuvo como objetivo analizar la incidencia de la seguridad jurídica en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario como garantía de los procesos judiciales. Para lo cual, se utilizó una investigación de tipo desriptiva y de campo, con un enfoque mixto y el método hermenéutico; para la recopilación de información primaria se aplicó una encuesta y entrevista a los juristas en libre ejercicio de su profesión. Se obtuvo que que todas las personas tienen derecho al debido proceso, el cual está ligado estrechamente al derecho a la seguridad jurídica ya que, este segundo implica el conocimiento y certeza del derecho positivo, la confianza de la sociedad en las instituciones del Estado y en el orden jurídico y la existencia de mecanismos jurídicos frente a las afectaciones que pudieren existir. Se concluyó que la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales es esencial para mantener la confianza en el sistema legal y para proteger los derechos fundamentales de las personas involucradas en cualquier procedimiento legal, ya sea voluntario, sumario u ordinario.
Keywords: Debido proceso; Due process; Judicial decisions; Legal certainty; Ordinary procedure; Procedimiento ordinario; Procedimiento sumario; Procedimiento voluntario; Resoluciones judiciales; Seguridad jurídica; Summary procedure; Voluntary procedure

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

L'amélioration de l'accès à la justice au Bénin dans le domaine commercial et foncier : comment les modes alternatifs de règlement des conflits et la technologie peuvent être mis à contribution ? - Agoïnon, Fifamè Danielle Esperancia (Université de Montréal, 2025)
En dépit de l'importance cruciale de la justice au sein de notre société, il est manifeste que le système judiciaire béninois présente d'importants défis en matière d'accessibilité, d'efficacité et de confiance publique. Les coûts de la justice, la perte de contrôle des problèmes, les délais d’attente avant procès, la structure labyrinthique des tribunaux, l'impossibilité de se représenter seul, ainsi que le caractère inhospitalier des tribunaux constituent des indicateurs d'un système judiciaire défaillant. En effet, des limitations dans l'accès à la justice alimentent la méfiance des citoyens à l'égard du système judiciaire étatique. Dans un souci de célérité et d'efficacité de la justice, un vent de généralisation des modes alternatifs de règlement des conflits et de recours des technologies souffle sur les procédures judiciaires en général et sur les procédures civiles et commerciales en particulier. S’inscrivant dans cette logique, la loi n° 2020-08 du 23 Avril 2020 portant modernisation de la justice en République du Bénin n’a pas manqué de faire faire une place aux modes alternatifs de règlement des conflits. Elle met également un accent sur la dématérialisation progressive des procédures judiciaires concernant la saisine des juridictions, le suivi des procédures et le paiement électronique des frais afférents. Cependant, malgré ces mesures à encourager, les juridictions, au risque de rompre, ploient toujours devant les litiges fonciers et commerciaux. La présente étude a pour objet d'analyser les forces et les faiblesses du système judicaire béninois et vérifier si la modernisation des modes alternatifs de règlement des différends et l’intégration de la technologie dans les processus de résolution des différends peuvent être un vecteur de l’accès à la justice au Bénin. Despite the crucial importance of justice in our society, it is clear that the Beninese justice system presents significant challenges in terms of accessibility, efficiency and public trust. The costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent the costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent oneself, as well as the inhospitable nature of the courts are indicators of a broken justice system. Indeed, limitations in access to justice fuel citizens' mistrust of the state justice system. In the interests of speed and efficiency of justice, a wind of generalization of alternative methods of dispute resolution and recourse of technologies is blowing through judicial procedures in general and civil and commercial procedures in particular. In line with this logic, Law No. 2020-08 of 23 April 2020 on the modernization of justice in the Republic of Benin did not fail to make room for alternative methods of conflict resolution. It also emphasizes the gradual dematerialization of judicial procedures concerning the referral of cases to the courts, the monitoring of procedures and the electronic payment of related costs. However, despite these measures to be encouraged, the courts, at the risk of breaking down, are still bending before land and commercial disputes. The purpose of this study is to analyze the strengths and weaknesses of the Beninese judicial system and to verify whether the modernization of alternative dispute resolution methods and the integration of technology into dispute resolution processes can be a vector of access to justice in Benin.
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Business; Bénin; Commercial; Différend; Dispute; Foncier; Information; Land; MARD; Technologie; Technology

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Global Arbitration Review, 2025)

Arbitration Fees, Expenses and Determination Controls - Al-Taani, Muhanned; Al-Majali, Tawfiq; Mosabeh, Rageh; Mayah, Yousef (Jordan Journal of Applied Science-Humanities Series, 2025)

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation, Mediation, and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation, Industrial; Officials and employees; Social justice

La mise en œuvre de la médiation institutionnelle en droit OHADA - Oueina, Florent; Oussale, Aladji Aberridjoua Aubin Hugues (Revue africaine de droit des affaires, 2025)
Il ne suffit pas d’adopter un nouvel Acte uniforme pour satisfaire à la demande ou garantir une sécurité juridique apparente du droit africain des affaires ou encore enrichir le régime uniforme du règlement des différends dans l’espace OHADA ; ou même pallier le vide législatif qui existait encore au sein de l’OHADA sur la médiation. Il ne s’agit pas d’un Acte uniforme de plus, mais d’un réel instrument juridique qui pourrait favoriser le retour des investisseurs et améliorer les conditions des affaires dans l’espace OHADA. Il faut chercher à savoir si cette nouvelle approche de la justice sera une réussite dans ledit espace.

Mediación y Arbitraje en Línea: Ventajas y Desafíos - Salguero, Katherine Coraima Guano; López, Vilma Patricia Salguero; Cáceres, Alez Remigio Escobar; Chávez, Luis Alberto Morales (Polo del Conocimiento, 2025)
La mediación y el arbitraje en línea han surgido como soluciones eficaces para la resolución de conflictos en un mundo digitalizado, ofreciendo ventajas como reducción de costos, accesibilidad y flexibilidad horaria. Sin embargo, enfrentan desafíos como la brecha digital y la seguridad de la información. Un estudio basado en encuestas a profesionales y usuarios confirma la utilidad de estas herramientas, pero subraya la necesidad de mejorar la infraestructura tecnológica y establecer marcos regulatorios claros. A pesar de los obstáculos, estos métodos representan una evolución significativa en la gestión de disputas legales.
Keywords: Arbitrage; Arbitragem; Arbitraje en línea; Arbitration; Brecha digital; Mediación; Mediation; ODR; Online dispute resolution

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

L'équité dans l'arbitrage - Djeudjo Tankeu, Ghislain (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le tribunal arbitral tranche le litige conformément aux règles de droit, mais cette garantie est fragile car le législateur OHADA ajoute à moins que les parties lui aient conféré mission de statuer en amiable composition. Ces amiables compositeurs sont donc des arbitres qui peuvent ne pas appliquer la loi, qui peuvent statuer en équité, ce qui implique la reconnaissance, aux arbitres, d’un pouvoir modérateur sur les obligations contractuelles litigieuses. Mais cette autorisation de statuer en amiable composition ne leur interdit pas de statuer en droit, simplement, le tribunal arbitral amiable compositeur qui appliquerait exclusivement les règles de droit, doit s’expliquer sur la conformité de celles-ci à l’équité. L’arbitrage tend aussi à la satisfaction de l’idéal du procès équitable. C’est ainsi que l’équité est une exigence dans la constitution et lors des suites du tribunal arbitral. The arbitral tribunal shall decide the dispute in accordance with the rules of law; but this guarantee is fragile because the OHADA legislator adds unless the parties have given him the mission to rule in amicable composition. These amicable composers are therefore arbiters who may not apply the law, who can rule in equity; which implies the recognition, to the arbitrators, of a moderating power over the disputed contractual obligations. But this authorization to rule in amicable composition does not prevent them from ruling in law. Clearly, the amicable arbitral tribunal which would exclusively apply the rules of law, must explain their compliance with fairness. Arbitration also tends to satisfy the ideal of a fair trial. This is how fairness becomes a requirement in the constitution and during the proceedings of the arbitral tribunal.

Le règlement des différends en matière d’environnement au Cameroun - Gueukam Tchako, Yannick (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La présente contribution intitulée « Le règlement des différends en matière d’environnement au Cameroun » ; vise la mise en œuvre des règles de protection de l’environnement de par l’impact des actes mis en cause ou du préjudice causé, selon l’origine des acteurs ou selon les règles invocables. Ce faisant, elle s’intéresse aux solutions qu’apportent certaines dispositions relatives à la matière environnementale au cameroun. A l’analyse, on observe dans la première hypothèse, que les modes alternatifs de règlement non contentieux des différends se veulent plus rapide et accessibles tout en favorisant le respect des lois environnementales. Dans la seconde hypothèse, il s’agit de faire appel au juge judiciaire pour trancher les différends. De par son impact, la position du juge apparaît comme l’outil essentiel d’identification des dommages susceptibles d’être causés à l’environnement et constituant le socle sur lequel est construit le plan de gestion de l’environnement. The present contribution entiled « The settlement of environmental disputes in Cameroon » ; aims at the implementation of environmental protection rules according to the impact of the acts in question or of the damage caused, depending on the origin of the impact or according to the invocable rules. In doing so, it looks at the solutions provited by certain provisions relating to environmental matters in Cameroun. On analysis, it can be observed in the first hypothesis, the alternative methods of non-contentious settlement of disputes that are intented to be faster and more accessible while promoting compliance with environmental laws. In the second hyperthesis, it is a question of appealing to the judicial judge to settle disputes. Because of its impact, the position of the judge appears to be the essentiel tool for identifying the damage likely to be caused to the environment and constituting the basis on which the environmental management plan is built.
Keywords: Différends; Disputes; Environment; Environnement; Jurisdictional settlement; MARD; Non-jurisdictional settlement; Règlement juridctionnel; Règlement non juridictionnel

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Du dessaisissement du juge étatique face à la convention d'arbitrage en droit de l'OHADA - Anciza Migani, Ryan; Mbazi, Grâce Beda; Murhula Bahati, Pacifique; Iragi Ntwali, Valéry (Studia Universitatis Babeș-Bolyai Studia Europaea, 2024)
The State Judge's Relinquishment of Jurisdiction over Arbitration Agreements under Ohada Law. The use of arbitration instead of state judges is increasingly popular in the business world. The parties to contracts thus prefer to choose a judge more quickly and less cumbersomely, with more confidentiality and less publicity. If the advantages of resorting to arbitration are undoubted, its effects leading to the total withdrawal of state jurisdictions attract the attention of many. The incompetence of the judge due to arbitration then tends to completely rule out the latter, which merits a better understanding of the powers and competence of the arbitrator and a good understanding of the place of the state judge in the arbitration procedure.
Keywords: Arbitration agreement; Convention d’arbitrage; Divestiture; Droit OHADA; Juge étatique; OHADA law; State judge

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Confidentialité, secret, protection des données et intelligence artificielle dans la procédure arbitrale - Zengue, Laurent-Fabrice (Modes Alternatifs de Règlement des Différends (MARD), Justice amiable, 2024)
L’arbitrage étant l’un des modes alternatifs de règlement des différends, sa particularité est qu’il est confidentiel, secret, rapide, conventionnel et juridictionnel. En ce qui concerne spécifiquement l’obligation de confidentialité et de secret, son étendue est double. D’abord, il y a l’étendue matérielle, qui porte sur la procédure arbitrale, la composition du tribunal arbitral, la nature du litige, les ordonnances du tribunal arbitral, les documents soumis par les parties litigantes, les délibérations et la sentence. En second lieu, il y a l’étendue personnelle, qui concerne les témoins, les parties, les arbitres, le comité d’arbitrage, l’institution ou le centre d’arbitrage, le secrétaire du tribunal arbitral, les experts et tous les autres intervenants de la procédure arbitrale. La problématique centrale est d’analyser comment la confidentialité, le secret, la protection des données personnelles, y compris dans l’hypothèse du recours à l’intelligence artificielle peut être adressée et solutionnée dans le cadre d’une procédure arbitrale.
Keywords: Arbitrage; Arbitration; Confidentialité des données; Intelligence artificielle; Protection des données

Essai sur les critères d'arbitrabilité des litiges en Droit OHADA et en Droit Français - Dizo, Kevin (Nantes Université, 2024)
Le sujet de thèse explore comment définir les critères d’arbitrabilité des litiges acceptés par la justice arbitrale et étatique en France et dans l’espace OHADA. Les recherches ont montré que chaque système juridique a déjà des critères établis par les législateurs et la doctrine. L’arbitrage, étant à la fois juridictionnel et conventionnel, implique une interaction entre les justices arbitrales et étatiques, nécessitant des critères d’arbitrabilité efficaces. Ces critères doivent distinguer clairement les litiges arbitrables des inarbitrables et repartir soigneusement les compétences entre les juridictions. Alors, notre thèse questionne l’efficacité de ces critères et propose des améliorations pour remédier à leurs limites. The thesis topic explores how to define the arbitrability criteria of disputes accepted by arbitration and state justice in France and in the OHADA space. Research has shown that every legal system already has criteria set by legislators and doctrine. Arbitration, being both jurisdictional and conventional, involves an interaction between the arbitral and state courts, requiring effective arbitrability criteria. These criteria must clearly distinguish between arbitrable and non-arbitrable disputes and carefully allocate jurisdiction between the courts. So, our thesis questions the effectiveness of these criteria and proposes improvements to remedy their limitations.
Keywords: Arbitrability; Arbitrabilité; Arbitrage (droit); Arbitration; Criteria; Critères; Droit prospectif; Effectiveness; Efficacité; Pays de l'OHADA; Prospective law

L'autonomie de la clause compromissoire en droit de l'arbitrage Marocain et Québécois: entre consécration et limites - Rafai, Khawla (Université de Montréal, 2024)
Le principe de l’autonomie de la clause compromissoire est au cœur du mécanisme de l’arbitrage, tout en demeurant complexe et polyvalent. Cette étude met en lumière les différentes dimensions de ce principe, tout en identifiant ses limites face aux exigences fondamentales de justice et d’ordre public. L’autonomie de la clause compromissoire signifie d’abord que cette clause, bien qu’intégrée dans un contrat principal, existe et survit de manière indépendante. Concrètement, cela veut dire qu’une contestation ou une invalidité du contrat principal n’affecte pas automatiquement la clause compromissoire. Cette indépendance permet aux parties de préserver leur engagement à soumettre les litiges à un tribunal arbitral, offrant ainsi une sécurité juridique et une continuité au processus de résolution des conflits. L’arbitrage repose ici sur un engagement volontaire et anticipé, qui ne saurait être remis en cause par des circonstances affectant le contrat lui-même. Au-delà de cette indépendance, l’évolution du principe d’autonomie a permis d’introduire une autre dimension : la liberté de choix dans les règles qui régissent la clause compromissoire. Cela signifie que les parties ne sont pas nécessairement liées aux règles du contrat principal. Cette forme d’autonomie favorise la flexibilité, permettant aux parties de concevoir une procédure arbitrale adaptée à leurs besoins spécifiques. Cependant, cette liberté rencontre certaines limites, notamment en matière d’ordre public, qui agit comme un rempart pour protéger les valeurs fondamentales de justice et d’équité. Un autre aspect fondamental de ce principe est son interaction avec le concept de compétence-compétence, selon lequel le tribunal arbitral est habilité à statuer sur sa propre compétence. Cette relation étroite entre les deux principes peut créer une certaine confusion, car si l’autonomie de la clause concerne sa validité et son indépendance, la compétence-compétence relève plutôt du pouvoir décisionnel des arbitres. Toutefois, ces deux notions, bien que distinctes, contribuent ensemble à garantir l’efficacité de l’arbitrage en permettant de résoudre rapidement les questions liées à la compétence et à la validité de la clause. L’étude aborde également la transmissibilité de la clause compromissoire, qui pose un défi théorique à l’idée d’autonomie. En cas de cession ou de transfert du contrat principal, la clause compromissoire accompagne généralement le contrat, ce qui semble paradoxal par rapport à son indépendance. Cette apparente contradiction s’explique toutefois par la nécessité pratique d’assurer la continuité des mécanismes d’arbitrage, en particulier dans des situations complexes comme les contrats multipartites ou les groupes d’entreprises. Enfin, le principe d’autonomie, malgré sa robustesse et son importance dans l’arbitrage, demeure encadré. La protection des intérêts fondamentaux des parties les plus vulnérables et des principes essentiels de justice impose des limites nécessaires. L’ordre public joue ici un rôle clé en veillant à ce que la liberté contractuelle ne se traduise pas par une atteinte aux droits fondamentaux ou aux valeurs essentielles de la société. En conclusion, l’autonomie de la clause compromissoire est un instrument essentiel qui garantit la stabilité et l’efficacité de l’arbitrage. Elle repose sur une double dynamique : une indépendance par rapport au contrat principal et une flexibilité permettant aux parties d’organiser librement la procédure arbitrale. Toutefois, cette autonomie doit coexister avec des limites claires pour concilier la liberté contractuelle avec les exigences de justice, assurant ainsi un équilibre nécessaire entre efficacité et protection des principes fondamentaux. The principle of the autonomy of the arbitration clause is central to the arbitration mechanism, while remaining both complex and multifaceted. This study sheds light on the various dimensions of this principle and identifies its limits in the face of fundamental justice and public policy requirements. The autonomy of the arbitration clause primarily signifies that the clause, although incorporated into a principal contract, exists and survives independently. In practical terms, this means that a dispute regarding or the invalidity of the principal contract does not automatically affect the arbitration clause. This independence enables the parties to uphold their agreement to submit disputes to arbitration, thereby ensuring legal certainty and continuity in conflict resolution processes. Arbitration thus rests on a voluntary and preemptive commitment that cannot be undermined by circumstances affecting the main contract. In addition to this independence, the development of the principle of autonomy has introduced another significant aspect: the freedom of the parties to determine the rules governing the arbitration clause. This autonomy allows the parties to deviate from the rules of the principal contract, fostering flexibility and enabling the design of arbitration procedures that meet their specific needs. However, this freedom is not without limits, particularly where public policy intervenes as a safeguard to preserve fundamental principles of justice and fairness. A crucial component of this principle is its interaction with the kompetenz-kompetenz doctrine, which empowers the arbitral tribunal to rule on its own jurisdiction. This close relationship between the two concepts may cause confusion: the autonomy of the arbitration clause concerns its validity and independence, whereas kompetenz-kompetenz pertains to the decision-making authority of arbitrators. Despite their distinctions, both principles collectively enhance the effectiveness of arbitration by facilitating the prompt resolution of jurisdictional and validity-related challenges. This study also explores the issue of the arbitration clause’s transmissibility, which presents a theoretical challenge to the notion of autonomy. In cases where the principal contract is assigned or transferred, the arbitration clause typically follows the contract, creating a seemingly paradoxical situation regarding its independence. This apparent contradiction can, however, be justified by the practical need to maintain the continuity of arbitration mechanisms, particularly in complex contexts such as multiparty contracts or corporate groups. Ultimately, despite its essential role and resilience, the autonomy of the arbitration clause is subject to necessary constraints. The protection of vulnerable parties and the preservation of fundamental principles of justice impose clear limitations. Public policy serves as a crucial safeguard to ensure that contractual freedom does not infringe upon fundamental rights or societal values. In conclusion, the autonomy of the arbitration clause is a cornerstone of arbitration’s stability and effectiveness. It is characterized by independence from the principal contract and the flexibility afforded to the parties in shaping their arbitration proceedings. However, this autonomy must be balanced against clear limits to harmonize contractual freedom with justice requirements, ensuring an essential equilibrium between efficiency and the protection of core principles.
Keywords: Arbitrability; Arbitrabilité; Arbitration; Arbitration clause; Autonomie; Autonomy; Clause compromissoire; Extension; Ordre public; Public policy; Transmissibility; Transmission

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (Global Arbitration Review, 2024)

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

Favoriser la culture du règlement amiable des différends : étude du droit béninois à la lumière du droit français - Ligan, Cyrille Sèmako (Université de Limoges, 2024)
Cette réflexion se propose de contribuer au développement des modes amiables de règlement des différends dans la culture juridique béninoise afin de permettre aux justiciables, majoritairement analphabètes, d'avoir des alternatives opportunes aux voies judiciaires classiques. Tandis que la justice fait face à de nombreux défis, aussi bien en France qu'au Bénin, le développement et la promotion remarqués des modes amiables de règlement des différends connaissent un certain succès en la matière en France. Au Bénin, le législateur encourage, incite mais ne propose aucun régime particulier pour le recours effectif au règlement amiable des différends. Cette recherche tente ainsi d'examiner de façon approfondie et d'interroger les différends mécanismes législatifs existants, tant les enjeux en termes d'accès à la justice sont considérables. Les principaux enjeux de cette thèse sont donc liées aux perspectives du développement des mode amiables et à leur encadrement pour remédier aux insuffisances et contre-performances de la justice étatique béninoise.
Keywords: Amicable settlement; Bénin / OHADA; Civil Procedure; Culture; France; Justice; MARD; Mediación; Mediation; Mediação; Médiation; Procédure civile; Règlement amiable

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Les qualités essentielles de l'arbitre en droit OHADA - Agbénoto, Koffi Mawunyo (Revue africaine de droit des affaires, 2024)

Les actualités de l'arbitrage maritime - Delebecque, Philippe (Revue africaine de droit des affaires, 2024)

Panorama critique de l’arbitrage OHADA - Ngono, Véronique Carole (Revue africaine de droit des affaires, 2024)

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

A renúncia a direitos fundamentais processuais na arbitragem: o caso particular do direito a requerer a anulação da sentença arbitral na arbitragem internacional - Teles, Joana Ataíde Cordeiro Galvão (Universidade Nova de Lisboa, 2024)
A arbitragem é um meio de resolução de litígios, que se alicerça na autonomia privada e é reconhecida, quer internacionalmente, quer nas constituições estaduais analisadas, como um modo de exercício, alternativo aos tribunais estaduais, do direito fundamental constitucional à tutela jurisdicional efetiva. A questão que se coloca é a de saber se, em primeiro lugar, as partes podem acordar renunciar, validamente, a direitos fundamentais processuais na arbitragem e, podendo, com que requisitos e dentro de que limites, para, em segundo lugar e em particular, aplicar os requisitos e limites referidos à (in)admissibilidade da renúncia ao direito a requerer a anulação da sentença arbitral na arbitragem internacional. Partindo da ponderação do âmbito, conteúdo e regime dos direitos fundamentais em confronto, de um lado, à tutela jurisdicional efetiva, incluindo o direito à arbitragem e outros direitos fundamentais processuais, como o de impugnar a sentença arbitral em determinados casos e, do outro lado, à autonomia privada, que fundamenta a renúncia, e sem prejuízo de a ponderação dever ser feita em cada caso concreto, concluo que a renúncia àqueles direitos é válida, se cumprir determinados requisitos subjetivos e objetivos, que identifico, incluindo os limites e os respetivos critérios para aferir da referida (in)validade. Quanto ao direito a requerer a anulação da sentença arbitral na arbitragem internacional, concluo que, sem prejuízo e com base nas soluções consagradas de jure constituto, a renúncia por acordo das partes é, do ponto de vista constitucional normativo e, de jure constituendo no direito português, válida, desde que se respeitem aqueles requisitos. Em particular, tem de existir um meio de impugnar a sentença arbitral, quando esta viole, de forma grave, direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, que não estão na disponibilidade das partes, nos casos e termos necessários a garantir o conteúdo essencial do direito fundamental à tutela jurisdicional efetiva. No entanto, há margem do legislador para adotar o regime mais adequado ao propósito referido. Na arbitragem internacional, do ponto de vista normativo-constitucional, podem as partes renunciar, total e/ou parcialmente, à anulação na sede, quando há a possibilidade de controlo último, pelo menos de violações graves de direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, aquando do reconhecimento e execução da sentença arbitral, sendo esta a solução legal que, na minha opinião, melhor se coaduna com a arbitragem internacional no seu todo. Arbitration is a dispute resolution mechanism rooted in private autonomy and internationally recognised, as well as in the national constitutions analysed, as an alternative means to state courts for exercising the constitutional fundamental right to effective judicial protection. The primary question of this dissertation is whether the parties can validly agree to waive fundamental procedural rights in arbitration, and if so, under what conditions and within what limits. Secondly, I specifically apply these conditions and limits to the (in)admissibility of waiving the right to seek annulment of the arbitral award in international arbitration. By weighing the scope, content and framework of conflicting fundamental rights – the right to effective judicial protection (encompassing the right to arbitration and other fundamental procedural rights, such as the right to challenge the arbitral award in certain cases), against private autonomy (which justifies the waiver) – and, without prejudice to the necessary case-by-case balancing, I conclude that the waiver of these rights is valid, provided that subjective and objective requirements, including the limits and criteria for assessing the (in)validity of the waiver, are met. Regarding the right to request annulment of the arbitral award in international arbitration, I conclude that, without prejudice to and relying on legal solutions established de jure constituto, the waiver by agreement of the parties is valid from a normative constitutional perspective and de jure constituendo under Portuguese Law, provided such subjective and objective requirements are respected. Specifically, there must be a means to challenge the arbitral award when it seriously violates fundamental procedural rights and/or public order interests of each State, which are beyond the parties’ disposal, in certain cases and under certain terms as necessary to protect the core essence of the fundamental right to effective judicial protection. However, the legislator retains discretion to adopt the most appropriate legal framework for this purpose. In the context of international arbitration, from a normative-constitutional perspective, the parties may waive annulment at the seat, in whole and/or in part, provided there is the possibility of ultimate oversight, particularly in cases involving serious violations of fundamental procedural rights and/or public order interests of each State at the stage of recognition and enforcement of the arbitral award. In my opinion, this legal solution is the one that best aligns with the global system of international arbitration.
Keywords: Annulment; Anulação; Arbitragem; Arbitragem Internacional; Arbitration; Autonomia Privada; Direitos Fundamentais Processuais; Fundamental Procedural Rights; International Arbitration; Private Autonomy; Renúncia; Waiver

L'amiable au service du sauvetage de l'entreprise en difficulté en droit OHADA : la médiation et la conciliation - Toe Adouabou, Laure (Revue africaine de droit des affaires, 2024)
L’acte uniforme originel sur les procédures collectives avait prévu une procédure préventive, le règlement préventif, au bénéfice des débiteurs qui traversent des difficultés sérieuses. La nécessité de la consécration d’une procédure à la fois amiable et préventive s’est imposée. C’est désormais chose faite depuis la révision de 2015. Le législateur a ainsi consacré les procédures de conciliation et de médiation à l’article 2-1 de l’Acte uniforme sur les procédures collectives d’apurement du passif (AUPC). Si pour la mise en œuvre de la première, il faut se référer à l’AUPC, la deuxième est règlementée dans l’Acte uniforme sur la médiation (AUM). Nous proposons donc dans cette étude, à la suite de la présentation de ces procédures amiables comme modes anticipatifs et efficaces de sauvetage d’entreprises, des pistes de réflexion afin de rendre effectif le recours à cet arsenal juridique.

L’autorité de la chose jugée dans l’arbitrage OHADA - Toe, Souleymane (Revue africaine de droit des affaires, 2024)

Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (10th Kuwait International Law School annual international academic conference (KILAW 2024), 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring,  as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

L'agence de régulation des télécommunications au Cameroun : un centre d'arbitrage d'une nature particulière - Silabing Ouethy, Jasmine Diane (Revue africaine de droit des affaires, 2024)
La Procédure de règlement des différends opposant les opérateurs de communications électroniques au Cameroun prévoit, en premier, la saisine de l’Agence de Régulation des Télécommunications (ART). Cette dernière devra tenter de concilier les parties. Si cette tentative de conciliation échoue, alors le dossier sera transmis au Comité de Règlement des Différends (CRD) qui devra trancher le litige. Au cas où la décision intervenue est contestée par une des parties, elle pourra saisir soit les juridictions de droit commun, soit l’arbitre. Cependant, le législateur de 2010 n’a pas résolu toutes les questions relatives à l’intervention de cet arbitre. Par exemple, qui le constitue ? Quelles règles gouvernent la procédure et sur la base de quelles normes doit-il trancher ? Où aura lieu l’arbitrage ? L’examen de la loi de 1998 qui a été abrogée par celle de 2010, plus explicite sur la question, nous livre un régime qui tantôt rapproche le régulateur d’un centre d’arbitrage sur certains aspects, tantôt l’éloigne sur d’autres.

L'adaptabilité de l'arbitrage OHADA au contexte africain - Zakari, Amadou Hamani (Revue africaine de droit des affaires, 2024)
Le règlement des différends par les parties à une relation d’affaires, à travers l’arbitrage, n’est pas un fait nouveau dans les pays africains. Seulement, la nécessité était posée d’adapter ce mode alternatif aux réalités économiques africaines. Pendant longtemps, la majeure partie des contentieux dans lesquels les parties africaines sont impliquées, était réglée en dehors de ses frontières. Ce qui ne favorisait pas leur participation active. Mais la mise en place de l’OHADA et surtout, la création de la CCJA et plus tard son Centre d’arbitrage, suivis par les différents Centres d’arbitrage des Etats ont permis de faire de l’effectivité de l’arbitrage, une réalité. De l’arbitrage traditionnel, l’OHADA, a élargi le champ d’application de ce droit, en y incluant l’arbitrage des investissements, à l’occasion de la réforme du 23 et 24 novembre 2017. Actuellement, cette réforme fait l’objet de nombreuses critiques, notamment, sur le fait que pour certains, ce mécanisme favorise plus l’investisseur étranger que l’Etat partenaire, et que la notion même de l’investissement, n’a jusque-là pas fait l’objet d’une définition claire, tant en droit, en jurisprudence encore moins en doctrine. Pour mettre en œuvre l’arbitrage, les parties font recours à des arbitres, auxquels elles confient leurs différends suivant une convention d’arbitrage ou un instrument d’investissement qui détermine leur mission. Cette dernière peut être accomplie selon les cas, sous la forme d’un arbitrage institutionnel ou ad hoc, et finira par une sentence arbitrale, qui tranchera ce conflit. Comme dans la justice étatique, cette sentence est susceptible des voies de recours. L’arbitrage ne va pas sans écueils : de la constitution du tribunal arbitral à la sentence finale, plusieurs difficultés peuvent surgir.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document.  The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Règlement d'arbitrage : En vigueur à compter du 15 janvier 2024 - Centre régional du Caire pour l’arbitrage commercial international (CRCICA, 2024)

التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

La mediación y la cultura del acuerdo - Lagones, Delcy de Anglim (Deconstruyendo la justicia, 2024)
Keywords: China; Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018); UNCITRAL Model Law on International Commercial Conciliation (2002)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

La bonne administration de la justice arbitrale en droit OHADA - Megou Ebock, Jocelyne Yvonne (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La résolution d’un litige passe généralement par la justice étatique habilitée à faire appliquer les lois, à corriger et réparer les injustices subies. Rendre justice suppose que certains moyens soient réunis afin de garantir une bonne administration de la justice. Mais de plus en plus la justice étatique est concurrencée par une forme de justice ayant pour principaux acteurs les parties : il s’agit de la justice arbitrale. Cette forme de justice semble être la parfaite incarnation d’une bonne administration de la justice dans la mesure où elle renvoie à un emploi équilibré des moyens de justice en conformité avec les objectifs de célérité de la justice arbitrale. Justice rendue sur la base d’une convention d’arbitrage, la justice arbitrale s’accommode bien du respect des exigences d’un procès équitable et garantie la bonne administration de la justice. S’agissant de la bonne administration de la justice arbitrale OHADA, tout parait plus simple dans la mesure où le législateur en a fait un mode privilégié de règlement des différends contractuels et un instrument juridique adapté aux exigences d’une justice de qualité. Ainsi, la préoccupation majeure de cette étude est celle de savoir dans quelle mesure la justice arbitrale pourrait être considérée comme la « pierre philosophale » de la bonne administration de la justice arbitrale en droit OHADA. C’est à travers l’analyse d’un corpus juridique entièrement rénové le 23 novembre 2017 que la justice arbitrale est considérée comme la pierre angulaire de la bonne administration de la justice. Ceci se justifie par la double assertion selon laquelle elle respecte les principes généraux de bonne administration de la justice et qu’elle demeure une justice ancrée sur le respect des principes spécifiques à la justice arbitrale.
Keywords: Administration; Arbitrage; Arbitragem; Arbitration; Arbitre; Good administration; Justice; Proceeding; Procès équitable

Jus Mundi Arbitration Review - Mistelis, Loukas; Fan, Kun (JMAR, 2024)
Articles The Seven Cardinal Sins of Investment Dispute Settlement Investment Arbitration in the New Era: Engine or Obstacle in the Fight Against Climate Change? The UNIDROIT Principles as a Tool for the Internationalisation of Contracts by Arbitral Tribunals AI: The Modern Tribunal Assistant – Impact on Enforceability of Arbitral Awards under the New York Convention Automation & Augmentation: Artificial Intelligence in International Arbitration The IBA Guidelines on Conflicts of Interest in International Arbitration 2024 CIETAC: Overview of Dispute Resolution in the Digital Environment in China Swiss Supreme Court rejects CJEU’s Komstroy ruling Romania’s Supreme Court Decides that Associations and Foundations Based in Romania Can Only Set Up Arbitral Institutions if Authorized by Law Book Review – On Arbitration: V. V. Veeder QC, Selected Writings and Contributions to the Development of Law (Wordsworth & Veeder (eds), OUP 2023) Book Review – Investment Arbitration and Climate Change (Ipp & Magnusson (eds), Kluwer 2024)

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

La compétence du for de situation de l’immeuble face aux conventions de juridictions - Tchouankeu Djeuda, Claudia (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
L’admission d’une maitrise par les parties de la compétence internationale par des clauses de juridictions ; notamment des conventions d’élection de for, des conventions d’arbitrage ou de médiation, amène à s’interroger sur l’efficacité réelle de ces accords. Pour ce qui est de la matière immobilière, le fort attachement de l’Etat aux questions de territoire et les considérations de proximité entre litige et le for du situs ont pour effet d’empêcher toute dérogation à la compétence directe du for de situation de l’immeuble ; tant lorsque l’immeuble est situé sur le for du juge saisi que lorsqu’il est situé à l’étranger. Toutefois, l’observation d’un possible fléchissement de l’exclusivité de ce critère de compétence conduit à un plaidoyer en faveur de l’efficacité, quoique encadrée, des conventions juridictions en la matière.
Keywords: Autonomie de la volonté; Autonomy of will; Compétence internationale des juridictions; Convention de juridiction; Immovable property’s location; International jurisdiction; Jurisdiction agreement; Lieu de situation de l’immeuble; Matière immobilière; Real estate matters

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Arbitrage et modes amiables de règlement des conflits - Clay, Thomas (Recueil Dalloz, 2023)
Le hasard a voulu que la décision qui a été distinguée comme la plus importante de l’année 2023 corresponde à un arrêt annulant une sentence rendue par un tribunal arbitral que présidait l’auteur de ces lignes. Les usages académiques interdisant de commenter un tel arrêt, il sera renvoyé aux innombrables publications dont il a déjà fait l’objet (JCP E 2023. 1061, note D. Mainguy ; JCP 2023. 507, note D. Mouralis ; D. actu. 14 mars 2023, obs. J. Jourdan-Marques ; Rev. arb. 2023. 423, note F.-X. Train ; RTD com. 2023. 582, obs. E. Loquin ; Cah. arb. 2023. 501, note M. Henry ; Gaz. Pal. 16 mai 2023, p. 12, obs. L. Larribère ; JCP 2023. 221, § 4, obs. P. Giraud ; Lexis®PSL, 27 janv. 2023, obs. M.-L. Cartier et A. Meyniel ; Paris Baby Arbitration 2023, n° 59, p. 9, obs. G. Ghedjati et M. Villeneuve ; IA Reporter 12 janv. 2023, obs. L. Bohmer ; Global Arbitration Rev. 13 janv. 2023, obs. A. Ross), ayant même eu les honneurs de l’Agence France Presse (AFP) dans une dépêche du 20 janvier 2023 et… du Canard enchaîné (18 janv. 2023, p. 3). Les commentaires de doctrine sont d’ailleurs très majoritairement critiques sur cet arrêt inattendu, parfois avec des nuances, en dehors d’un seul, celui publié à la Revue de l’arbitrage, qui suit une approche univoque si singulière qu’elle interroge sur les motivations réelles de l’auteur : un professeur de droit ne devrait pas écrire ça. Il n’en reste pas moins que cet arrêt, aussi remarqué qu’il fût, ne sera donc pas commenté dans ces colonnes. Mais, pour que soit moins iconoclaste le paradoxe d’un panorama de droit de l’arbitrage qui n’évoque pas la décision la plus remarquée de l’année en droit de l’arbitrage, encore fallait-il qu’il en fût fait mention dans cet éditorial, lieu d’une licence académique plus libre, sous peine de laisser croire à une auto-censure, voire à une gêne du soussigné, qui, au contraire, assume pleinement d’user de sa liberté d’expression en toutes circonstances.
Keywords: Arbitrage; Arbitration; Convention d'arbitrage; Sentence arbitrale

La distinction entre recours en annulation et exequatur en droit français de l'arbitrage international - Alain, Alex (Université Paris 1, 2023)
S’interroger sur la distinction entre le recours en annulation et exequatur, c'est poser la question du régime juridique applicable à chacun de ces mécanismes de contrôle de la sentence arbitrale. Ces derniers paraissent, par hypothèse, différenciés puisqu’ils relèvent de deux catégories de procédures que le droit français ne confond pas : les voies de recours et l’exequatur. L’application des règles du droit processuel français commande donc en principe de ne pas confondre le recours en annulation, qui est une voie de recours, avec l’exequatur. Or, s’il est bien une notion qui innerve tous les pans du droit français de l’arbitrage international, c’est celle d’« autonomie ». Il en résulte que malgré la référence expresse à des notions bien connues du droit commun - i.e 1’exequatur et la voie de recours pour le recours en annulation -, celles-ci paraissent recevoir une acception spéciale en droit français de l’arbitrage international. Gommant les différences qui séparent traditionnellement les voies de recours de l’exequatur, le droit français de l’arbitrage international semble à bien des égards confondre le recours en annulation et l’exequatur. Émerge ainsi l’idée que les sentences arbitrales font l’objet d’une procédure de contrôle unique. Une confusion certaine entre le recours en annulation et l’exequatur existe en droit français de l'arbitrage international, elle est à l’origine de nombreuses incertitudes. Pour remédier à ce constat, l’étude propose l’application aux sentences arbitrales des règles du droit commun, relatives aux voies de recours et à l’exequatur.
Keywords: Action for annulment; Arbitrage international; Civil Procedure; Contrôle de la sentence arbitrale; Distinction; Droit international privé; Exequatur; International Arbitration Law; Jugements étrangers; Private International law; Procédure civile; Recours en annulation; Voie de recours; Voies d'exécution

Le développement du recours aux modes amiables en matière civile : étude comparée entre la France, les Etats-Unis et le Canada - Watrin, Geoffrey (Université de Strasbourg, 2023)
Darwin disait que « les espèces qui survivent ne sont pas les espèces les plus fortes ou les plus intelligentes, mais celles qui s’adaptent le mieux aux changements ». La justice n’échappe pas à cette règle. Sans cesse confrontée à de nouveaux défis, tels que l’encombrement judiciaire ou la pacification des relations entre les parties, cette dernière va devoir trouver les moyens qui lui permettront de fonctionner en accord avec les besoins de son temps. Les modes amiables de résolution des conflits pourraient bien en faire partie. Implantés de longue date et particulièrement appréciés aux États-Unis et au Canada, ces derniers semblent pour l’heure boudés par les praticiens et les justiciables en France. Le législateur montre néanmoins un intérêt de plus en plus important pour ces méthodes et pour cause : elles ont fait leurs preuves Outre-Atlantique. Dès lors, comment parvenir à les développer au sein de notre système ? C’est la question à laquelle nous essayerons de répondre dans cette thèse.
Keywords: ADR; Canada; Development; Droit comparé; Développement; France; MARC; Mediation; Modes amiables; Médiation; Procédure civile; United States; États-Unis

La mediación y el arbitraje laboral en el Procedimiento concursal: regulación y dificultades aplicativas - Dormido Abril, Julia (Trabajo, Persona, Derecho, Mercado: Revista de Estudios sobre Ciencias del Trabajo y Protección Social, 2023)
La declaración de concurso de una empresa no solo va a afectar al deudor concursado, pues tal calificación también tiene un efecto directo sobre los trabajadores. Sobre todo, si en el seno de un procedimiento concursal, para salvar la continuidad de la actividad empresarial, se decide adoptar alguna medida de reestructuración, tal y como pueden ser las modificaciones sustanciales de las condiciones de trabajo, el traslado, el despido, la suspensión de contratos o la reducción de jornada por causas económicas, técnicas, organizativas o de producción. Las decisiones que sobre cualquier de éstas se tomen pueden dar lugar a conflictos que tienen que solucionarse mientras el proceso judicial sigue su curso. Por ello, el legislador ha incorporado la mediación y el arbitraje en la norma mercantil como vías de solución extrajudicial de tales conflictos. Se trata de una fórmula jurídica no exenta de interrogantes, relacionados en este caso con aspectos como, la norma aplicable a tales mecanismos de solución extrajudicial, la incorporación de la solución al auto o el modo en el que impugnar el acuerdo o el laudo en materia laboral. The declaration of insolvency of a company will not only affect the insolvent debtor, as such a classification also has a direct effect on the employees. Particularly if, within the context of an insolvency procedure, in order to save the continuity of the business activity, it is decided to adopt any restructuring measure, such as substantial modifications to working conditions, relocation, dismissal, suspension of contracts or reduction of working hours for economic, technical, organisational or production reasons. The decisions taken on any of these may give rise to conflicts that have to be resolved while the judicial process is still underway. For this reason, the legislator has incorporated mediation and arbitration into commercial law as a means of extrajudicial settlement of such disputes. This is a legal formula that is not free of questions, related in this case to aspects such as the rule applicable to such out-of-court settlement mechanisms, the incorporation of the solution into the or-der or the way in which to challenge the agreement or award in labour matters.

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Chronique de jurisprudence de droit de l’arbitrage - Larribère, Lilian (Gazette du Palais, 2023)
Dans la période récente, de nombreuses précisions viennent affermir le régime procédural des recours portés devant le juge français du contrôle. Ainsi, de l’article 1520 du Code de procédure civile qui ne liste que les griefs portant sur la sentence arbitrale elle-même, et qui autorise donc à se prévaloir des moyens d’irrecevabilité de la requête d’exequatur (Cass. 1re civ., 13 avril 2023, n° 21- 50053). Ainsi encore, de l’irrecevabilité du recours en annulation qui n’emporte pas exequatur de la sentence arbitrale (Cass. 1re civ., 7 juin 2023, n° 22-12757). On notera également les arrêts nombreux portant sur le régime de la convention d’arbitrage, et partant de la compétence arbitrale. Enfin, l’arrêt rendu par la Cour de Strasbourg dans l’affaire Semenya (CEDH, 11 juill. 2023, n° 10934/21, Semenya c/ Suisse) montre que le contrôle des droits fondamentaux devra être mené de manière scrupuleuse par le juge de l’annulation, et ce, même si la situation litigieuse ne présentait guère de liens avec les États parties à la CEDH.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contentieux para-arbitral; Contentieux post-arbitral; Jurisprudence arbitrale

Les modes alternatifs de traitement des conflits familiaux : étude comparative des droits français et ivoirien - Ouattara, Tiégolo Fougniguéta (Université de Bordeaux, 2023)
La famille se fonde sur des liens qui ne sont pas nécessairement rompus par l'existence d'un conflit. De ce fait, la résolution des conflits familiaux nécessite l'usage de méthodes favorisant la restauration des relations familiale ou un vivre ensemble harmonieux entre les membres de la famille. Dans cette perspective, en droit français et ivoirien, les systèmes traditionnels de résolution des conflits familiaux étaient partagés entre la méthode amiable et la méthode judiciaire. En droit français, ce partage s'observe durant la période de l'Ancien régime et la période révolutionnaire. En droit ivoirien, cela s'observe durant la période coloniale. Cependant, dans ces deux ordres juridiques, dans le cadre légal, la méthode amiable a été reléguée au second plan au profit de la méthode judiciaire. Toutefois, ces dernières années, face au besoin de réduire la charge de travail du juge, d'apporter des solutions aux conflits dans des délais raisonnables et d'adapter la résolution des conflits à la conception sociale de la justice, se développent les modes alternatifs. Ceux-ci regroupent un ensemble de mécanismes ayant pour objet la résolution amiable des conflits. Le développement de ces modes varie d'un pays à l'autre. En France, ils font l'objet d'un développement accru. En Côte d'Ivoire leur développement est timide. Néanmoins, des méthodes similaires aux modes alternatifs sont utilisées par le justiciable ivoirien pour la résolution des conflits familiaux, mais dans un cadre informel. Eu égard à l'attachement du justiciable ivoirien à la justice informelle, aussi qualifiée de justice traditionnelle, se manifeste un besoin de sa reconnaissance légale. La justice traditionnelle ivoirienne étant par principe amiable tout comme les modes alternatifs, le développement de ces modes dans la législation familiale ivoirienne pourrait se faire dans le cadre d'une conciliation des règles les régissant avec celles régissant la justice traditionnelle ivoirienne. Mais cette conciliation devrait être faite en tenant compte des limites des modes alternatifs observées grâce à l'expérience française de ces mécanismes et des réalités sociales ivoiriennes. The family is founded on ties that are not necessarily broken by the existence of conflicts. Therefore, resolving family conflicts requires the use of methods that promote the restoration of family relationships or a harmonious living together among family members. In this regard, under French and Ivorian law, traditional systems for resolving family conflicts were divided between the amicable method and the judicial method. In French law, this division can be observed in the periods of the Old Regime and the Revolution. In Ivorian law, this can be observed during the colonial period. However, in both legal systems, the amicable method failed from a legal point of view in favor of the judicial method. This failure was due to the litigant and the legislator. However, in recent years, faced with the need to reduce the judge's workload, provide solutions to conflicts in reasonable timeframes, and adapt conflicts resolution to the social conception of justice, alternative methods of resolution are developed. These comprise a set of mechanisms aimed at amicably resolving conflicts. The development of these methods varies from one country to another. In France, they are subject to increased development. In Côte d'Ivoire, their development is modest. Nevertheless, similar methods to alternative modes are used by Ivorian litigants for the resolution of family conflicts, but in an informal setting. In view of the Ivorian litigants' attachment to informal justice due to the fact that it represents Ivorian traditional justice, there is a need for its legal recognition. Since Ivorian traditional justice is amicable by nature, just like alternative modes, the development of these methods in Ivorian family legislation could take place within the framework of a reconciliation of the rules governing them with those governing Ivorian traditional justice. However, this reconciliation should take into account the limitations of alternative modes observed through the French experience of these mechanisms and ivorian social realities.
Keywords: Alternative modes; Comparative law; Conflicts; Conflits; Côte d'Ivoire; Différends; Disputes; Droit; Droit comparé; Famille; Famille (droit); Family law; France; Justice traditionnelle; Litigation; Litiges; Modes alternatifs; Médiation familiale; Règlement de conflits; Traditional justice

Justice civile amiable, justice pénale négociée... vers une justice consensuelle ? (Revue Justice Actulaités, 2023)
Keywords: Conciliation; Conciliação (processo civil); Consentement; Justice amiable; Justice négociée; Médiation; Politique de l'amiable; Procédure pénale

Arbitrabilidade objetiva em contratos administrativos - Cardoso, Paula Butti (Universidade de São Paulo, 2023)
A Lei n° 9.307, de 1996, a Lei de Arbitragem, com a redação que lhe foi dada pela Lei n° 13.129, de 2015, passou a prever expressamente que a Administração Pública direta e indireta poderá utilizar-se da arbitragem para dirimir conflitos relativos a direitos patrimoniais disponíveis. Ultrapassadas as discussões em torno da arbitrabilidade subjetiva, a arbitrabilidade objetiva das disputas envolvendo a administração pública ganha papel de destaque. Divergências a respeito do que seriam os direitos patrimoniais disponíveis da administração pública faz com que a questão seja frequentemente levada ao poder judiciário, em atentado a valores informadores da arbitragem, como a segurança jurídica e a celeridade. Daí a necessidade de se buscar solução para a questão, o que pode ser feito a partir do direito administrativo contemporâneo, que valoriza cada vez mais a atuação consensuada em detrimento da atuação unilateral e impositiva da administração pública. Law No. 9,307, of 1996, the Brazilian Arbitration Law, amended by Law No. 13,129, of 2015, expressly provides that the direct and indirect public administration may use arbitration to resolve conflicts relating to renounceable patrimonial rights. Discussions relating to arbitrability regarding the parties in arbitration have given place to discussions regarding subject-matter arbitrability relating to disputes involving public administration. Different understandings about the renounceable patrimonial rights of the public administration frequently take the discussion to be ruled by judiciary courts, jeopardizing values that inform arbitration, such as legal certainty and celerity. The current scenario demands that a solution to the issue is provided. That can be done based on modern administrative Brazilian law, which increasingly values consensual action rather than unilateral action by public administration.
Keywords: Administrative contract; Administrative law; Arbitrabilidade objetiva; Arbitrability; Arbitrage; Arbitragem; Arbitration; Consensualidade; Consensuality; Contrat administratif; Contrato administrativo; Direito administrativo; Droit administratif

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (2023 TIAC Journal of international dispute settlement inaugural annual conference (TJIDS 2023), 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

L'unification des pratiques de médiation et de conciliation dans les pays membres de l'OHADA - Dah, Sègla Septime (Université de Toulon, 2023)
L’unification des pratiques de médiation et de conciliation s’inscrit dans une démarche centrée sur l’activité du médiateur ou du conciliateur et présente un intérêt double. D’une part, elle forge l’action du médiateur ou du conciliateur en répertoriant les critères afin d’instituer un référentiel qualité. Ce dernier servira à évaluer ses bonnes pratiques du médiateur ou du conciliateur. L’unification desdites pratiques n’entend pas instituer une bonne pratique de la médiation ou de la conciliation. Elle prône pour une identification desdites pratiques afin de constituer un socle commun à l’action et aux prestations de tous les médiateurs des pays membres de l’OHADA. D’autre part, elle est garante du droit à un médiateur compétent et de l’accès à un processus de résolution des conflits de qualité pour une médiation efficace. Le droit à un médiateur compétent et l’accès à un processus de résolution des conflits de qualité sont les deux composantes essentielles du recours effectif à la justice amiable en droit OHADA. Ce recours découle d’un droit de la médiation et de la conciliation qui est en codification dans les pays membres de l’OHADA. Ladite codification est un préalable à cette démarche d’unification. Ainsi, la construction du droit de la médiation et la conciliation doit être accompagnée d’une réelle politique d’unification des pratiques de médiation et de conciliation afin d’inscrire le recours à l’amiable dans l’habitude des justiciables.
Keywords: Amicable settlement; Appeals; Conciliation; Droit de l’amiable; Effectif; Effective; Efficace; Efficient; Evaluation; Justice; Justiciables; Litigants; MARD; Mediation; Médiation; Médiation internationale; Organisation pour l'harmonisation en Afrique du droit des affaires; Quality standards; Recours; Référentiel qualité; Unification; Évaluation

L’intervention du juge étatique dans l’arbitrage de l’Organisation pour l'Harmonisation du Droit des Affaires en Afrique (OHADA) : Une carence normative du droit communautaire - Fofana, Modibo Mohamed; Diallo, Hamadi (International Journal of Strategic Management and Economic Studies (IJSMES), 2023)
Les attributions du juge étatique sont confrontées à un flou juridique qui en résulte l’absence d’un régime juridique claire. A l’issue de cette réflexion, il convient de retenir que l’intervention du juge étatique à l’arbitrage dans l’espace OHADA est une œuvre particulièrement complexe car, si dans l’arbitrage spécifique de la CCJA, Il revient au juge communautaire la charge d’administrer la procédure et d’assurer le suivi durant la phase post-arbitrale, la détermination du juge étatique dans l’arbitrage de droit commun est une opération complexe et ses attributions ne sont pas claires. En effet, le flou lexical entourant l’expression générique désignant le juge étatique, entraîne un morcellement de son champ de compétence. Ce sont ses faiblesses qui justifient que des palliatifs soient proposés en vue de renforcer l’efficacité de l’intervention du juge national et de garantir par la même occasion la sécurité juridique dans l’espace OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration; Juge communautaire; Juge d’appui; Juge étatique; OHADA

La transformation du Système de résolution des conflits entre État hôte et investisseur étranger : la conciliation des intérêts d’acteurs d’un système adaptatif complexe - Deligny Malchair, Marion (Université de Lorraine, 2023)
Les conflits entre État hôtes et investisseurs étrangers occupent, depuis une dizaine d’année le devant de la scène géopolitique. Le questionnement se porte aujourd’hui de façon globale sur l’articulation des méthodes de règlement de conflits particulièrement complexes en raison de leurs implications institutionnelles, juridiques et économiques. Cette thèse se consacre à appréhender le cadre de règlement des conflits d’investissements selon le modèle du système afin de déterminer les conditions nécessaires à la transformation profonde du Système de résolution des différends entre États-hôtes et investisseurs.L’analyse du Système de résolution des différends entre États-hôtes et investisseurs suppose d’abord d’en restituer le contexte historique et d’examiner les bases institutionnelles posées par le système CIRDI, celui-ci étant le fruit d’une idée, la substitution du droit à la force pour la résolution des différends d’investissement : « le paradigme juridictionnel ». Or, si des bases institutionnelles avaient été posées, celles relationnelles ne l’étaient pas. Il s’en suit un usage des mécanismes du Système de résolution des différends entre États-hôtes et investisseurs dans une logique défensive et adversariale. Cependant, la complexification croissante du monde et incidemment du système des investissements, conduit les acteurs de l’investissement à passer d’une logique adversariale à une logique de collaboration et de co-construction pour résoudre les inévitables problématiques auxquelles ils font face : « le paradigme consensuel ».Nous nous interrogeons alors sur les conditions nécessaires à la mise en œuvre de ce nouveau paradigme comme fondement du Système afin d’en provoquer la transformation profonde. L’application de concepts issus du champ d’étude de la complexité et des systèmes adaptatifs complexes permet de conclure que le consensualisme est tout à la fois le résultat et le moyen à mettre en œuvre pour faciliter cette transformation. Seule une démarche holistique, incluant l’ensemble des acteurs dans leur diversité, peut permettre de faire émerger des solutions innovantes à la hauteur des enjeux. Notre proposition est d’utiliser les outils et méthodes du Design Thinking appliqués au droit – le Legal Design- dont la démarche place les parties prenantes, et donc les éléments de culture et de contexte, au cœur du processus de conception de solutions, et susceptible de provoquer un changement dans la dynamique relationnelle des acteurs vers une logique de collaboration. Cette conclusion s’applique aux deux échelles retenues : celle de la transformation globale du Système de résolution des différends entre États-hôtes et investisseurs, et celle des projets d’investissement, dont une gouvernance participative doit être encouragée afin d’en permettre le succès et de permettre de réaliser une des vocations premières du système des investissements qu’est le développement des États d’accueil au bénéfice de leurs communautés. Conflicts between host states and foreign investors have been at the forefront of the geopolitical scene for the past ten years. Now the question is being raised on a global scale concerning the articulation of particularly complex conflict resolution methods because of their institutional, legal and economic implications. This thesis focuses on understanding the framework for resolving investment disputes based on the system model in order to determine which conditions are necessary for the profound transformation of the Dispute Resolution System between host states and investors.Before any analysis of the Dispute Resolution System between host states and investors can be undertaken, it is necessary to provide an insight into the historical context and to examine the institutional foundations of the ICSID system. These are the result of an idea, substituting international law to the use of force for the resolution of investment disputes: “the jurisdictional paradigm”. If institutional foundations were laid, relational ones were not. This resulted in the use of the Dispute Resolution System mechanisms between host states and investors in a defensive and adversarial logic. However, the increasing complexity of the world and, incidentally, of the investment system, has led investment players to move from an adversarial logic to one of collaboration and co-construction in order to resolve the inevitable problems they face: “the consensual paradigm”.We then question the conditions required for the implementation of this new paradigm as the foundation of the System in order to bring about its profound transformation. Applying concepts from the fields of study into complexity and complex adaptive systems leads to the conclusion that consensus constitutes both the outcome and the means to facilitate this transformation. Only a holistic approach, including all the actors involved and their diverse contexts, can make it possible to develop innovative solutions that meet these challenges. Our proposal is to apply Design Thinking tools and methods in a legal context – Legal Design. This approach places stakeholders, and therefore the elements of culture and context, at the heart of the process of designing solutions, and is therefore well suited to bringing about a change in the relational dynamics of the actors towards a logic of collaboration. This conclusion applies to both scales: that of the overall transformation of the Dispute Resolution System between host states and investors and that of investment projects, whose participative governance structure must be recognized as a crucial success factor and a means to support one of the primary purposes of the investment system, which is the development of host states for the benefit of their communities.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Complex Adaptive System; Dispute System Design; Droit international; Foreign investment; Investissements étrangers; Investment Conflits Resolution; Investment Mediation; Legal Design; MARD; Mediación; Mediation; Mediação; Médiation; Médiation d'investissement; Règlement de conflits; Résolution des conflits d'investissement; Système adaptatif complexe

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

Reconstruction of CCMA Commissioners' Perceptions of Dispute Resolution in South Africa: a multi-perspective approach - Bendeman, H. M. A. (Potchefstroomse Univèrsiteit vir Christelike Hoër Onderwys, 2023)
A reconstruction of CCMA commissioners' perceptions of dispute resolution in South Africa: A multi-perspective approach This study focuses on the problems in the dispute resolution system in South Africa. The aim of this study is to explore the perceptions of commissioners of the Commission for Conciliation, Mediation and Arbitration (CCMA) regarding the capacity of parties to effectively deal with labour .conflict and disputes within the legal framework provided by the Labour Relations Act (LRA) (66/95). This includes an investigation into the reasons for the high referral rate of unfair dismissal cases to the CCMA and the influence of the case-overload on the effective functioning of the disputé resolution system. The · functionalist and conflict theoretical perspectives are used to study the structural aspects of the dispute resolution system and to explore structural strain. The interactionist perspective is used in the methodology of this study to reconstruct the perceptions of a group of CCMA commissioners. This study is predominantly of a qualitative nature and was conducted in an exploratory manner through in-depth interviews and e-mail questionnaires. Dunlop's open systems approach allowed for the conceptualisation of the major dispute resolution components of the labour relations system. T!Je analysis of the transformation of conflict formed the basis for understanding the background, the problem statement, the aims and assumptions of this study. lt was found that the guidelines in Schedule eight of the LRA (66/95) have become the norm for dealing with conflict within an enterprise, creating complex and technical processes for dealing with disputes. However, most of the employers and individual employees do not have the knowledge and skills to operate effectively in the system. This has led to a new type of adversarialism in the individual employment relationship, which is based on rights, rules and power. The very technical nature of the internai conflict resolution mechanisms, the incapacity of the parties and the adversarial nature of the labour relationship have resulted in the high referral rate and consequent problems that the CCMA is experiencing.
Keywords: Afrique du Sud; Arbitrage; Arbitragem; Arbitration; Conciliation; Conflict resolution; Conflits de travail; Dispute settlement; Industrial sociology; Labour dispute; Labour relations; MARD; Mediación; Mediation; Mediação; Médiation; Relations de travail; Règlement des différends; Résolution de conflit; Sociologie industrielle; South Africa

La pérennité du contrat international entre pacta sunt servanda et rebus sic stantibus : réflexions au regard du pouvoir interprétatif de l’arbitre - Bejeoui, Imed (UAEU Law Journal, 2023)

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

L’immunité des arbitres dans l’arbitrage OHADA - Diallo, Hamadi; Traoré, Abdramane; Traoré, Abdou Bougoury (International Journal of Strategic Management and Economic Studies, 2023)
Cet article, est une contribution à la réflexion sur le statut de l’arbitre en droit OHADA, entamée par plusieurs chercheurs africains, et au centre de laquelle se trouve la problématique de l’immunité en droit de l’arbitrage OHADA. Le débat sur le choix d’un système d’immunité et la définition d’un véritable statut pour l’arbitre est toujours d’actualité. Cet article fait le point global des approches et conceptions sur l’immunité diplomatique des arbitres de la CCJA. En effet, le débat sur la responsabilité touche de façon étroite celui du statut de l’arbitre : la responsabilité étant la résultante d’un statut, cela nous permettra d’aborder la question du statut juridique de l’arbitre en droit OHADA. Dans un contexte où les différentes législations, la jurisprudence ou encore les conventions internationales, n’abordent que très peu le statut de l’arbitre, la détermination des éléments permettant de préciser les contours des devoirs, droits et obligations de l’arbitre, contribuera de façon certaine à mieux appréhender la mission de l’arbitre.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitre; CCJA; Immunité; OHADA

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

L’ouverture du droit d’agir au système des règlements alternatifs des différends en droit OHADA et Camerounais : un procédé séduisant mais d’une efficacité incertaine - Njock, Luc Kevin Leny (Uniform Law Review, 2023)
The processes by which a model of social regulation channels its way of resolving conflicts make the strength of its conflict resolution system. Court justice has lost its exemplary function. The crisis of effectiveness and the crisis of legitimacy that the processual mode of dispute resolution is undergoing in our States, make it a justice system that is considered to have broken down. The need for justice thus directly raises the question of social regulation, the relevant model of social regulation. The call for a ‘right to sue’ open to the system of alternative dispute resolution rather than restrictively to the judiciary to resolve disagreements is the spearhead of the combinatorial approach to the administration of conflicts, the ferment of a plural approach to access to justice. Has Cameroonian law begun to renew its vision of the right to take legal action? Does it renew the dominant classical approach to the system of social regulation? The study notes the global and integral recognition of the alternative dispute resolution system, another, less contentious, way of dealing with disputes, the emergence within the traditional dispute resolution system of a right to amicable dispute resolution, but in an embryonic state. It then poses, in a prospective approach, the need for a unitary and global approach to private justice as challenges to be met to ensure the quality of this form of justice.

L'Arbitrage en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Le recours à l’arbitrage en matière des litiges contractuels entre des parties privées présente des avantages par rapport aux procédures devant les tribunaux. Les avantages de l’arbitrage qui a une valeur particulière en matière contractuelle se multiplient : les arbitres peuvent être choisis en raison de leurs compétences spéciales selon le sujet du contrat; la confidentialité peut être préservée; l’arbitrage peut être utilisé pour régler des questions sur le même sujet ou des sujets semblables mais survenant dans des pays différents, ceci peut présenter l'avantage de régler en une seule fois tous les différends entre les parties, surtout en matière de commerce.
Keywords: Arbitrage; Arbitrage Conventionnel; Arbitrage Judictionnel; Arbitragem; Arbitraje; Arbitration; Commerce; Droit civil; France; Jordanie; Litiges contractuels

La médiation en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Dans une économie de plus en plus globalisée, faute d’harmonisation juridique, les parties aux litiges contractuels n’hésitent plus à consulter les forums juridiques pour identifier les pays susceptibles de leur offrir le meilleur niveau de protection. Presque tous les litiges en matière contractuels se prêtent au début des conflits à la médiation. Il arrive souvent que lors d’un litige relatif aux droits contractuels, les parties recourent à la médiation. Cependant, pour pouvoir y recourir de manière utile, il est important d’éluder certains obstacles. Un litige ayant trait à un contrat, soulève des questions complexes de faits et de droit, peut nécessiter des dépenses importantes et exiger la présence de témoins experts. Puisque l’obligation contractuelle émise sera presque toujours un enjeu, un litige ayant trait au commerce, notamment international, commande une connaissance approfondie de la législation sur les objets de transactions, ainsi qu’une expérience des tribunaux qui traitent la plupart du temps de ces questions. En pratique, l’espace de rencontre entre la médiation et les litiges contractuels est le contrat lui-même. Or, le domaine contractuel est le domaine privilégié de la médiation. En réalité, la médiation peut avoir lieu dans les relations liée aux contrats de commerce, dans lequel une dévolution des droits contractuels est prévue. Ce mode alternatif fournit un moyen pour éviter les contentieux judiciaires.
Keywords: Approche comparée; Commerce international; Droit civil; France; Jordanie; Litiges contractuels; Mediation; Médiation

La place contestée de l'arbitrage international en droit de l'investissement - El Issa, Rayyan (Université Paris-Saclay, 2023)
La place de l'arbitrage en droit de l'investissement est discutée. Les réfutations à son encontre grandissent. De nombreuses problématiques édulcorent la définition même de la notion d'investissement. Les controverses doctrinales restent toujours nombreuses et débattues à ce sujet. De même, des doctrines s'affrontent sur la question de savoir s'il faut ou non élaborer un corps de règles cohérentes pour des sentences arbitrales homogènes. L'opposition à l'arbitrage dans le droit de l'investissement se retrouve aussi dans les problématiques liées à l'exequatur des sentences arbitrales liées à l'arbitrage d'investissement dans l'Union européenne. Un manque de soutien apparent au développement de l'arbitrage dans l'Union européenne s'est installé, comme le démontre le récent traité CETA conclu entre l'Union européenne et le Canada. L'arbitrage d'investissement ferait courir le risque d'un recul de la souveraineté. En effet, du fait l'arbitrage d'investissement, les Etats seraient moins incités à légiférer sur des matières pouvant avoir un impact sur l'activité d'une entreprise étrangère, par crainte d'une procédure arbitrale. Un lien délicat apparait alors, entre souveraineté et arbitrage d'investissement. Plusieurs doctrines se sont longtemps affrontées, notamment celle élaborée par Calvo et Drago en Amérique Latine entre 1870 et 1900, proposant de réduire les droits des investisseurs étrangers, face à une doctrine opposée, celle militant pour un standard minimum international de protection des investisseurs étrangers. Or, une renaissance de ces débats apparaît aujourd'hui, avec une problématique liée à la souveraineté de plus en plus ancrée dans les débats liés à l'arbitrage d'investissement. Pourtant, l'arbitrage d'investissement doit être perçu comme une méthode permettant à des investisseurs de bénéficier d'un arbitre indépendant et permettant de « dépolitiser » les contentieux. Mais des Etats admettent de moins en moins que leurs lois établies démocratiquement pour l'intérêt général puissent être contestées par des investisseurs étrangers devant un tribunal arbitral. Des auteurs parlent de « chilling effect », par lequel des Etats n'osent plus légiférer, par crainte de contentieux ultérieurs. De plus en plus d'Etats refusent que leur droit soit remis en cause par des juges privés. Plusieurs questions se posent. Est-il toujours concevable de protéger davantage un investisseur étranger qu'un investisseur national ? Est-il légitime de privilégier des juges privés, plutôt que des juges nationaux pour trancher les litiges en matière d'investissement ? L'utilité de l'arbitrage peut être comprise, dans des pays où la justice étatique est dite « corrompue » ou « biaisée ». En pareille situation, un investisseur étranger est légitime à vouloir saisir un arbitre neutre et indépendant. Mais la légitimité d'avoir recours à l'arbitrage dans des pays développés bénéficiant d'une justice étatique indépendante pose plus de difficultés. Dès lors, faudrait-il limiter l'arbitrage d'investissement aux pays souffrant d'un déficit d'indépendance de justice étatique ? Et donc d'exclure ce mode de règlement des litiges en la matière dans l'Union européenne ? La « politisation » du débat est en pleine renaissance. L'arbitrage d'investissement est un domaine relativement jeune et il convient de se demander s'il s'agit là d'un mode de règlement des litiges adéquat et d'un mode adapté au commerce international en général ? Assistera-t-on prochainement ou assiste-t-on déjà à ce que des auteurs qualifient de « fin de cycle » ? Il s'agit de questions ancrées dans l'actualité, que ce soit en France ou ailleurs dans le monde. The place of arbitration in investment law is discussed. The rebuttals are growing. Many issues water down the very definition of the notion of investment. The doctrinal controversies are still numerous and debated on this subject. Similarly, doctrines clash on the question of whether or not it is necessary to develop a body of coherent rules for homogeneous arbitral awards. The opposition to arbitration in investment law is also found in issues related to the exequatur of arbitral awards related to investment arbitration in the European Union. An apparent lack of support for the development of arbitration in the European Union has set in, as demonstrated by the recent CETA treaty concluded between the European Union and Canada. Investment arbitration would run the risk of a decline in sovereignty. Indeed, because of investment arbitration, States would be less encouraged to legislate on matters that could have an impact on the activity of a foreign company, because of the fear of arbitration proceedings. A delicate link then appears between sovereignty and investment arbitration. Several doctrines have long clashed, in particular the one developed by Calvo and Drago in Latin America between 1870 and 1900, proposing to reduce the rights of foreign investors, in front of an opposing doctrine, that campaigning for a minimum international standard of protection for foreign investors. A revival of these debates is appearing today, with an issue linked to sovereignty increasingly rooted in the debates linked to investment arbitration. However, investment arbitration must be seen as a method allowing investors to benefit from an independent arbitrator and allowing disputes to be “depoliticised”. But states admit less and less that their laws democratically established for the general interest can be challenged by foreign investors before an arbitration tribunal. Authors talk about the “chilling effect”, by which States no longer dare to legislate, because of the fear of subsequent litigation. More and more States refuse to have their rights challenged by private judges. Several questions arise. Is it always conceivable to protect a foreign investor more than a national investor ? Is it legitimate to favor private judges, rather than national judges, to settle investment disputes ? The usefulness of arbitration can be understood in countries where state justice is said to be “corrupt” or “biased”. In such a situation, a foreign investor is legitimate in wanting to seize a neutral and independent arbitrator. But the legitimacy of having recourse to arbitration in developed countries benefiting from independent state justice arouses more difficulties. Therefore, should investment arbitration be limited to countries suffering from a lack of independence of state justice ? And therefore to exclude this method of settling disputes in this area in the European Union ? The “politicization” of the debate is in full revival. Investment arbitration is a relatively young field and it is worth asking whether it is an adequate mode of dispute resolution and a mode suitable for international trade in general ? Will we soon witness or are we already witnessing what some authors describe as the “end of the cycle” ? These are issues rooted in the news, whether in France or elsewhere in the world.
Keywords: Arbitrage; Arbitragem; Arbitration; Contentieux; Contentieux de la concurrence; Droit de l'investissement; Droit et État; Investment Law; Investments; Litigation; Souveraineté; Sovereignty

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

La Diplomatie juridique : Défense et illustration du droit français et du droit continental dans le droit global à travers les exemples de la médiation et de l'arbitrage international - Gontier, Jean-Yves (Université Paris-Saclay, 2023)
Dans la conception traditionnelle de la diplomatie, l'action extérieure des États est cantonnée aux domaines politique, économique et culturel. Le droit est plus rarement pris en compte comme outil d'influence dans l'action extérieure des États.Or, le droit joue un rôle fondamental dans la diplomatie économique. En effet, un pays qui n'est pas capable de défendre son système juridique est un pays qui économiquement est en péril, car c'est un pays qui ne peut pas s'exporter.Si la France par exemple, ou d'autres pays, se mettent à la remorque de l'Alternative Dispute Resolution jusque dans leur propre droit interne, ces pays ne pourront plus exporter leur système juridique au risque de ne plus pouvoir exporter tout court. Ils risquent alors de perdre une partie essentielle et substantielle de leur capacité de projection sur la scène internationale.De même, lorsque la francophonie économique perd du terrain, c'est tout un pan de la diplomatie économique qui perd de sa force de frappe.Avec les clauses compromissoires et clauses de médiation inspirées des modèles anglo-saxons qui se répandent dans les contrats internationaux, comment les juridictions des pays francophones qui ont été calquées sur le système judicaire français pourront-elles continuent à exister ? Les arbitres anglo-saxons finiront-ils par imposer lentement mais sûrement la Common law ? Il y a là un enjeu de diplomatie économique énorme.Nous verrons comment défendre au mieux la francophonie économique et juridique en évitant que l'Alternative Dispute Resolution ne devienne le cheval de Troie du droit anglo-saxon, avec à terme, le risque que des systèmes nationaux disparaissent.Ce sont là des questions légitimes et très graves, et l'on peut comprendre qu'elles soient posées avec une certaine persistance.Avec l'élargissement continu du champ des relations internationales, le droit doit devenir l'objet d'une politique extérieure stratégique à part entière. C'est pourquoi nous plaidons pour la mise en place d'une diplomatie juridique française et formulons des recommandations ainsi qu'une stratégie d'influence juridique extérieure.En prenant la défense et en illustrant le droit continental et le droit français dans le droit global à travers les exemples de la médiation et de l'arbitrage international, nous espérons contribuer à l'ébauche d'une théorie de la diplomatie juridique et à ouvrir des pistes nouvelles de réflexion en matière d'influence internationale, en particulier d'influence juridique internationale.Nous espérons contribuer ainsi modestement mais utilement à la défense du droit français et du droit continental pour que la confrontation et la compétition des système juridiques n'aboutissent pas à la domination d'un système juridique sur un autre mais que cette compétition aille au contraire dans le sens d'un meilleur équilibre entre les systèmes juridiques, dans le sens du progrès et de l'amélioration du droit français et du droit continental, mais aussi - s'il se peut -dans le sens des progrès dans la défense des causes et des valeurs universelles. In the traditional conception of diplomacy, the external action of States is confined to the political, economic and cultural domains. Law is more rarely taken into account as a tool of influence in the external action of States.However, Law plays a fundamental role in economic diplomacy. Indeed, a country that is not able to defend its legal system is a country that is economically in danger, because it is a country that cannot be exported. If France, for example, or other countries, follow the Alternative Dispute Resolution right up to their own domestic law, these countries will no longer be able to export their legal system at the risk of no longer being able to export at all. They then risk losing an essential and substantial part of their ability to project themselves on the international scene.Similarly, when the economic Francophonie loses ground, a whole section of economic diplomacy loses its strike force.With arbitration clauses and mediation clauses inspired by Anglo-Saxon models that are spreading in international contracts, how will the courts of French-speaking countries that have been modeled on the French judicial system be able to continue to exist? Will Anglo-Saxon arbitrators end up slowly but surely imposing the Common law? There is a huge stake in economic diplomacy here.We will see how best to defend the economic and legal Francophonie by preventing the Alternative Dispute Resolution from becoming the Trojan horse of Anglo-Saxon law, with the eventual risk that national systems will disappear.These are legitimate and very serious questions, and one can understand that they are asked with a certain persistence.With the continuous widening of the field of international relations, Law must become the object of a strategic foreign policy. This is why we plead for the establishment of a French legal diplomacy and formulate recommendations as well as a strategy of external legal influence.By defending and illustrating continental law and French law in global law through the examples of mediation and international arbitration, we hope to contribute to the sketch of a theory of legal diplomacy and to open new paths of reflection in terms of international influence, in particular international legal influence.We hope in this way to contribute modestly but usefully to the defense of French law and continental law so that the confrontation and competition of legal systems does not lead to the domination of one legal system over another but that this competition goes on the contrary in the sense of a better balance between legal systems, in the direction of progress and improvement of French law and continental law, but also - if possible - in the direction of progress in the defense of universal causes and values.
Keywords: Arbitrage; Arbitragem; Arbitration; Diplomatie; Diplomatie juridique; Diplomatie économique; Droit global; Economic Diplomacy; Global Law; Influence; Influence juridique internationale; International Legal Influence; Legal Diplomacy; MARD; Mediación; Mediation; Mediação; Médiation; Relations extérieures; Relations économiques internationales

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

L'arbitrage à l'épreuve des procédures belges d'insolvabilité d'entreprises - Dantinne, Rouslan (Université de Liège, 2023)
Alors que deux entreprises sont liées par une convention d’arbitrage, une procédure d’insolvabilité est ouverte en Belgique à l’égard de l’une d’elles. De nombreuses questions émergent : L’instance arbitrale en cours doit-elle être suspendue ? Dans la positive, pourra-t-elle reprendre ? Les pouvoirs de l’arbitre sont-ils impactés ? L’instance n’a pas débuté, la validité de la convention d’arbitrage est-elle compromise ? La convention n’existe pas, les parties peuvent-elles la conclure ? L’entreprise en difficulté perd-elle sa capacité compromissoire ? Cette capacité est-elle transférée au praticien de l’insolvabilité ? La sentence a été rendue, peut-elle être exécutée ? Dans le présent exposé, nous mettons l’arbitrage à l’épreuve des procédures belges d’insolvabilité d’entreprises.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Faillite; Insolvabilité; Insolvency; Procédures d'insolvabilité; Réorganisation judiciaire

L'unanimité de l'accord de conciliation en droit OHADA : une logique juridique irréaliste ? - Kourouma, Moussa Fanta (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2023)

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Les garanties du procès équitable à l’épreuve des modes alternatifs de règlement de conflits - Guedegbe, Igor Samson Bidossessi (Revue Béninoise des Sciences Juridiques et Administratives, 2023)

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

Effective Conflict Management - International Chamber of Commerce (ICC Publication DRS, 2023)

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

Regards sur l’intervention du juge étatique dans la constitution du Tribunal Arbitral dans l’espace OHADA - Mainibe Tchiombe, Calice Cléopâtre (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Qu’il soit institutionnel ou adhoc, L’arbitrage est vu comme un mode de règlement des litiges qui a vocation à se dérouler, de la requête initiale à la sentence finale, sans l’intervention du juge étatique. Il arrive, cependant que, ce juge soit amené à intervenir dans le processus arbitral, pour une raison ou pour une autre. On a pu ainsi dire qu’il n’y a pas de bon arbitrage sans un bon juge. Bien que l’intervention du juge étatique doivent rester exceptionnelle en matière d’arbitrage, il importe que ledit juge soit identifié, d’autant qu’il n’est pas le mena selon la phase à laquelle il intervient et peut varier d’une organisation judiciaire à une autre.
Keywords: Juge étatique; Organisation judiciaire

L’encadrement juridique de la médiation dans l’espace OHADA : analyse critique de l’acte uniforme relatif à la médiation - Mukuamu, Prince (Université de Sherbrooke, 2023)
Aujourd'hui plus qu'hier, la médiation suscite l’intérêt tant des chercheurs, des praticiens, que des politiques. Cet intérêt se matérialise notamment par les différents cadres juridiques dont elle bénéficie dans plusieurs législations. Afin de promouvoir la médiation au sein de ses États membres, L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a adopté le 23 novembre 2017 un Acte Uniforme relatif à la Médiation (AUM). Après avoir adopté depuis plus de deux décennies un Acte uniforme sur l’arbitrage, l’organisation régionale confirme sa volonté de promouvoir les modes alternatifs de règlement de conflits dans le domaine du droit des affaires. Cependant, l’AUM est un instrument juridique particulier attendu qu'il est le premier de son genre à s’appliquer également aux domaines non encore régis par le droit OHADA. Toutefois, si la médiation tend à se développer de plus en plus, il convient de prendre garde à ce que cette évolution, notamment en ce qui concerne son encadrement légal, ne conduise pas à sa dénaturation. Voilà l’un des défis auquel est également soumis le législateur OHADA.
Keywords: AUM; Acte uniforme; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; OHADA

Les principes directeurs du procès équitable en médiation OHADA - Ngono Yakam, Marie Joseph (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
L'image de l’alternative et de la souplesse de la médiation semble aux premiers abords exclure les principes directeurs du procès équitable de ce mode de règlement des conflits. Mais la réalité en est tout autre. Entant qu'instrument de justice, la médiation ne saurait s’affranchir des garanties d’ordre procédurales. Cette survivance va donc de soi puisque tout comme le procès, la médiation fait intervenir un tiers. La présente étude consiste donc à examiner la question des principes du procès équitable appliqués à la médiation OHADA.
Keywords: Fair trial; Guiding principle; MARD; Mediación; Mediation; Mediação; Médiation; OHADA; Principe directeur; Procès équitable

L'arbitrage international dans les contrats publics en droits marocain et français - Raissi, Imane (Revue du Droit Marocain, 2023)
Le recours à l’arbitrage, comme mode de règlement des différends commerciaux internationaux qui s’applique aux contrats publics reliant les Etats et leurs démembrements et avec des investisseurs privés, s’est étendu au fur et à mesure de l’interventionnisme croissant de l’Etat dans l’économie et de la multiplication des leviers juridiques qui lui sont dédiés (marchés publics, gestion déléguée, partenariat public-privé, etc.). Or, ces contrats ainsi soumis à l’hypothèse de l’égalité des parties posent la problématique de l’équilibre entre la portée de la clause compromissoire et la souveraineté des Etats en matière du régime juridique et de la compétence juridictionnelle. Dans une approche comparée entre les Droits marocain et français, cet article analyse les effets du recours à l’arbitrage international sur les règles applicables aux contrats publics à l’origine du différend, notamment, au niveau de la clause attributive de compétence, la compétence juridictionnelle et l’exequatur des sentences arbitrales.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Commande publique; Contrat public; Droit comparé; France; Maroc; Morocco

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

La jurisprudence arbitrale : composante principale du droit international des investissements - Uranga, Paul (Les Cahiers de droit, 2023)
Le droit international des investissements résulte principalement d’une multitude de traités d’investissement, souvent bilatéraux, parfois régionaux et très rarement multilatéraux. Ce régime éclaté, ayant l’arbitrage comme moyen principal de règlement des différends entre investisseurs et État, ne favorise pas, en théorie, l’émergence d’une jurisprudence réellement cohérente et pertinente. Toutefois, la pratique arbitrale florissante en matière d’investissement s’est révélée constituer une véritable jurisprudence à l’importance non négligeable. Bien que le précédent n’ait pas de valeur juridique obligatoire, force est de constater sa valeur persuasive et la systématicité de son usage. Une telle utilisation des précédents arbitraux a pu permettre le développement d’une compréhension commune des normes des traités d’investissement et favoriser ainsi indirectement le développement conventionnel de ce droit. La jurisprudence arbitrale innerve de ce fait tous les pans du droit international des investissements, du discours des arbitres à l’évolution même des normes applicables. C’est en cela que la jurisprudence arbitrale peut s’entendre comme la composante principale du droit international des investissements.

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on.  There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk

L'opposabilité aux tiers de la convention d'arbitrage - Mhaoun, Jalal (Université de Bordeaux, 2022)
Il existe en droit commun et en droit de l’arbitrage deux mécanismes similaires ayant un objectif commun : rendre l’acte juridique apte à faire sentir ses effets à l’égard des tiers. Il s’agit, pour le droit commun, du principe de l’opposabilité et, pour le droit de l’arbitrage, de la règle de l’attraction des tiers à la procédure arbitrale. Ces deux techniques, qui procèdent de la même manière et partagent presque les mêmes conditions de mise en œuvre, ont en revanche une qualification distincte. En droit commun, l’opposabilité est connue pour être un principe à part entière dont la fonction principale, la fonction de sanction, est relativement offensive, puisqu’elle oblige les tiers, sujets auxquels l’opposabilité est habituellement attachée, au devoir général de respect, à l’obligation de ne pas nier l’existence des engagements d’autrui et de ne pas y porter atteinte au risque de subir les conséquences de leur immixtion. Le principe de l’opposabilité a également une fonction probatoire qui permet aux tiers d’opposer aux parties, ou aux autres tiers, l’existence d’un contrat pour apporter la preuve d’un fait. Alors qu’en droit de l’arbitrage, la règle de l’attraction permet une extension des effets de la convention d’arbitrage à l’égard des tiers qui se trouvent impliqués positivement ou négativement, directement ou indirectement à la négociation, la formation, l’exécution ou l’anéantissement du contrat dans lequel est insérée la clause d’arbitrage.Puisque les deux techniques partagent le même procédé et agissent sur les mêmes personnes, la présente thèse a pour but d’étudier la réception du principe d’opposabilité en droit de l’arbitrage. Cette réception passe par une intégration et un attachement de la règle de l’attraction au principe de l’opposabilité comme fonction nouvelle. L'objectif principal est donc de répondre à une question précise : comment faire en sorte que le principe de l'opposabilité soit accepté et transposé en matière arbitrale pour ainsi voir à l’œuvre toutes ses fonctions, y compris celle qu’il vient d’intégrer, sans que le système juridique ne subisse de profonds bouleversements.Notre analyse de la réception se déroule en deux étapes. Après avoir rappelé et établi le cadre théorique du principe de l'opposabilité, dans lequel avons-nous examiné les différentes conceptions, justifications et sujets de l’opposabilité ; cadre qui nous a offert une image plus claire et réaliste des applications de l'opposabilité en droit commun et nous a permis de voir si ces applications et fonctions étaient en mesure de justifier la règle de l'attraction. Nous avons donc conclu que l’opposabilité est parfaitement recevable en droit de l’arbitrage à condition d’y intégrer ladite règle de l’attraction comme fonction nouvelle. Convaincus de sa réception en droit de l'arbitrage, nous avons, ensuite, soumis la nouvelle fonction d’attraction à un ultime test, celui de l’efficacité. L’examen de l’efficacité aura permis de recenser les limites de la règle de l’attraction dont nous avons proposé un certain nombre de solutions de renouvellement, et ce, dans le but de mieux intégrer la fonction et pour que celle-ci puisse avoir un impact systématisé sur le droit de l’arbitrage.
Keywords: Arbitrage; Arbitrage multipartite; Arbitragem; Arbitraje; Arbitration; Convention d'arbitrage; Extension; Opposability; Opposabilité; Règle de l'attraction; Third parties; Tiers; Tiers (droit); Transmission

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

L’arbitrage des marchés publics - Sinclair, Kongni Ngoula (International Multilingual Journal of Science and Technology, 2022)
Les contrats administratifs, plus précisément les marchés publics, sont moyens par lesquels l’Etat assure sa mission d’intérêt général. Ainsi, il peut arriver que pendant la phase de passation ou d’exécution d’un contrat de marché public, que l’une des parties ne puisse pas accomplir les formalités, d’où la naissance d’un litige. De ce fait, pour résoudre ce litige, les parties peuvent décider d’un règlement à l’amiable du différend. L’arbitrage étant le mode par excellence de règlement à l’amiable des litiges, il est donc opportun en partant de ces spécificités, de mettre en œuvre la procédure d’arbitralité des marchés public et l’issue positive de cette procédure qu’est la sentence arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CEMAC; Commande publique; Contrats administratifs; GICAM; Marchés publics; Organes communautaires; Procédure arbitrale; Sentence arbitrale

La convention d’arbitrage : étude comparée de droit franco-marocain - Ajouby, Samia (Université Paris 2, 2022)
Terre attractive pour les investisseurs étrangers, le Maroc voit son économie muter au gré de l'implantation d'entreprises. Face à cette situation, l'adaptation du droit est essentielle. Il s'agit effectivement d'un instrument fondamental pouvant être mis à la disposition des entreprises pour leur offrir un cadre légal rassurant quant à la prospérité de leurs intérêts. Or la justice étatique inspire traditionnellement la crainte du fait de sa lourdeur administrative et de son incapacité à assurer des garanties procédurales suffisantes Pour résorber cela, le législateur marocain a tendu à développer les modes alternatifs de règlement des conflits, tel que l'arbitrage. C'est dans ce contexte que la loi intitulée "arbitrage et médiation conventionnelle" a été ratifiée, le 6 décembre 2007. Elle s'inspire du droit français pour modifier les articles 306 à 327 du Code de procédure civile marocain. Ce cadre procédural vise à insuffler une vigueur nouvelle aux modes alternatifs de règlement des conflits. Néanmoins, la souplesse du régime a pour corollaire des pathologies qui peuvent affecter les conventions d'arbitrage. La rédaction des clauses approximatives, et la formation insuffisante de certains arbitres se traduisent par des conventions d'arbitrage bancales, sources de nouveaux problèmes là où elles devraient faciliter la résolution des litiges. Dans ces conditions, une nouvelle réforme a donné naissance à un Code de l’arbitrage, ratifié le 24 mai 2022. Il s’agira d’étudier l’évolution de la législation marocaine de l’arbitrage, dans une dimension comparatiste avec le droit français, et à la lumière d’une recherche constante de l’efficacité de la convention d’arbitrage. [Abstract] The arbitration agreement : a comparative study of French and Moroccan law : Morocco is an attractive country for foreign investors, and its economy is changing as companies are setting up. Faced with this situation, the adaptation of the law is essential. Indeed, it is a fundamental instrument that can be made available to companies to offer them a reassuring legal framework for the prosperity of their interests. However, the state justice system traditionally inspires distrust because of its administrative cumbersomeness and its inability to ensure sufficient procedural guarantees. In order to solve this, the Moroccan legislator has tended to develop alternative methods of dispute resolution, such as arbitration. It is in this context that the law entitled "arbitration and conventional mediation" was ratified on December 6, 2007. It is inspired by French law to modify articles 306 to 327 of the Moroccan Code of Civil Procedure. This procedural framework aims at breathing new life into alternative dispute resolution. Nevertheless, the flexibility of the regime has as a corollary pathologies that can affect arbitration agreements. The drafting of unprofessional clauses and the inadequate training of arbitrators result in flawed arbitration agreements, which are a source of problems where they should facilitate the resolution of disputes. In these conditions, a new reform has led to an Arbitration Code, ratified on May 24, 2022. The aim is to study the evolution of Moroccan arbitration legislation, in a comparative dimension with French law, and in the light of a constant search for the efficiency of the arbitration agreement.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Comparative law; Contentieux international; Contract law; Contrats; Convention d'arbitrage; Conventions d'arbitrage international - Maroc; Dispute resolution; Droit comparé; Droit des contrats; Droit international; Efficacité; Efficiency; France; International law; International litigation; Maroc; Modes alternatifs; Procedure; Procédure; Règlement de conflits; Résolution des litiges

The Unilateral Arbitration Clause between Permissibility and Nullity - Mahmoud Jaradat, Nashat; JassimSarhan, Ghassan (Information Sciences Letters, 2022)
Researching the judicial applications of Arab countries to one of the issues that have occupied legal thoughts in the Western world for decades and still in one form or another, the so-called Unilateral Arbitration Clauses, we did not find a discussion of the applicability of this clause within the laws. Even though this condition takes a reasonable space of the legal arguments as previously mentioned, it has even become widely used in contracts, such as tenancy, contracting, and financial investments. The study showed that the above-mentioned clause has recently increased its use in financing contracts, especially with the increasing globalization of banking services and bank transfers. Although banks usually prefer to resort to traditional litigation, lack of similarity in the legal rules and judicial applications related to banking transactions and their difference from one country to another was a reason for the banks preference of resorting to arbitration. There is no examination of the legitimacy of an unequal or optional arbitration clause in Bahrain. Also, the Bahraini and Egyptian courts, to the best of our knowledge, did not decide whether it should be considered null or valid. The same case is applied to the French courts which have no cases that examined this type of clauses except for a case in 2006 and the other is a judgment close to the same issue on October 7, 2015, from the French Court of Cassation. The English and American courts were different; they examined this clause and had several judicial implementations due to the fact that most of the arbitration terms are either related to multinational companies operating within the framework of the Wall Street Stock Exchange in New York or those that stipulate the enforcement of British and Wales law on the provisions of the contract . However, many Arab countries, in general, as well as Bahrain and some Gulf countries, in particular, are seeking in their economic model to attract foreign investments and capital, especially those related to financial and banking industries, to diversify sources of income. The decision of investing or not investing the capital in a country is made by the judicial authority in terms of independence as well as the judicial application of legal texts as these factors are directly reflected in the desire to invest and show the possibility of protecting investors.

Settlement of Disputes Arising from Documentary Credit Under National and International Regulations - Nour, Hoda Magdy (UAEU Law Journal, 2022)
The need Settlement of disputes arising from bank credit between national and international rules, protecting the interests of the bank and ensuring its financial rights before the debtor. As the Bank faces different technical and legal difficulties, as well as the multiplicity of legal adaptation, we deal with the rules governing banking accreditation from the point of pleadings law, and the methods of amicable settlement of these disputes and following, and compulsory execution. International efforts are taking the lead in establishing the technical regulation of bank accreditation and setting rules "DOCDEX" in 1997, and the 2015 amendments, which still need more as they do not provide a legal way to implement them. It is necessary to find out legal regulation at the domestic and international levels, which calls for the legislator to intervene to organize its rules and procedures. We have sought in this study to weave the legal entity to seize bank credit within the legally acceptable limits based on a system of seizure of the debtor with third parties against the background of the legal system of documentary credit and the relationships arising from it, and its financial and economic effects that go beyond the parties to the beneficiaries of companies, bodies, and economic institutions, As the matter still requires the existence of special legislation regulating the seizure of bank credit, to ensure the effectiveness of the guarantees surrounding the appropriations by the national legislator and at the international level. This would expand the insurance of bank credit so that the creditors recover their full right directly or by seizing the value of the credit, which calls for organizing this seizure with rules that consider the privacy of this seizure and its rules and are consistent with the required speed in such transactions in a way that protects the creditor from abuse, in a manner that ensures the observance of confidentiality, due process, and the spirit of banking work, anticipate the possible future that will witness the decline of documentary credit and replace it with electronic transactions, the establishment of specialized banking courts that save time and effort.

Business Dispute Settlement Through Mediation in State Courts and Arbitration Institutions - Yuspin, Wardah; Aziz, Abdul (International Journal of Social Science Research and Review, 2022)
In social life, there are often differences in perceptions between humans, causing problems or disputes, whether minor or serious. Likewise in the relationship of economic activities or more commonly known as business relations. Not infrequently humans experience a clash and differences of opinion that lead to disputes. Various problems will always arise in business as long as humans run their business solely for profit, so there are often differences of opinion because the parties will not be harmed which will eventually lead to disputes. In the end, dispute resolution, especially business disputes, is often resolved through a trial in court through a lawsuit by one of the parties who feel aggrieved. However, what was expected from the settlement turned out to be unsatisfactory for the parties because the settlement through litigation sometimes took a long time to obtain legal certainty so that it actually harmed business people because of the loss of time, energy and materials. As an alternative to resolving business disputes, business actors have a tendency to avoid disputes in court and choose to use mediation or through arbitration institutions. This study will briefly describe the comparison of business dispute resolution through court mediation with settlement through arbitration institutions. The research was conducted through descriptive empirical legal research.
Keywords: Arbitration; Business; Dispute

Processo arbitral: a estabilização da demanda - Leão, Fernanda de Gouvêa (Universidade de São Paulo, 2022)
Esta tese trata da estabilização da demanda no processo arbitral. Ao se falar da estabilização da demanda no processo arbitral, são muito comuns as afirmações de que, no processo arbitral, o tratamento é diferente, pois é mais flexível. Também, comumente se afirma que a estabilização da demanda na arbitragem se daria no momento de assinatura do termo de arbitragem. No entanto, entende-se que o tema não foi analisado de forma aprofundada, e, inclusive, com base nas pesquisas realizadas, poucas foram as obras nacionais que trataram especificamente da estabilização da demanda arbitral. Diante disso, este trabalho buscará analisar como se dá a estabilização da demanda no processo arbitral e as hipóteses de modificação da demanda no decorrer do processo. Para tanto, inicialmente serão apresentadas considerações iniciais, necessárias ao desenvolvimento do trabalho, como a natureza jurídica da arbitragem e sua inclusão na teoria geral do processo. Após, analisa-se o processo arbitral, a formação da demanda na arbitragem e como se dá a definição das regras a serem observadas no processo arbitral, e como são definidos os poderes jurisdicionais dos árbitros. Ainda, ao se falar de estabilização da demanda, necessariamente deve ser estudado o conteúdo da demanda arbitral e sua individualização, ou seja, o que constitui o objeto litigioso do processo arbitral. Em seguida, será feita a investigação de quais são os elementos da demanda arbitral, as teorias que tratam de cada um deles e qual deve ser seu conteúdo mínimo. Ultrapassada essa investigação e fixados os conceitos necessários ao desenvolvimento do tema, serão analisadas as linhas gerais da estabilização da demanda, sua natureza jurídica e os fundamentos que embasam não só a regra da estabilização da demanda, mas também sua mitigação, do que decorre da análise dos sistemas rígidos e flexíveis. Definidos os conceitos gerais acerca da estabilização da demanda arbitral, analisaremos como outros ordenamentos tratam da questão, bem como as disposições no processo estatal brasileiro, para que se possa compreender o que o sistema processual entende como estabilização da demanda e as hipóteses de mitigação. Em seguida, trataremos do momento de estabilização da demanda arbitral, possibilidade de modificação dos elementos da demanda e consequências da violação da regra da estabilização da demanda. Por fim, todo estudo teórico deve mostrar seu viés prático, de modo que as análises que foram feitas possam ser aplicadas pelas partes e pelo árbitro. Por essa razão, o último capítulo é dedicado às recomendações sobre o tratamento da estabilização da demanda na arbitragem. This thesis addresses the stabilization of demand in the arbitral procedure. When discussing the demand stabilization in the arbitration procedure, it is widely asserted that in the arbitration proceeding the treatment is different since it is more flexible. Furthermore, it is commonly stated that the stabilization of demand in arbitration would occur when the terms of reference are signed. Nevertheless, it is understood that the issue has not been analyzed comprehensively and, based on the research conducted, few Brazilian studies have specifically addressed the stabilization of the arbitral demand. Thus, this study will analyze how the stabilization of the demand occurs in the arbitration procedure and the hypotheses of modification of the claim in the course of the procedure. For this purpose, the necessary initial considerations for the development of the study will be presented, such as the legal nature of arbitration and its inclusion in the general theory of procedure. After that, we will analyze the arbitration process, the formation of the demand in arbitration, and how the rules to be observed in the arbitration process are defined, as well as the jurisdictional powers of the arbitrators. Afterward, we will then proceed to the analysis of the arbitration process, the constitution of the demand in arbitration, and how the rules to be observed in the arbitration procedure are defined, as well as how the jurisdictional powers of the arbitrators are defined. Moreover, when discussing the stabilization of the demand, one must necessarily study the content of the arbitration claim and its individualization, i.e., what constitutes the litigious object of the arbitration procedure. Following that, an investigation of the elements of the arbitration claim, the theories that deal with each of them, and what the minimum content should be, will be carried out. Once this investigation has been concluded and the concepts necessary for the development of this thesis have been established, the general lines of the stabilization of demand will be analyzed, as well as its legal nature and grounds that support, not only the rule of stabilization of demand, but also its mitigation, which follows from the analysis of rigid and flexible systems. Once the general concepts concerning the stabilization of arbitral demand are defined, we will analyze how other legal systems address the issue, as well as the provisions in the Brazilian state process, so that we can comprehend what the procedural system understands as stabilization of demand and the hypotheses of mitigation. Next, we will address the moment of stabilization of the arbitral demand, the possibility of modifying the elements of the claim and the consequences of the violation of the rule of stabilization of demand. Finally, every theoretical study must reveal its practical side, so that the analyses that have been made can be applied by the parties and the arbitrator. For this reason, the last chapter is devoted to recommendations on the treatment of demand stabilization in arbitration.
Keywords: Alemanha; Arbitrage; Arbitragem; Arbitration; Arbitration procedure; Brasil; Direito Comparado; Direito Processual Civil; Espanha; Estados Unidos; Juízo arbitral; Litígio; Modification of the elements of the demand; Portugal; Procedimento especial; Stabilization of the demand

Desconsideração da personalidade jurídica na arbitragem - Ferraz, Renato de Toledo Piza (Universidade de São Paulo, 2022)
A presente tese se ocupa de analisar a possibilidade de vinculação de não signatário da convenção de arbitragem ao processo de jurisdição privada via desconsideração da personalidade jurídica no âmbito de arbitragens domésticas. Para tanto, no Capítulo 1, examinam-se premissas teóricas ligadas ao processo de aquisição da personalidade jurídica; de como ele opera limitando a responsabilidade dos integrantes do ente personalizado; e do embate entre autonomia da atividade societária e abuso de direito do qual pode resultar a desconsideração da personalidade jurídica. A teoria desconstitutiva é verificada desde sua criação até os dias atuais, enfatizando-se seu modo de funcionamento à luz dos pressupostos que autorizam sua incidência e os efeitos que se seguem desse reconhecimento segundo a concepção clássica da técnica desconstitutiva. No Capítulo 2, aborda-se o papel da autonomia da vontade para a teoria geral dos contratos e para a arbitragem, apontando-se o alcance e a classificação desta última para, a seguir, adentrar no tema da verificação do consentimento para arbitrar conflitos. Nesse contexto, são analisadas diversas teorias que fundamentam a participação de parte não signatária em arbitragens para se chegar à formulação daquilo que se denominou de consentimento suficiente para arbitrar conflitos. Ao ensejo do estudo das diversas teorias que embasam a extensão da cláusula compromissória, procura-se assinalar distinções, mas também semelhanças, que tornem viável apropriar seus argumentos, quando for o caso, para a específica hipótese de vinculação de terceiro via desconsideração da personalidade jurídica. No Capítulo 3, o epicentro da tese, são investigados os fundamentos que, segundo se defende, autorizam a hipótese. Para tanto, são levados em consideração implicações próprias da natureza jurídica da arbitragem e da regra do kompetenz-kompetenz; a equiparação entre árbitros e juízes togados no exercício de suas funções; o valor da efetividade para a jurisdição arbitral, com foco na análise econômica do direito e no impacto para os custos transacionais da arbitragem ao se rechaçar a hipótese defendida; a boa-fé objetiva como meio apto a identificar o consentimento suficiente; e, finalmente, uma análise individual de alguns trabalhos doutrinários que defendem a hipótese contrária, expondo criticamente seus motivos. Como resultado dos pontos abordados, procura-se responder se a análise da pretensão desconstitutiva por árbitros choca-se com o sistema por alargar os limites da convenção, seja em razão da matéria, seja em virtude dos sujeitos contratantes do pacto arbitral. A conclusão a que se chega é no sentido de que a conjugação desses fatores possibilita a vinculação de parte não signatária ao processo arbitral em razão da utilização abusiva da personalidade jurídica, sendo essa a solução mais consentânea com os propósitos da técnica desconstitutiva estampada no art. 50 do CC e conforme o que dispõe o sistema arbitral. This thesis is dedicated to analyzing the possibility of binding a non-signatory of the arbitration agreement to the private jurisdiction process via disregard doctrine in domestic arbitrations. To this end, Chapter 1 analyzes the theoretical premises linked to the process of acquisition of legal entity, the way it operates in limiting the liability of the members of the personalized entity, and the conflict between the autonomy of the companys activity and abuse of rights, which may result in the disregard of legal entity. The disregard doctrine is verified from its conception to the present days, emphasizing the way it works according to the requirements that allows its incidence and the effects from its recognition according to the classic doctrine of the corporate veil. Chapter 2 deals with the role of autonomy of the will in the general theory of contracts and arbitration, pointing out the reach and classification of the arbitration to then go into the theme of the verification of consent to arbitrate conflicts. In this context, the various theories that support the participation of a non-signatory party in arbitration proceedings are analyzed to formulate what is called "sufficient consent" to arbitrate disputes. In the course of analyzing the various theories on which the extension of the arbitration clause is based, an effort is made to point out distinctions as well as similarities that could make feasible to adopt their arguments, where appropriate, for the specific hypothesis of binding a third party through vail of legal entity. In Chapter 3, the epicenter of the thesis, the grounds by which, according to what has been defended, the arguments that authorizes the hypothesis are examined. To this end, the implications of the legal nature of arbitration are taken into consideration; the rule of kompetenz-kompetenz; the equivalence between arbitrators and judges in the exercise of their functions; the value of effectiveness for the arbitral jurisdiction, focused on the Economic Analysis of Law and the impact on the transactional costs of arbitration when the defended hypothesis is rejected; objective good faith as liable ground for identifying sufficient consent; and finally, individual analysis of some doctrinal works defending the contrary hypothesis, critically exposing their motives. As a result of all the points analyzed, an attempt is made to answer whether the analysis of the unconstitutional claim by arbitrators clashes with the system by extending the limits of the arbitration convention, whether due to the subject matter or to the contracting parties of the arbitration agreement. The conclusion is that the combination of these factors allows the binding of the non-signatory party to the arbitration process due to the abusive use of the legal entity, being this the most consistent solution with the purposes of the unconstitutional technique stamped in article 50 of Brazilian Civil Code and according to what the arbitration system disposes of.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Arbitration Law; Arbitration clause; Binding of non-signatories; Civil procedural law; Cláusula compromissória arbitral; Convenção de arbitragem; Direito arbitral; Direito processual civil; Limites subjetivos; Personalidade jurídica; Subjective limits; Vail of legal entity; Vinculação de não signatários

El principio de voluntariedad y la tenencia en mediación - Sarmiento, Mónica Piedra; Pazmiño, Esteban Polo (Polo del Conocimiento, 2022)
En los últimos tiempos la mediación se ha visto involucrada en varios conflictos y sucesos de la realidad actual, pues este procedimiento, como el resto de métodos alternativos de solución de conflictos siempre ha estado presente, sólo se tiene que acudir a los autores clásicos y observar que se hacía referencia a ellos. Sin embargo, la mediación ha tomado fuerza a través de su verdadero desarrollo hacia una cultura de paz. El principio de voluntariedad es una característica esencial en los medios alternativos a la solución de conflictos, en el que, las partes resuelven sus controversias en materia transigible, asistidos por un tercero neutral llamado Mediador/a, el mismo que, guía, y conduce a las partes a resolver de manera eficaz, eficiente, rápida, y legal los conflictos. Si bien es cierto, dentro de este procedimiento se presentan muchos problemas al momento de resolver esta situación, y se ha encontrado en el mismo con personas, situaciones, posiciones, intereses y necesidades diferentes, así también se evidencian sentimientos, que al momento de llegar a un acuerdo de tenencia, lo único que se prioriza es todo lo mencionado anteriormente, pero no de manera consciente y responsable el bienestar de los menores, y ante este escenario, las partes deciden, y como es lógico el tercero neutral (mediador) debe respetar esa voluntad. Para esta investigación se ha utilizado una metodología histórica - lógica, así como inductiva - deductiva y dogmática jurídica, con un tipo de investigación cuantitativo, y un nivel de investigación descriptivo, lo que permite detallar y caracterizar el fenómeno en estudio.
Keywords: Conciliación; Conciliation; Mediación; Mediation; Médiation; Relación padre – hijo.; Tenencia

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

L'efficacité des mesures provisoires et conservatoires dans l'arbitrage interne : étude du droit français et du droit koweïtien - Alenezi, Ali (Université Jean Moulin Lyon 3, 2022)
En droits français et koweïtien, il existe une juridiction de référé quelque soit la matière. Cette juridiction a le pouvoir de prendre des mesures provisoires et/ou conservatoires pour régler momentanément une situation urgente ou pour sauvegarder provisoirement et rapidement un droit dans l’attente qu’un jugement au fond soit rendu. Toutefois, en matière arbitrale, le juge étatique n’est pas le seul compétent pour pouvoir prendre lesdites mesures. En effet, l’arbitre désigné dans la convention d’arbitrage dispose également de cette prérogative. À ce titre, les juges étatiques ou arbitraux français et koweitiens, bénéficient de points forts mais également de faiblesses lorsqu’ils rendent ces mesures. D’une part, les juges des référés français et koweïtiens disposent de toutes les prérogatives permettant de rendre leurs décisions provisoires d’une manière efficace et rapide. Toutefois, la lourdeur des règles procédurales applicables devant les juridictions de référé peut s’avérer dissuasif. Elles peuvent ainsi préférer se tourner vers l’arbitre puisque les règles de procédure propre à l’arbitrage sont souvent perçues comme étant modernes, simples et rapides. Toutefois, les arbitres de ces deux États ne disposent pas de l’impérium, qui garante garantissant l’efficacité et l’effectivité de leurs mesures. À ce titre, la substance de cette thèse résidera dans la comparaison entre le juge des référés et les arbitres français et koweitiens concernant l’efficacité et la célérité de leurs mesures provisoires et/ou conservatoires. La présente thèse s’attachera à démontrer, au travers de cette comparaison, que l’arbitrage est préférable au traitement du litige malgré l’absence de certaines prérogatives importantes qui aident les arbitres pour rendre leurs mesures provisoires et/ou conservatoires rapides et efficaces. In French and Kuwaiti national courts, the power of urgency exists regardless of the nature of the courts, civil or commercial. The power of urgency entitles to grant all provisional and precautional orders to address an emergency situation or to preserve the right of the parties without prejudice to the origin of the substantive right. However, in the case of an existence of an arbitration agreement, the judge does not have the right to grant these orders solely. In fact, the arbitrator appointed in the arbitration agreement also has the right to this privilege. In this regard, every French and Kuwaiti judge whether an arbitrator or a national judge has points of strength and weakness when granting these orders. On one hand, the French and Kuwaiti national judge has all the privileges that entitle them to grant provisional and precautional orders effectively and quickly. However, the nature of the procedures used to grant these orders can sometimes be stressful and exhausting to the parties involved in a way that affects the speed and effectiveness of these orders. On the other hand, the procedures followed before the arbitrators are easy, fast, and effective, but the arbitrators do not have the power to redress to ensure the execution of these orders, which affects the administration of justice. Therefore, the essence of this study lies in the comparison between the national judge and the arbitrator, French and Kuwaiti, in terms of the effectiveness and the speed of granting provisional and precautional orders. This study shows that arbitration is always preferred by disputants to obtain provisional and precautional orders more quickly and effectively than national courts.
Keywords: Arbitrage; Arbitral proceedings; Arbitration; Arbitrator; Arbitrator privileges; Arbitre; Astreintes; Célérité et efficacité des mesures provisoires et/ou conservatoires; Droits français et koweïtien; Imperium; Judicial expedited proceedings; Juge des référés; Mesures provisoires et/ou conservatoires; Pouvoir coercitif; Pouvoirs de l'arbitre; Pouvoirs du juge des référés; Référé arbitral et judiciaire; The French and Kuwaiti Laws; The power of redress; The provisional and precautional orders; The speed and effectiveness of provisional and precautional orders; Threatening fines; Urgent judge

La mise en question de l’arbitrage d’investissement et la réforme du règlement des différends entre investisseurs et États - Sucharitkul, Vanina (Université Paris 2, 2022)
Au cours des dernières décennies, le régime de règlement des différends entre investisseurs et États (« RDIE »), par le biais de l’arbitrage ad hoc, a été l’objet d’un examen approfondi et de critiques croissantes. Au fur et à mesure que les États défendeurs de diverses régions ont perdu des affaires d’arbitrage d’investissement, ils ont été comme désenchantés par ce type de mécanisme de résolution des litiges, dans ce qui est désormais connu comme le contrecoup de l’arbitrage d’investissement. Plus récemment, ces critiques se sont intensifiées au point que l’Union Européen a remplacé le RDIE contemporain par une cour permanente d’investissement pour régler ces différends. Une approche intermédiaire de la réforme du système par l’établissement d’un organe d’appel visant à donner de la cohérence aux nombreuses sentences arbitrales ad hoc est également envisagée. Cette thèse analyse les principales critiques du système du RDIE actuel afin d’examiner sa pertinence et effectue une comparaison entre les options de réforme, la manière dont elles sont censées résoudre les défauts du système, ainsi que les implications découlant de certaines des solutions les plus débattues. L’objectif de la thèse est de faire valoir qu’une refonte radicale ou révolutionnaire du système d’arbitrage des investissements ne fera que générer des incertitudes, susciter des problèmes juridiques et pratiques très complexes, et ne n’apportera finalement pas de meilleurs résultats. L’accent devrait plutôt être mis sur une indispensable évolution ou réforme substantielle au niveau des traités, afin de tirer les leçons des cas passés et de s’assurer que la rédaction des traités répond mieux aux défis actuels. = The dispute settlement regime between investors and States through ad hoc arbitration has come under heavy scrutiny and mounting criticism in the past few decades. As respondent States in various regions have lost investment arbitration cases, those States have become disenchanted with this form of dispute resolution mechanism in what has become known as the backlash against investment arbitration. More recently, these critiques have escalated to the extent that the European Union has replaced it with a completely new scheme that includes dismantling the investment arbitration system by replacing it with a permanent investment court to settle such disputes in its trade agreement. An intermediate approach to reforming the system, the establishment of an appellate body aimed at providing consistency to the numerous ad hoc arbitration awards, is also being considered. This thesis analyses the main criticisms of the current investor-State dispute settlement (“ISDS”) system to determine its validity and carries out a comparison between the policy reform options, how they are intended to solve the system’s purported flaws, as well as the implications arising from some of the hotly debated options. The aim of the thesis is to argue that drastic overhaul or revolutionary reform to the investment arbitration system will only lead to uncertainties, more complex legal and practical problems and would not yield better results. Instead, the focus should be on the evolution of substantive reform at the treaty level, to address the lessons learned from past cases and ensure that treaty drafting responds to current day challenges.
Keywords: Appellate Mechanism; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Convention CIRDI; Cour Multilatérale d’Investissement; Droit et État; Groupe de travail III de la CNUDCI; ICSID Convention; INVESTMENTS; ISDS; ISDS Reform; Incohérence de sentences arbitrales; Inconsistent Arbitral Awards; Investissements étrangers (droit international); Investisseurs et État; Investment Court System; Investor-State Dispute Settlement; Multilateral Investment Court; Mécanisme d’appel; RDIE; Règlement des différends; Règles de transparence; Réforme du RDIE; Système de Cour d’Investissement; Transparency Rules; UNCITRAL Working Group III

La négociation dans le règlement des litiges internationaux d'investissement - Paredes Balladares, Francisco Xavier (Université Paris 1, 2022)
La négociation est une institution fascinante du droit de l’investissement, polyvalente et multifonctionnelle. L’étude systématisée de la négociation dans le droit de l’investissement fait ressortir que cette institution est plus qu’un simple moyen permettant de parvenir à des accords. En réalité, la négociation est partout dans le droit de l’investissement. Il s’agit de la seule institution véritablement transversale au droit des investissements, qui intervient de nombreuses manières dans les rapports entre les investisseurs et les États d’accueil. Nous pouvons attester de l’existence des négociations avec la négociation des accords internationaux d’investissement ou de contrats d’investissement entre l’État d’accueil et l’investisseur. De surcroît, la négociation est un instrument au service de l’instance juridictionnelle qui sert aux arbitres dans l’interprétation des accords ainsi que pour la détermination de la responsabilité des parties. Si les divers rôles de la négociation dans le droit de l’investissement ont fortement contribué à l’évolution du droit international, la négociation reste une institution peu connue. Sa nature, sa portée, et son contenu juridique restent peu étudiés et non systématisés dans le droit de l’investissement. De ce fait, cette recherche offre une analyse approfondie de la négociation afin de trouver sa place dans l’ordre juridique de l’investissement (en général) et dans le règlement des litiges (en particulier). Nous examinerons dans cette recherche les nombreux apports de la négociation au droit de l’investissement permettant d’affirmer que la négociation constitue le mécanisme essentiel dans la conclusion des accords ; qu’elle impose aux parties des comportements précis ; qu’elle est un instrument qui permet aux tribunaux internationaux de déterminer la responsabilité des parties en fonction de leurs actions et inactions ; enfin, qu'elle constitue un instrument qui aide la justice arbitrale à interpréter les accords ponctuels. Ainsi, cette recherche a pour ambition de comprendre la nature, la portée et les fonctionnalités de la négociation dans le règlement des litiges transnationaux d’investissement. Negotiation is a fascinating instrument of Investment Law, versatile and rich in legal content. The systematic study of negotiation in Investment Law reveals that this institution is much more than just an instrument for reaching agreements. In fact, negotiation is everywhere. It is the only institution of Investment Law that is truly transversal, intervening in many layers of the relationship between investors and Host States. We can recognize the existence of negotiations from the very beginning of an investment process (the negotiation of a contract between the investor and the Host State), as well as negotiations over the course of the life and operation of an investment, and negotiations at the termination of a transnational investment project. Moreover, negotiation is an instrument that serves arbitral tribunal as element for the interpretation of the agreements, and the determination of the parties’ liability. The various roles of negotiation in Investment Law have certainly contributed to the evolution of international law. Nevertheless, negotiation remains an unknown institution to lawyers, regarding its nature, scope, uses and legal content. Investment law requires a thorough analysis of this institution and a structure that adapts to the transnational legal order. In this research, we will examine numerous contributions of negotiation to Investment Law: as a necessary mechanism for the conclusion of agreements that impact Investment Law; as a mandatory rule that it imposes specific behaviors on the parties in respect to the principle of good faith; as an instrument that serves international tribunals to determine the parties’ liability for their actions taken over the course of negotiations, and as an instrument to assist the justice system to construe contracts. Thus, the ambition of this research is to comprehend the nature, scope, and the features of negotiation in International Investment Law. La negociación es un instrumento fascinante de Derecho de las inversiones, a la vez versátil y rico en contenido legal. El estudio sistematizado de la negociación en el Derecho de las inversiones revela que esta institución es mucho más que un instrumento para alcanzar acuerdos. En realidad, la negociación está en todas partes en el derecho de las inversiones. Es laúnica institución verdaderamente transversal al Derecho de las inversiones, que interviene de varias formas en la relación entre inversionistas y los Estados receptores de inversión. Podemos constatar la existencia de las negociaciones desde el inicio de un proceso de inversión (en la negociación de un tratado bilateral deinversión, o de un contrato entre el inversionista y el Estado anfitrión), negociaciones durante la vida y la operación de una inversión y negociaciones encaminadas a la terminación o liquidación de la inversión transnacional. Resalta, además, que la negociación es un instrumento al servicio de la instancia jurisdiccional, que sirve a los árbitros en su tarea de interpretación de acuerdos, y a la determinación de la responsabilidad de las partes. Los diversos roles que presenta la negociación en el Derecho de las inversiones ciertamente han contribuido a la evolución del Derecho internacional. Sin embargo, la negociación sigue siendo una institución poco conocida por los juristas, especialmente en lo tocante a su naturaleza, alcance, usos y contenido legal. ElDerecho de las inversiones requiere de un análisis exhaustivo de esta institución, acompañado de una estructura que se adapte al orden legal transnacional.En esta investigación examinaremos las diversas contribuciones que hace la negociación al Derecho de las inversiones, a saber: se muestra como un mecanismoinevitable para concluir acuerdos que terminan contribuir en la evolución del Derecho de las inversiones; impone a las partes comportamientos específicos enrespeto del principio de la buena fe; es un instrumento para que los tribunales internacionales determinen la responsabilidad de las partes en razón de sus accionesdurante la fase de negociación y se constituye en un instrumento que asiste al sistema de justicia en la tarea de interpretar los acuerdos. La ambición de esta investigación no es otra cosa que comprehender la naturaleza, el alcance y la funcionalidad de la negociación en el Derecho internacional de las inversiones.
Keywords: Accord; Arbitrage; Arbitrage d'investissement; Arbitration; Bonne foi; Buena fe; Contenido jurídico; Contract interpretation; Contrahendo; Contrato; Derecho Internacional Público; Derecho de las Inversiones; Droit de l’investissement; Droit international; Duty to negotiate; Estoppel; Good faith; Interpretación de acuerdos; Interprétation de l’accord; Investissements étrangers; Investment Law; Investments; Justicia; Negociación; Negotiando; Negotiation; Negotiation agreement; Négociation; Négociations; Obligación de negociar; Obligation de négocier; Pacto de negociación; Pactum; Período de negociación; Public International Law; Transnacional; Transnational

Visão Contemporânea da Jurisdição Arbitral - Bellocchi, Marcio (Universidade de São Paulo, 2022)
A questão fundamental que está por detrás da investigação feita para elaboração deste estudo consiste em saber se a arbitragem é jurisdição. A pesquisa foi conduzida de forma analítica de molde a que conclusões fossem alcançadas no sentido de se saber até que ponto a arbitragem é mesmo jurisdição. É claro que, para que isso fosse feito, isto é, para que esse caminho fosse percorrido, o primeiro tema a ser tratado deveria ser, necessariamente, a própria jurisdição. Trata-se de um conceito construído pela cultura humana cujo conteúdo, exatamente por isso, variou ao longo da história. Seguiu-se a mesma abordagem no que diz respeito à arbitragem. Assim, o primeiro objetivo desta tese foi o de acompanhar a evolução do conceito de jurisdição, ao longo do tempo, como forma de composição de conflitos, desde o direito romano, até a atualidade. Foi explorado o caminho pelo qual passou a jurisdição, com o fim de se investigar por qual motivo, em determinado momento, se começou a afirmar, de modo peremptório, que a jurisdição seria uma atividade realizada exclusivamente pelo Estado. O segundo objetivo consistiu em analisar a arbitragem, pondo-a lado a lado com a jurisdição estatal, explorando-se os pontos que ambos os fenômenos apresentam em comum, assim como os que diferenciam essas duas formas de exercício do poder-dever de julgar. Por isso, foi objeto de investigação e reflexão uma outra função da jurisdição estatal, recentemente assumida de forma clara pela jurisdição estatal, que é a de contribuir para a criação do direito. Procurou-se identificar em que contexto e extensão isso pode acontecer, tanto na jurisdição do Estado, quanto na jurisdição contratada pelas partes. Em um terceiro momento deste estudo, colocamos luzes sobre determinados institutos do processo civil, desenvolvendo-os, também, no terreno do procedimento arbitral. Num quarto e último momento, nossas reflexões se voltaram para o problema de se saber até que ponto a arbitragem seria mesmo jurisdição, equivalente à jurisdição estatal, em todos os seus aspectos, em toda a sua extensão, seus limites e suas funções. The fundamental question behind the research done to prepare this paper is whether arbitration is jurisdiction. The research has been conducted in an analytical manner so that conclusions could be reached in order to know to what extent arbitration is even jurisdiction. For this to be done, the first topic to be addressed should necessarily be jurisdiction itself. This is a concept constructed by human culture whose content, precisely for this reason, has varied throughout history. The same approach has been followed about arbitration. Thus, the first aim of this thesis was to follow the evolution of the concept of jurisdiction, over time, as a form of dispute resolution, since Roman law, until today. Jurisdiction has been explored, to investigate why, at a certain point, it began to affirm, peremptorily, that jurisdiction would be an activity performed exclusively by the State. The second aim was to analyze arbitration, placing it side by side with State jurisdiction, exploring points that both: state and arbitral jurisdiction have in common, as well as those that differentiate these two forms of judging. Therefore, another function, recently clearly assumed by the state jurisdiction, which is to contribute to the creation of law, has been object of investigation and reflection. It was sought to identify in what context and extent this can happen, both in the State and arbitral jurisdiction. In a third moment of this study, we shed light on certain institutes of civil procedure, developing them, also, in the field of arbitration procedure. In a fourth and last moment, our reflections turned to the problem of knowing to what extent arbitration would even be jurisdiction, equivalent to the State jurisdiction, considering all its aspects, its extent, limits and functions.
Keywords: Arbitrage; Arbitragem; Arbitration; Creation; Criação; Jurisdiction; Jurisdição; Procedure; Processo

Assessment Report of Arbitration Centre in Egypt (CRCICA) - SNFI (African Development Bank, 2022)

Arbitrage commercial international - Weiszberg, Guillaume (Arbitrage commercial international (seconde édition) (int), 2022)
La première version de cet article (datant de 2010), traitait largement de la jurisprudence et de la doctrine, parfois confidentielle, et le droit de l’arbitrage du commerce international (au moins dans sa conception et sa présentation françaises) était chaque jour davantage affiné , il complétait des formations internationales, les sources s’éclaircissaient, les commentaires foisonnaient et, aujourd’hui, nous vivons sans doute l’âge d’or de l’arbitrage commercial international[1]. Surtout, la première édition n’avait pu rendre compte de la réforme opérée peu après par ‘‘‘décret du 13 janvier 2011’‘‘. Un décret du Premier ministre français, autant dire tout de suite que le champ de l’étude présentée ici est à dominante principale franco-française, et que la principale préoccupation ici relèvera du ‘‘droit de l’arbitrage’’ dans une conception comparée, mais à partir du modèle français. Ainsi des réflexions seront menées dans le cadre du droit comparé et conventionnel international de ce type de résolution extra-judiciaire qu’est l’arbitrage commercial international, avec la présence à Paris de la Chambre de commerce internationale (CCI) et de sa Cour internationale d’arbitrage (CIA/CCI ci-après). La France est à l’avant-garde du sujet. Compte tenu de l’application de la loi dans le temps et pour une meilleure intelligibilité de la réforme, une réforme voulue par les acteurs et les juristes, ‘‘lato sensu’’, le droit antérieur à la réforme de 2011 est rappelé plus ou moins cursivement, qui montrera utilement les nombreux « progrès » de la discipline.

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

La notion de sentence arbitrale : étude de droit de l'arbitrage commercial - Merabti, Priscilla (Université Paris 1, 2022)
Qu’est-ce qu’une sentence arbitrale ? La sentence arbitrale est le résultat attendu par les parties qui se soumettent à une procédure arbitrale. Elle constitue le seul outil juridictionnel mis à la disposition de l’arbitre au cours d’un arbitrage. La sentence se voit revêtue d’un régime particulier, qui n’est pas ouvert aux autres types d’actes délivrés par l’arbitre, qui sont les ordonnances de procédures. La qualification en tant que sentence arbitrale d’une décision est donc une question primordiale, lorsqu’il est question d’arbitrage. La notion de sentence arbitrale n’est pas identique d’un droit à un autre et la définition française de la sentence arbitrale issue de l’arrêt Sardisud de la cour d’appel de Paris apporte son lot d’incertitudes en termes de qualification. En effet, la confrontation de cette définition à un certain nombre de cas d’objet d’étude suscite des interrogations. Ces interrogations poussent à l’analyse de chacun des critères permettant sa qualification, questionnant leur interprétation, mais aussi parfois leur nécessité. Certaines « zones grises » font naître des doutes de qualification de certaines décisions délivrées par l’arbitre en tant que sentence arbitrale : c’est le cas de la mesure provisoire, mais aussi de la sentence d’accord-parties. D’autres cas de figure posent des difficultés de qualification en deux temps, avec tout d’abord la question de la qualification de la procédure en tant qu’arbitrage et ensuite celle de la décision qui en découle en tant que sentence arbitrale. En effet, ces deux qualifications sont étroitement liées, d’une part puisque la sentence arbitrale ne peut exister sans arbitrage et d’autre part, car il existe une porosité des critères utilisés dans les définitions de l’arbitrage et de la sentence arbitrale. Ces difficultés de qualification en deux temps existent dans le cadre de la procédure d’arbitrage à deux degrés, la procédure devant un Dispute Adjudication Board en matière de construction, lors des procédures pré-arbitrales d’urgence, mais aussi lors d’une demande d’adaptation de contrat à un arbitre. L’étude de l’ensemble de ces cas de figure offre la possibilité de mettre à l’épreuve la définition actuelle de la sentence arbitrale, de souligner ses déficiences et de proposer une nouvelle approche de la notion de sentence arbitrale qui se décompose en deux propositions : d’une part, une interprétation plus élargie de certains critères utilisés dans la définition de la sentence arbitrale et d’autre part la disparition de certains critères qui apparaissent injustifiés.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; Arbitres (droit); Notion; Qualification; Sentence arbitrale

Effectiveness of the Recognition and Enforcement of the OHADA`S Arbitral Award - Juvelin, Rezara (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization consists of arbitral tribunal within regions in Africa to deal with international disputes on investment and commercial related. Henceforth, the purpose of the study examines the effectivity of arbitral awards enforcement under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal effect to country members, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards, effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving the arbitration rules on enforcement of arbitral awards. It is found the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law for undefinable conflict of interest
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Enforcement; OHADA; res judicata and exequatur

L’exécution des sentences arbitrales contre les personnes publiques de l’OHADA - Vodounon-Djegni, Comlan René (Université Côte d'Azur, 2022)
La thèse porte sur « L’exécution des sentences arbitrales contre les personnes publiques de l’OHADA ». Elle a pour but de démontrer comment mettre en œuvre ces sentences sans se heurter à l’immunité d’exécution des personnes qui en bénéficient. En effet, en l’absence d’une exception arbitrale, l’interdiction de l’exécution forcée et des mesures conservatoires à l’encontre de ces personnes semble s’étendre à l’exécution forcée des sentences arbitrales contre les personnes publiques de l’OHADA. Or, comme ces dernières, l’immunité d’exécution a également un fondement contractuel ; c’est une règle d’ordre public de protection à laquelle le bénéficiaire peut renoncer. Donc, son application ne serait requise que si son bénéficiaire n’y a pas renoncé. Mais, pour être valable, la renonciation à l’immunité d’exécution doit être expresse, au sens du droit international coutumier, dont fait partie la Convention des Nations Unies sur l’immunité juridictionnelle des Etats et de leurs biens du 2 décembre 2004, applicable en droit OHADA, pour raison de droit. Cette condition de validité de la renonciation pose le problème de l’efficacité des contrats soumis aux règles impératives du droit public ou des conventions et règlements d’arbitrage. Alors, faudrait-il envisager la réécriture des modèles habituels de conventions et règlements d’arbitrage pour y intégrer cette condition ? Cette approche garantirait l’effectivité des sentences arbitrales administratives, sur le fondement de la force obligatoire des contrats (Pacta sunt servenda) et de leur exécution de bonne foi. Aussi, pourrait-on renforcer cette renonciation par la mention de biens affectés à l’activité en cause ou à l’exécution de la sentence qui s’ensuivra sans lien avec l’activité qui y a donné lieu. En tout état de cause, l’immunité d’exécution ne s’oppose ni à l’identification des débiteurs des condamnations pécuniaires des personnes publiques, ni à l’exequatur des sentences arbitrales adm inistratives, ni même à l’exécution volontaire ou spontanée desdites sentences. Ainsi, en dépit de sa conception absolue ou stricte, l’immunité d’exécution de l’OHADA a des limites à l’égard des sentences arbitrales administratives.
Keywords: Administrative arbitration award; Arbitrage; Arbitrage (droit administratif); Arbitragem; Arbitration; Mandatory rules of public law; Organisation pour l'harmonisation en Afrique du droit des affaires; Personnes publiques; Renonciation à l’immunité d’exécution; Règles impératives du droit public; Sentence arbitrale administrative; Waiver of immunity from execution

L'attractivité de l'arbitrage au regard des nouvelles réformes de l'OHADA - Kounouho, Marcson Smile Geoffroy Tagnon (Université d'Abomey-Calavi, 2022)

Third Party Investment in International Commercial Arbitration - Ebrahimi, Seyed Sadegh; Boloori, Peyman; Solhchi, Mohammad Ali (Public Law Researsh, 2022)
International commercial arbitration imposes heavy costs to the parties involved. In this regard, one of the new phenomena in international commercial arbitration is "financing of court costs by a third party investor. There are several reasons for the emergence of a third party investor: 1- involved parties may not have the resources to pay for the costs of arbitration or they may be reluctant to use their funds to finance the litigation: 2. the uncertainty of receiving compensation as a result of paying the arbitration fees might encourage the parties to transfer this risk to a third party; 3. having its own advantages and disadvantages. Since the funder holds the power of the purse, TPF entails the risk of the control of the claim being transferred to the third party funder. We might ask whether international arbitration tribunals should examine the extent of the investor's influence in determining the allocation of costs or not. In addition, is it essential to disclose the third parties contracts confidential? Overall, it is concluded that those mentioned Tribunals should allocate and guarantee the arbitration cost and agree on disclosing of third parties fund contracts under urgent conditions by international arbitration tribunal. مراجعه به داوری تجاری بین المللی هزینه های کلانی را برای طرفین درگیر در فرآیند داوری به همراه دارد و تأمین این هزینه ها در خیلی از موارد به‌صورت مانع در مراجعه به داوری نمود پیدا می‌کند. در همین راستا یکی از پدیده‌های جدید در داوری تجاری بین المللی، «تأمین مالی هزینه دادرسی توسط سرمایه گذار ثالث» است. ظهور سرمایه گذار ثالث دلایل متعددی دارد؛ اولاً طرفین دعوی ممکن است فاقد امکانات مالی کافی برای هزینه های داوری باشند، ثانیاً ممکن است طرفین دعوی تمایلی به استفاده از منابع مالی خود برای تأمین مالی دادرسی پرهزینه نداشته باشند، ثالثاً عدم قطعیت ذاتی که در زمینه امکان اخذ خسارت در نتیجه دادرسی وجود دارد می تواند باعث تمایل طرف منازعه به انتقال این ریسک به شخص ثالث شود. پرسش این است که آیا محاکم تجاری بین‌المللی تعیین تخصیص هزینه‌ها بپردازد یا خیر؟ و آیا افشاسازی قراردادهای شخص ثالث ضروری می‌باشد؟ در نهایت این نتیجه حاص می‌شود که محاکم مذکور باید به تعیین تخصیص و تضمین هزینه‌های داوری پرداخته و از سویی با افشاسازی قراردادهای تامین مالی شخص ثالث در داوری تجاری بین المللی، در شرایط خاص و ضروری موافقت نمایند.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Cost Allocation; Disclosure; International Arbitration Tribunals; International commercial arbitration; Investments; Third Party Investment; Third parties; افشاسازی; تخصیص هزینه‌ها; داوری تجاری بین‌المللی; دیوان‌های داوری بین‌المللی; سرمایه‌گذاری شخص ثالث

A Legal Analysis of the Structure of Dispute Resolution Mechanisms of International Tax Agreements - Salehifar, Alireza (Public Law Researsh, 2022)
As international trade is expanding, international trade and tax disputes are increasing. Under international tax agreements, there are two mechanisms for the resolution of potential disputes between contracting States. These agreements mostly rely on a form of negotiation known as the “Mutual Agreement Process (MAP)” as the main mechanism for the settlement of disputes. During the last decade, the inclusion of “ad hoc arbitration” as a new dispute resolution mechanism in international tax treaties has become popular to augment the MAP. Iran has long concluded several international tax agreements with several countries for the avoidance of double taxation. Due to Iran’s macroeconomic policy for relying more on tax revenues as an alternative to revenues from the petroleum industry, it is important that the Iranian lawyers seek to focus more on tax law and tax dispute resolution mechanisms. The purpose of this article is to introduce and critically analyse the dispute resolution mechanisms of international tax agreements. In this article, to make some suggestions for the improvement of the dispute resolution system of tax treaties, the strengths and weaknesses of the MAP and ad hoc arbitration, will be scrutinised by adopting a descriptive-analytical approach. همسو با گسترش تجارت فراسرزمینی،‌ میزان دعاوی مرتبط با تجارت و مالیات‌های بین‌المللی نیز افزایش یافته است. در بسیاری از معاهده‌های مالیاتی بین‌المللی برای حل اختلافات، دو ساز و کار با عنوان «فرآیند توافق دوجانبه» و «داوری موردی» وجود دارد. فرآیند توافق دوجانبه که مبتنی بر مذاکره بین طرفین معاهده است بعنوان ساز و کار اصلی و داوری موردی هم که در یک دهه اخیر در این معاهده‌ها رواج یافته، بعنوان ساز و کار مکمل فرآیند توافق دوجانبه برای حل اختلافات استفاده می‌شوند. ایران از دیرباز جهت اجتناب از مالیات مضاعف، معاهده‌های مالیاتی متعددی را با کشورهای مختلف منعقد نموده است. همچنین سیاست کلان اقتصادی کشور در سال‌های اخیر مبتنی بر اتکای بیشتر به درآمدهای مالیاتی بعنوان جایگزینی برای درآمدهای نفتی بوده است. لذا اهمیت شناخت این نوع معاهده‌ها و‌ مکانیسم‌های حل و فصل اختلافات آنها برای حقوقدانان کشور بیش از پیش آشکار می‌شود. هدف این مقاله معرفی،‌ تحلیل و نقد ساز و کارهای موجود در معاهده‌های مالیاتی بین‌المللی برای حل اختلافات می‌باشد. در این مقاله نقاط ضعف و قوت فرآیند توافق دوجانبه و داوری موردی به شیوه توصیفی-تحلیلی بیان و راهکارهایی جهت بهبود این مکانیسم‌ها ارائه می‌شود.
Keywords: Arbitrage; Arbitragem; Arbitration; Dispute Resolution; International Tax Agreements; Mutual Agreement Procedure (MAP); Negotiation; داوری; فرآیند توافق دوجانبه; مذاکره; معاهده مالیاتی بین‌المللی; ‌ حل و فصل اختلاف

The Singapore Convention on Mediation: a commentary - Alexander, Nadja; Chong, Shouyu; Giorgadze, Vakhtang (Kluwer Law International, 2022)
Article-by-article commentary
Keywords: Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018)

İslam borçlar hukuku açısından ticari ihtilafların çözümünde 'Arabuluculuk' - Almasri, Raed (Ankara Üniversitesi, 2022)
Bu tez, anlaşmazlıkları çözmede arabuluculuk konusunu ele almaktadır. Arabuluculuk konusu ticari mali muamelelerdeki anlaşmazlıklar ile sınırlıdır. Dolayısıyla tez ailevi anlaşmazlıklardaki nafaka gibi diğer mali anlaşmazlıklara değinmemektedir. Tez konusu fıkhi açıdan ele alındığı için, dört fıkhi mezhebin konuyla ilgili görüşleri, mukayeseli olarak işlenmiş, mezhepler arasında ihtilaf ve ittifak edilen noktalar ele alınmış ve görüşler arasında tercih yapılarak ortaya konulmuştur. Tez; bir mukaddime, üç bölüm, bir sonuç ve kaynakçadan meydana gelmektedir. Mukaddime de tezin planı, fihrist ve içerik ele alınmıştır. Tezin birinci bölümünde; arabuluculuk kavramının tanımı ve meşruiyeti, ikinci bölümde; arabuluculuğun rükünleri ve arabuluculukla ilgili hükümler ve şartlar, üçüncü bölümde ise; arabuluculuğun sonuçları ve etkisi ele alınmıştır. The dissertation aims to cover the subject of mediation in dispute resolutions exclusively in commercial disputes. Therefore, the research does not cover mediation in other disputes such as domestic disputes even when it's related to financial matters such as alimony. The research also studies mediation in commercial disputes from a jurisprudential perspective. Hence the jurists' opinions are presented and analyzed in a comparative approach to show its similarities, differences and present a jurisprudential preference. The dissertation is presented in an introduction, three chapters, a conclusion followed by the list of references and resources. The introduction provides an insight into the research contents and methodology. The first chapter discuss the definition of mediations and its legitimacy. The second chapter tackle the main pillars of mediations and clarify its ruling and conditions. Finally, the third chapter view the results of mediations and its expected impacts.
Keywords: Arabuluculuk; Borçlar hukuku; Commercial disputes; Incompatibility; Islamic law; Law of obligations; Mediation; Ticari uyuşmazlıklar; Uyuşmazlık; İslam hukuku

Dissenting opinions in international arbitration : More than an opinion? - Baltag, Crina (Principia, 2022)
Dissenting opinions have increasingly gained acceptance in international arbitration, with arbitration rules and laws allowing them, by either providing directly for such a possibility, or indirectly, by referring to ‘arbitral awards taken with majority of votes.’ Alan Redfern’s seminal 2003 Freshfields Lecture on dissenting opinions has highlighted the benefits, as well as the concerns with dissenting opinions, in particular, with those directed to alleged irregularities in the arbitral procedure. More recently, in the motion to set aside the arbitral award in Vantage Deep Water Co. v. Petrobras Am., Inc., the US District Court for the Southern District of Texas has rejected Petrobras’ argument that ‘the arbitral process was [so] “fundamentally flawed” … that “produced the extraordinary Dissent filed” by Mr Gaitis.’ While it is accepted that dissenting opinions have no legal effects, and in particular no legal effects similar to arbitral awards, they can have significant impact on the set aside and recognition and enforcement of arbitral awards. Las opiniones disidentes han ganado aceptación en el arbitraje internacional mediante reglas de arbitraje y leyes permitiéndolos, ya sea aceptando directamente la posibilidad de emitirlos, o indirectamente refiriéndose a ‘laudos arbitrales decididos por mayoría de votos’. El seminario del 2003 de Freshfields dictado por Alan Redfern sobre opiniones disidentes llamó la atención sobre los beneficios y las preocupaciones, en particular, aquellas opiniones disidentes dirigidas a señalar irregularidades en el procedimiento arbitral. Más recientemente, durante el procedimiento para anular el laudo arbitral de Vantage Deep Water Co. v. Petrobas Am., Inc., la Corte del Distrito Sur de Texas rechazó el argumento de Petrobras de que ‘el procedimiento arbitral había sido [tan] “fudamentalmente viciado…” que “produjo la extraordinaria opinión disidente consignada” por el Sr., Gaitis’. Mientras que es aceptado que las opiniones disidentes no tienen efectos legales, y en particular ningún efecto legal parecido a los laudos arbitrales, pueden lograr impactar significativamente a lograr la nulidad y el reconocimiento y ejecución de los laudos arbitrales.
Keywords: Anulación; Arbitral Awards; Dissenting opinions; Laudo arbitral; Recognition and enforcement; Reconocimiento y ejecución; Set aside; Voto salvado

Règlements d’Arbitrage en vigueur à compter du 1er janvier 2021 et de Médiation en vigueur à compter du 1er janvier 2014 - Chambre de commerce internationale (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; MARD; Mediación; Mediation; Mediação; Médiation; Règlement d'arbitrage; Règlement de médiation

COFOLA International 2022: Current Challenges of Resolution of International (Cross-Border) Disputes (Publications of the Masaryk University, theoretical series, editions Scientia, 2022)
- Bridging the Public-Private Law Divide in the Conflict of Laws; - New Practices in Alternative Dispute Resolution: New Pathways to Peace; - The Singapore Convention: A Giant Leap for Mediation or Just Too Good to Be True; - Potential Nexus Between the Enforceability of Foreign Judgments and the Quality of Civil Justice in ASEAN Did the Preliminary Objections Judgment Resolve the Chagos Archipelago Sovereignty Dispute? - The Order of Periodic Penalty Payments by the CJEU in Cases Filed by a State Against Another State; - The Dichotomy of Obligations of Conduct and Result in International Investment Law; - Investment Arbitration Reform: Third-Party Funding in Investment Arbitration; - Between Protection and Access to Justice: On the Regulation of Returns in Third-Party Litigation Funding; - Contract Adjustment in Arbitration : Should the Approach Be Adjusted? - Current Challenges of Enforcing Annulled Arbitral Awards; - Condifentiality of Arbitral Awards on National, International and Institutional Level; - Digitalisation of Judicial Cooperation in the EU: A Long Road Ahead; - Resolving Cross-Border Consumer Disputes: The Digital Experience in China; - Law Applicable to Non-Consumer Contracts Concluded at an Electronic Auction; - Can Robot Judges Solve the So-Called “Hard Cases”? - Current Challenges of Cross-Border Disputes in Slovakia : Is Slovak Law Anchored in the 21st century

Arbitration Rules In force as from 1 January 2021 and Mediation Rules In force as from 1 January 2014 - International Chamber of Commerce (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration rules; MARD; Mediación; Mediation; Mediation rules; Mediação; Médiation

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

Los medios jurisdiccionales de solución de las controversias internacionales : avances y nuevos retos - Petrova Georgieva, Virdzhiniya (Doctrina Jurídica, 2022)

A Closer Look at the Doctrine of Separability in Arbitration - Todorović, Ilijana (IUS LAW Journal, 2022)
In the ever-growing business world impacted by globalization, many commercial contracts nowadays contain an arbitration clause. This article focuses on the history behind arbitration as an alternative method of dispute resolution and its penetration to the forefront of mechanisms for resolving commercial disputes -with focus on England, France, and the United States. The article also delves into some of the key questions related to the relationship between an arbitration clause and the underlying contract in which it is contained. And those are the infamous separability and competence-competence doctrines. The author’s conclusion is that the efficiency of an arbitration clause is feasible only if its autonomy is entrenched and safeguarded from preventative and baseless court intervention. In that regard, the author addresses the consequences, current challenges, judicial and academic discourse, and the need for improvement when it comes to these two arbitral principles -all with the goal to provide contracting parties with forethought as to what to consider when drafting their contracts as to avoid unwelcome consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Competence-Competence; Doctrine; International Arbitration; Issues of Jurisdiction

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

ال رقابة القضائية على أحكام ال ت حكيم دراسة مقارنة في القوانين العربية - زريفي, محمد (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
إن كان التحكيم طريقا بديلا للقضاء في حسم المنازعات، فإن عملية التحكيم تحتاج لكي تكتمل أسباب فاعليتها وانفاذ أحكامها لتدخل قضاء الدولة باعتباره سلطة عامة، تملك قوة إل ا زم الخصوم بتنفيذ أحكام المحكمين. ومن باب المفارقة، أن هذه الرقابة القضائية على أحكام التحكيم، تؤدي إلى إقحام القاضي الوطني في ن ا زع، أستبعد منه مسبقا بإ ا ردة المتنازعين، إلا أن المفارقة ظاهرية، حيث أن دور القاضي يبقى منحص ا ر في رقابة مدى مطابقة الحكم التحكيميي لمبادئ أساسية، أتت على سبيل الحصر، دون أن يكون له فحص وقائع وموضوع الن ا زع. غير أن تحديد سلطة القاضي لي س مطلقة، فبناء على المقاربة الجديدة المبنية على نوع المصالح المطلوب حمايتها، كمعيار لتحديد درجة وشدة الرقابة المسلطة على حكم لتحكيم، يستطيع هذا الأخير، تعديل رقابته بين مشددة ومخففة . وعلى هذا الأساس، فإن غالبية القضاءات العربية تبنت موقفا وسطيا بين مذهبي التوسع والتضييق من نطاق رقابة المحاكم على حكم التحكيم الدولي، تماشيا مع متطلبات التجارة الدولية ومقتضيات مصالحها الوطنية . If arbitration is an alternative means of resolving disputes, the arbitration process needs, for the reasons of its effectiveness and the application of its provisions, the intervention of the judicial power of the State, in order to oblige the parties to carry out the arbitral awards. Paradoxically, this judicial review of arbitral awards leads to involving the national judge in a dispute, which was previously excluded by the will of the parties in dispute. However, this paradox is apparent, because the role of the national judge remains limited to the strict control of the compliance of the arbitration award with the basic principles enacted in an exclusive manner, without having to examine the facts and the subject of the dispute. However, this limitation of judicial power is not absolute, because on the basis of the new approach, based on the type of interests to be protected, as the criterion for determining the extent of the control exercised over an arbitral award, the latter can modulate its control between strict and attenuating. On this basis, the majority of Arab jurisdictions have adopted a middle position between the two tendencies, so-called maximalist control, and minimalist tendency of the jurisdictions' control over the international arbitration award, in accordance with the needs of international trade and the requirements of their interests. Si l'arbitrage est un moyen alternatif pour de résoudre les différends, le processus d'arbitrage a besoin, pour les raisons de son efficacité et l'application de ses dispositions de l'intervention du pouvoir judiciaire de l'État, afin d'obliger les parties d'exécuter les sentences arbitrales. Paradoxalement, ce contrôle judiciaire sur les sentences arbitrales conduit à impliquer le juge national dans un litige, qui en était auparavant exclu par la volonté des parties en litige. Toutefois, ce paradoxe est apparent, car le rôle du juge national reste limité au strict contrôle de la conformité la sentence arbitrale aux principes de base édicté d’une manière exclusive, sans avoir à examiner les faits et l'objet du litige. Cependant, cette limitation de pouvoir juge n'est pas absolue, car sur la base de la nouvelle approche, fondée sur le type d'intérêts à protéger, comme critère de détermination de l'étendue du contrôle exercé sur une sentence arbitrale, ce dernier peut moduler son contrôle entre strict et atténuant. Sur cette base, la majorité des juridictions arabes ont adopté une position médiane entre les deux tendances, contrôle dite maximaliste, et tendance minimaliste du contrôle des juridictions sur la sentence d'arbitrage international, conformément aux besoins du commerce international et aux exigences de leurs intérêts.
Keywords: Arbitrage international; Arbitration; Commerce international; Contrôle des juridictions; International Trade; International arbitration award; Sentence arbitrale

L'intervention du juge étatique dans l'arbitrage : une approche de droit comparé - Ranjbari, Hiva (Université Paris Cité, 2021)
Aujourd'hui, l'arbitrage s'impose comme un mode indépendant de règlement des litiges. Même si l'arbitrage implique, par définition, l'exclusion de la compétence juridictionnelle des tribunaux étatiques, un lien existe entre la justice arbitrale et la justice étatique. Cette étude concerne l'intervention du juge étatique dans l'arbitrage international. Elle a été menée à partir des systèmes français, anglais et suisse. L'intervention du juge étatique dans l'arbitrage, obéit à deux principes directeurs : l'efficacité de l'arbitrage en tant qu'un mode définitif de règlement des litiges ; et le respect des droits fondamentaux et de l'ordre public international. En premier lieu, le juge peut être appelé à intervenir en soutien de l'arbitrage, complétant la compétence de l'arbitre pour des questions qui excèdent ses pouvoirs, avant et pendant la procédure arbitrale. En second lieu, il peut intervenir pour contrôler la sentence rendue. Avant le prononcé de la sentence, l'efficacité de l'arbitrage suppose l'appui du juge étatique dans certaines situations comme le commencement de la procédure arbitrale, la désignation des arbitres, ou le prononcé des mesures provisoires et conservatoires. Le juge apporte son soutien à l'arbitrage pour assurer le bon déroulement de la procédure. Après le prononcé de la sentence, l'intervention du juge prend la forme d'un contrôle judiciaire, l'idée directrice est d'assurer la protection des droits des parties et de l'ordre public international. Aujourd'hui, l'arbitrage s'impose comme un mode indépendant de règlement des litiges. Même si l'arbitrage implique, par définition, l'exclusion de la compétence juridictionnelle des tribunaux étatiques, un lien existe entre la justice arbitrale et la justice étatique. Cette étude concerne l'intervention du juge étatique dans l'arbitrage international. Elle a été menée à partir des systèmes français, anglais et suisse. L'intervention du juge étatique dans l'arbitrage, obéit à deux principes directeurs : l'efficacité de l'arbitrage en tant qu'un mode définitif de règlement des litiges ; et le respect des droits fondamentaux et de l'ordre public international. En premier lieu, le juge peut être appelé à intervenir en soutien de l'arbitrage, complétant la compétence de l'arbitre pour des questions qui excèdent ses pouvoirs, avant et pendant la procédure arbitrale. En second lieu, il peut intervenir pour contrôler la sentence rendue. Avant le prononcé de la sentence, l'efficacité de l'arbitrage suppose l'appui du juge étatique dans certaines situations comme le commencement de la procédure arbitrale, la désignation des arbitres, ou le prononcé des mesures provisoires et conservatoires. Le juge apporte son soutien à l'arbitrage pour assurer le bon déroulement de la procédure. Après le prononcé de la sentence, l'intervention du juge prend la forme d'un contrôle judiciaire, l'idée directrice est d'assurer la protection des droits des parties et de l'ordre public international.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitraje; Arbitral proceedings; Arbitral tribunal; Arbitration; Dispute settlement; Interim measures; International Arbitration; Mesures provisoires; Ordre public; Procédure arbitrale; Public policy; Sentence arbitrale; Tribunal arbitral

Les compétences exclusives en matière civile et commerciale : étude de droit international privé - Georgakoudi, Nikoleta (Université Paris 1, 2021)
La consécration des règles de compétence exclusive en matière civile et commerciale est largement admise en droit international privé comparé. Elles sont généralement présentées comme étant fondées sur l’implication de la souveraineté de l’État, soit parce que son territoire est physiquement en cause soit parce que le litige concerne le fonctionnement des services publics de l’État. À ces arguments juridiques, s’ajoute une série de considérations pratiques, comme la coïncidence nécessaire entre le forum et le jus. Toutefois, les arguments avancés, afin d’expliquer l’édiction de ces règles de compétence, sont-ils véritablement convaincants, surtout si on se place dans un espace judiciaire fortement intégré, fondé sur la confiance mutuelle et la coopération, comme celui de l’Union européenne ? Le caractère raisonnable des fors exclusifs est, en effet, critiqué dans certains domaines visés, puisque la prépondérance de l’élément étatique dans une matière ne requiert pas l’adoption d’une compétence exclusive. Les règles de compétence exclusive peuvent, par ailleurs, susciter des problèmes pratiques lors de leur mise en œuvre et on assiste à une profonde mutation, au niveau européen, du for exclusif prévu en matière de propriété intellectuelle. Dans ces conditions, il convient de s’interroger sur l’avenir et même la pertinence de la survivance de ces règles. Un système alternatif d’organisation des compétences, fondé sur la coopération et le dialogue fluide entre les juges, est envisageable, dans l’espace judiciaire européen, permettant d’échapper à l’exclusivité de la compétence juridictionnelle dans certaines matières visées. The establishment of exclusive jurisdiction rules in civil and commercial matters is widely accepted in comparative private international law. These rules are generally presented as being based on the implication of State sovereignty, either because its territory is physically involved or because the dispute concerns the functioning of the State public services. In addition to these legal arguments there is a series of practical considerations that support the justification of the court’s exclusive jurisdiction, such as the necessary coincidence between the forum and the jus. However, an open question is whether the arguments, put forward to explain the adoption of these rules of jurisdiction, are really convincing, especially in a highly integrated judicial area, based on mutual trust and cooperation, such as the European Union. The rationality of exclusive fora is indeed criticized in some of the concerned areas, since the preponderance of the state element in a matter does not require the adoption of an exclusive jurisdiction rule. Moreover, the rules on exclusive jurisdiction may give rise to practical problems when implemented, and we are witnessing a profound change, at European level, of the exclusive forum provided in intellectual property matters. Under these conditions, it is appropriate to question the future and even the relevance of the survival of these rules. An alternative system of jurisdiction, based on cooperation and fluid dialogue between judges, is conceivable in the European judicial area, making it possible to avoid the court’s exclusive jurisdiction in certain targeted matters.
Keywords: Arbitrage commercial international; Arbitrage international; Civil Procedure; Compétence exclusive en raison de la matière; Conflict of jurisdictions; Conflit de juridictions; Droit international privé; European Union law; European federalism; Exclusive subject matter jurisdiction; Fédéralisme européen; Hague Convention system; International Arbitration; Mechanisms of inter-jurisdictional cooperation; Mécanismes de coopération interjuridictionnelle; Principe de souveraineté; Principle of sovereignty; Private international law; Procédure civile; Procédure civile (droit européen); Système des conventions de La Haye; Union européenne (droit)

L'obligation de règlement des différends à la charge des organisations internationales - Weil, Elodie (CY Cergy Paris Université, 2021)
Le travail de recherche porte sur les modes et modalités de règlement des différends qui mettent en cause directement une organisation internationale. En fait très peu de mécanismes de règlement des différends sont prévus ou existent pour engager la responsabilité d'une organisation internationale ou mettre en cause la légalité de l'un de ses actes. C'est vrai qu'aujourd'hui il y a une prise de conscience sur la nécessité d'organiser le règlement des différends avec le nombre croissant des organisations internationales et des litiges. Si les mécanismes se développent ils restent encore à un stade sporadique à tel point que certains considèrent que les organisations internationales agissent en toute impunité. La question est alors de savoir si elles sont liées par une obligation de prévoir un mode de règlement des différends. Il n'existe pas réellement d'obligation générale de règlement des différends à la charge de l'organisation internationale les opposant à d'autres sujets de droit international. S'agissant des différends avec des personnes privées, la multiplication des clauses de règlement des différends dans les accords de siège ou protocole sur les immunités incitent à y voir l'émergence d'une norme coutumière à la charge des organisations internationales. Ce sentiment est d'autant plus grand que l'interdiction du déni de justice incite à ce que ce mode de règlement soit au surplus entouré de principes propres au règlement juridictionnel. Sans que l'obligation de règlement des différends ne se limite au règlement juridictionnel, il y a néanmoins un développement de la part des juges nationaux à sanctionner l'organisation internationale qui ne prévoit pas de mode de règlement alternatif en mettant à l'écart l'immunité de juridiction. The means and methods for resolving disputes involving international organizationsThe research focuses on the means and methods of dispute settlement which directly involve an international organization. In fact very little dispute settlement mechanisms exist to engage the responsibility of an international organization. Howether today there is an awareness of the need to organize the settlement of disputes with the increasing number of international organizations and litigation. The obstacles to the settlements of disputes are so huge that some consider that international organizations act with impunity. The question is whether international organizations are bound by an obligation to provide for dispute settlements mechanisms. The answer is probably negative when the dispute arises between an international organization and another subject of international law. The settlement of disputes is governed by sovereignty : that means subjects of International Law have to consent to the jurisdiction of a mechanism. The problems known for States are the same for international organizations, eventhough the laters don’t have any sovereignty. As far as disputes with private individuals are concerned, the proliferation of dispute settlement clauses in headquarters agreements or protocol on immunities encourage the emergence of a customary norm in charge of international organizations. This feeling is even greater than the prohibition of denial of justice urges that this settlement is in addition surrounded by principles specific to jurisdictional settlement. Enventhough the obligation is not limited to the jurisdictional settlement, there is a development from national judges to penalize the international organization which does not provide for alternative method, by waiving their immunity.
Keywords: Dispute resolution; Immunity; Immunités; International Organizations' Liability; International organizations; Organisations internationales; Responsabilité des organisations internationales; Règlement des différends

La responsabilité civile de l'arbitre - Moreau-Cucchi, Matthieu (Université Paris-Saclay, 2021)
L’arbitrage est une institution hybride qui mêle des aspects contractuels et juridictionnels. En effet, l’arbitre est contractuellement investi d’une mission juridictionnelle consistant à trancher un litige. Or, cette hybridité ne rejaillit aujourd’hui que partiellement sur la responsabilité de l’arbitre : la responsabilité qu’il engage dans l’exercice de ses fonctions est pleinement contractuelle, mais la faute génératrice de responsabilité est définie différemment selon que le manquement se rattache ou non à la mission de juger.La présente thèse propose de tirer toutes les conséquences de la nature duale de l’arbitrage sur la responsabilité de l’arbitre. Ainsi, seuls les manquements commis par l’arbitre en sa qualité de contractant devraient être de nature à engager sa responsabilité contractuelle. Les fautes commises dans l’exercice de sa fonction juridictionnelle, en revanche, devraient conduire à l’engagement d’une responsabilité délictuelle. Pour faire le départ entre ces différents manquements, il est proposé de classer les obligations l’arbitre en distinguant celles qui sont contractuelles de celles qui sont juridictionnelles. Le critère retenu pour procéder à cette classification tient dans la comparaison entre l’arbitre et le juge étatique. Sous réserve de quelques ajustements, les obligations qui pèsent à la fois sur le juge et sur l’arbitre seront qualifiées de juridictionnelles ; celles qui ne pèsent que sur l’arbitre seront qualifiées de contractuelles.Une fois identifié le régime applicable à la responsabilité arbitrale, il reste à dérouler les conditions de sa mise en œuvre. Cela passe, d’une part, par l’identification des règles de droit international privé applicables dans les cas où le litige portant sur responsabilité de l’arbitre présente un élément d’extranéité. Dans ces hypothèses, il conviendrait de retenir des critères identiques de désignation du juge compétent et de la loi applicable : à titre principal, c’est la volonté des parties qui doit prévaloir ; à titre supplétif, le lieu du siège de l’arbitrage paraît être le critère le plus adapté pour régir la compétence du juge et la loi applicable en matière de responsabilité arbitrale.La mise en œuvre de la responsabilité de l’arbitre passe, d’autre part, par une application des conditions d’engagement de la responsabilité prévues en droit français interne. A cet égard, les conditions de droit commun tenant au fait générateur de responsabilité paraissent devoir être repensées pour pouvoir s’adapter à la question de la responsabilité arbitrale. Ainsi, s’agissant de la responsabilité délictuelle qu’encourt l’arbitre en cas de faute juridictionnelle, le fait générateur pourrait être repensé autour de la notion de faute lourde juridictionnelle. Celle-ci serait définie comme un manquement de l’arbitre à ses obligations juridictionnelles essentielles, lequel suppose un défaut d’impartialité ou d’indépendance auquel s’ajoute la violation d’une autre obligation juridictionnelle. S’agissant de la responsabilité contractuelle qu’encourt l’arbitre en cas de faute contractuelle, la thèse propose d’identifier, pour chaque obligation contractuelle, le comportement qui peut être attendu de l’arbitre et, en miroir, celui qui pourrait être considéré comme un manquement. Sur cette question, en effet, la distinction classique entre les obligations de moyens et de résultat n’est d’aucun secours pour identifier les manquements générateurs de responsabilité.S’agissant ensuite de la question du dommage et du lien de causalité, les règles qui les entourent dans le droit commun de la responsabilité paraissent adaptées à la responsabilité arbitrale. Elles devraient donc pouvoir être mobilisées en l’état, sous réserve de préciser les types de dommages réparables, notamment en termes de perte de chance, et de trancher en faveur de la théorie de l’équivalence des conditions pour apprécier le lien de causalité, tant en matière contractuelle que délictuelle. Arbitration is a hybrid institution in which contractual and jurisdictional aspects are mixed. As a matter of fact, an arbitrator is invested by a contract with the mission to settle a dispute. And yet, this hybridity does only partially reflect on arbitral liability. The arbitrator’s liability is always contractual, but the misconduct that gives rise to his liability is defined differently when it is related to his jurisdictional mission.The present thesis tries to draw all the consequences from the hybrid nature of arbitration, concerning liability matters. Thus, the liability should be contractual only when the misconduct occurred while the arbitrator was acting as a contractor. By contrast, when he acts as a judge, his liability should be tortious. In order to distinguish those different situations, we offer to classify arbitrators’ obligations into two categories based on a comparison between arbitrators and judges. Overall, the obligations that lie with judge and arbitrators would be jurisdictional and would give rise to tort liability. On the contrary, the obligations that only weigh on arbitrators would be contractual and would give rise to contractual liability.Once one knows which set of rules to apply when it comes to arbitral liability, it remains to implement those rules. In this perspective, it is necessary, firstly, to know which court is competent and which law is applicable to international arbitral liability cases. Regarding jurisdiction as well as law applicable, it seems that same criteria should be used : parties’ will should be applied in the first place. On a suppletive basis, if there is no agreement between parties, the dispute regarding arbitral liability should be submitted to the courts of the State where the place of arbitration has been settled. Likewise, the law applicable to this dispute should be determined by the place of arbitration if the parties did not choose another law.Secondly, it is necessary to determine which conditions need to be fulfilled so that the arbitrator can be found liable, according to French internal liability law. In this regard, it appears necessary to adapt general law of liability to the specificities of arbitral liability. Concerning tort law, the misconduct giving rise to liability could be defined as jurisdictional gross misconduct. It would be characterized when the arbitrator has not been independent or impartial and has furthermore breached another jurisdictional obligation. As for contractual liability, misconducts should be defined on a case-by-case basis : different misconducts should be identified with each contractual obligations, for there is no general definition of contractual misconduct. The distinction between obligations of means and obligations of result is of no use when one tries to know precisely which behavior will give rise to contractual liability.Finally, concerning prejudice and causal link, general law of liability can be applied as it stands to arbitral liability without any modification. It only appears necessary to specify what damages can be remedied, notably regarding loss of chance. Moreover, the causal link should always be applied on the basis of equivalence of conditions rather than adequate causation, both in contractual and tort liability.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Civil; Civile; Liability; Responsabilité; Responsabilité (droit); Responsabilité contractuelle

Les demandes reconventionnelles de l’Etat en arbitrage transnational - Abonnat Ruggeri, Elise (Université Paris 2, 2021)
La demande reconventionnelle est une prétention du défendeur à l’instance qui revêt une finalité offensive et défensive. Reconnue en droit du contentieux international comme un droit dans le patrimoine du défendeur, elle est une demande incidente qui vise à contre-attaquer sur le plan substantiel le demandeur principal. Dans le contentieux transnational de l’investissement, l’appréciation de la compétence et de la recevabilité des demandes reconventionnelles par les tribunaux arbitraux est entravée par l’asymétrie des instruments de protection des investissements étrangers dont l’objet est principalement axé sur la protection des droits des investisseurs. Proposant une interprétation restrictive des conditions d’admission des demandes reconventionnelles, certains tribunaux arbitraux amenuisent l’effectivité du droit de contre-attaquer, notamment lorsque le traité applicable au différend prévoit des obligations réciproques limitées. Toutefois, l’objet du différend d’investissement que l’arbitre est appelé à trancher n’est pas toujours limité à l’ensemble normatif prévu par l’instrument servant de base à la demande de l’investisseur et peut couvrir une pluralité de normes. La diversité du droit applicable au différend d’investissement et l’étendue de la compétence matérielle des tribunaux arbitraux devrait ainsi permettre qu’un Etat mette en cause la licéité du comportement de l’investisseur au regard de l’ordre juridique interne et international. La demande reconventionnelle des Etats pose alors la question de la capacité de l’investisseur internationalement protégé à voir sa responsabilité engagée pour la violation du droit de l’Etat hôte et parfois aussi du droit international. Les demandes reconventionnelles peuvent alors servir d’agent révélateur des attentes légitimes de l’Etat à l’égard de l’investisseur internationalement protégé.
Keywords: Admissibility; Compétence; Connection; Connexité; Counterclaims; Demande reconventionnelle; Demandes reconventionnelles; Diligence due; Domestic law; Droit international; Droit interne; Due diligence; Due diligence (droit international); Fondements juridiques; International law; Jurisdiction; Legal basis of claims; Objet du différend; Recevabilité; Responsabilité; Responsibility; Subject matter of the dispute

Pratique de l'arbitrage international en Algérie : enjeux et modernisation - Bouchelaghem, Saloua (Revue des Sciences Juridiques et Politiques, 2021)
A l’instar des autres pays, l’Algérie a adopté la conception dualiste de l’arbitrage, avec un régime juridique réservé à l’arbitrage interne et un autre destiné à réglementer l’arbitrage international par des dispositions particulières (Titre II Chapitre IV du CPCA). Ce qui laisse supposer une plus grande faveur pour l’arbitrage international dont le régime juridique est moins contraignante que celui de l’arbitrage interne. Ce droit de l’arbitrage parvenu certes à un stade en évolution vers la modernité ne comporte pas moins certaines lacunes que le législateur ne manquera pas de combler au gré de l’expérience de la pratique. Like the other countries, Algeria has adopted the dualistic conception of arbitration, with a legal regime reserved for internal arbitration and another intended to regulate international arbitration by specific provisions (Title II Chapter IV of the CPCA). This suggests a greater favor for international arbitration, whose legal regime is less restrictive than that of internal arbitration. this law of arbitration, which has certainly reached a stage in evolution towards modernity, nevertheless has certain shortcomings, which the legislator will not fail to fill with the experience of practice.
Keywords: Algérie; Arbitrage; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Contrôle des sentences internationales; Etat; Examination of international awards; Juge étatique; Personnes publiques; State judge; public figures

Noms de domaine et modes alternatifs de règlement de conflits - Pavlenko Chapuis, Radmila (Université Paris 2, 2021)
Afin de régler les litiges relatifs aux noms de domaine, l’ICANN, entité gouvernant le DNS, crée en 1999 la procédure UDRP (Uniform Domain Name Dispute Resolution Policy, en français : règlement uniforme des litiges relatifs aux noms de domaine). Il s’agit du plus connu mais également du plus controversé des modes alternatifs de règlement de conflits en ligne. Il s'inscrit dans un millefeuille procédural au sein duquel l’ICANN superpose un grand nombre de procédures destinées à prévenir ou résoudre des litiges relatifs aux noms de domaine. Cette obscure et complexe matrice que l’ICANN qualifie d’ « administrative », n'organise cependant ni le rapport de ces procédures entre elles ni avec le droit étatique. Ces dernières années, une augmentation stratosphérique des litiges sur les noms de domaine est observée, résultant de la multiplication exponentielle de l'utilisation d'Internet par l'ensemble de la population mondiale suite à la crise sanitaire. Dans ce contexte, la sécurité juridique des titulaires de droits de propriété intellectuelle invite à repenser l'organisation du règlement des litiges relatifs aux noms de domaine en le faisant bénéficier d’une réforme unificatrice. Elle offre non seulement l'opportunité de créer un système de règlement de litiges unique mais également d’en préciser la nature et de clarifier les concepts à prouver. À cette fin, nous proposons de transformer le système actuel, historiquement extrajudiciaire et par nature privé, en un processus d'arbitrage avec l'objectif d'établir un lien procédural entre le système extrajudiciaire de l’ICANN et le droit étatique ainsi que d’assurer davantage de garanties procédurales aux parties. In order to settle disputes relating to the registration of internet domain names, ICANN, the governing body of the DNS, created the Uniform Domain Name Dispute Resolution Policy (UDRP) in 1999. This is the best known but also the most controversial of the alternative methods of online dispute resolution. UDPR is a part of the arbitration structure in which ICANN imposes a process intended to prevent or resolve disputes relating to domain names. The obscure and complex matrix that ICANN qualifies as ''administrative'', does not organize the relationship of these arbitration procedures to each other or to state law. In recent years, a stratospheric increase in domain name disputes has been observed, resulting from the ten-fold increase in Internet use by the entire world population following the Covid health crisis.In this context, the legal security of the holders of Intellectual Property (IP) rights invites a rethinking of the organization of the settlement of disputes relating to domain names by proposing a unifying reform. This offers an opportunity to create a new unique dispute resolution system, and also to specify its nature and clarify the concepts to be proven. Towards this end, we propose a full reform to transform the current system, which has been historically extrajudicial and is by its nature private, into a full arbitration process, pursuing the objective of establishing a procedural link of the extrajudicial system with state law as well as to provide more procedural guarantees to all parties.
Keywords: ADR; Alternative dispute resolution; Alternative methods; Arbitrage; Arbitrage (droit); Arbitragem; Arbitraje; Arbitration; DNS; Disputes; Domain names; Extra-Judicial system; Extra-judiciaire; ICANN; Internet Corporation for Asigned Names and Numbers; Litiges; Marques de commerce; Modes alternatifs de règlement des conflits; Noms de domaine; Noms de domaine (Internet) -- Droit; ODR; Online dispute resolution; Règlement de conflits; Système de règlement de litiges unique; UDRP; Unique dispute resolution system

Provas ilícitas e arbitragem - Avolio, Luiz Francisco Torquato (Universidade de São Paulo, 2021)
O presente estudo é dedicado ao tema da prova ilícita na arbitragem, com sua repercussão na formação do convencimento do árbitro, em consonância com as garantias que um processo justo e equitativo impõe às partes e aos julgadores. A tutela processual de supremos valores da Constituição, pela ampla e dogmática vedação à admissibilidade das provas ilícitas no sistema brasileiro, deve permear qualquer tipo de processo, evitando-se, assim, que o uso de provas vedadas se constitua em redobrada violação dos direitos fundamentais. Por outro lado, o mais aprofundado enfoque sobre a origem e natureza da prova supostamente inadmissível poderia ensejar o manejo de provas em menor grau ou não propriamente ofensivas a essas regras e princípios, evitando que se esvazie por completo o direito à prova, comprometendo-se, por consequência, o princípio da demanda ou da ampla defesa. Nesse caso, abre-se a discussão sobre se o aporte de provas ilícitas ao processo simplesmente as legitimaria à luz do princípio da comunhão (ou aquisição) da prova, ou se poderiam ser consideradas subjetivamente ilícitas tão somente quando deduzidas contrariamente ao titular dos direitos violados, mas ao mesmo tempo lícitas para demonstrar a ocorrência de uma violação a esses direitos. No tocante às consequências práticas, se a decisão, contaminada pelo acolhimento de prova ilícita, ou, ao revés, que deixou de considerá-la, no que pertinente, comprometer o livre convencimento do árbitro, pode ensejar ação de nulidade por violação do art. 32, inciso VIII c.c. art. 21, § 2º da LA, afetando, por arrasto, os princípios da igualdade das partes e da imparcialidade do árbitro. Excepcionalmente, nos casos em que se afigure a inexistência da decisão pela fundamentação exclusiva em prova ilícita, seria possível cogitar do manejo de ação declaratória, mesmo após decorrido o prazo decadencial da ação anulatória. The study is dedicated to the theme of illegal evidence in arbitration, with its repercussion in the formation of the arbitrator's conviction, in line with the guarantees that a fair and equitable process imposes on the parties and judges. The procedural protection of the supreme values of the Constitution, by the broad and dogmatic prohibition of the admissibility of illicit evidence in the Brazilian system, must permeate any type of process, thus preventing the use of prohibited evidence from constituting a redoubled violation of fundamental rights. On the other hand, a deeper focus on the origin and nature of the supposedly inadmissible evidence could lead to the handling of evidence to a lesser degree or not properly offensive to these rules and principles, preventing the right to proof from being completely emptied, compromising, consequently, the principles of demand and full defense. In this case, a discussion arises as to whether the provision of illicit evidence to the process would simply legitimize them in light of the principle of sharing (or acquisition) of evidence, or whether they could be considered subjectively illicit only when deducted contrary to the holder of the violated rights, but at the same time lawful to demonstrate the occurrence of a violation of these rights. With regard to practical consequences, if the decision, contaminated by the acceptance of unlawful evidence, or, on the other hand, which failed to consider it, as pertinent, compromises the arbitrator's free conviction, it may give rise to an action of nullity for violation of art. 32, item VIII c.c. art. 21, § 2 of the LA, affecting, by drag, the principles of equality of the parties and the impartiality of the arbitrator. Exceptionally, in cases where it appears that the decision does not exist on the exclusive basis of unlawful evidence, it would be possible to consider handling a declaratory action, even beyond the deadline for the annulment action.
Keywords: Acquisition of evidence; Admissibility; Arbitrage; Arbitragem; Arbitration; Arbitrator; Ação anulatória; Deadline; Declaratory action; Devido processo legal; Direito comparado; Direito de defesa; Equality of the parties; Evidence; Free knowledge; Full defense; Illicit proof; Impartiality of the arbitrator; Nullity action; Principles of demand; Prova ilícita

Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

O acesso à justiça na era da automação, da inteligência artificial e da mineração de dados: o nascimento do devido processo digital (e-due process of law) - Mariano Junior, Raul (Universidade de São Paulo, 2021)
Trata o presente trabalho de aspectos da absorção da tecnologia, em especial a inteligência artificial e a automação no ambiente processual brasileiro. Discute-se aqui aspectos importantes da tecnologia ligada à computação, e a forma como já interfere e pode interferir, positiva e negativamente, no acesso à justiça (entendido como acesso à ordem jurídica justa). O conhecimento das tecnologias de machine learning, deep learning, processamento de linguagem natural, redes neurais, reconhecimento de fala, transcrições automáticas e conversão de texto em fala, já são largamente utilizados pelos tribunais, advogados e órgãos públicos, tudo num cenário transformador e disruptivo da tradição jurídica, sem qualquer ou muito pouca normatividade legal. O imbricamento da tecnologia com o princípio do devido processo legal, numa análise mais próxima, pode revelar que a tradição jurídica secular acumulada não mais se presta à finalidade de garantir decisões justas, esgarçando-se e perdendo importância e eficácia. O mundo jurídico precisa aproximar-se da tecnologia e das ciências da computação, para conformar sua aplicação e não ser conformado por elas. Por outro lado, a tecnologia computacional pode ser muito positiva no alargamento do acesso à justiça, se for adequadamente compreendida e utilizada especialmente para o tratamento de demandas repetitivas e para a aproximação da população mais carente do acesso à ordem justa. Isto se dá desde a organização e melhora das informações jurídicas disponíveis, até pelo desenho de novas formas, através do desenho de soluções de disputas, combinadas com a computação, criando vias de acesso como a ODR (Online Dispute Resolution). Pode, entretanto, esta mesma tecnologia, provocar efeitos nefastos ao estado de direito e aos direitos fundamentais se ignorada e não normatizada em tempo, traçando-se seus limites, usos, condições e responsabilidades, em velocidade equivalente ao desenvolvimento tecnológico, evitando-se, assim, lacunas de alto poder destrutivo, que certamente serão preenchidas pelo interesse econômico e político. This paper deals with aspects of technology absorption, especially artificial intelligence and automation in the Brazilian procedural environment. Important aspects of computing technology are discussed here, and the way it already interferes and can interfere, positively and negatively in the access to justice (understood as access to the fair legal order). Knowledge of machine learning, deep learning, natural language processing, neural networks, speech recognition, automatic transcriptions and text-to-speech conversion are already widely used by courts, lawyers and public bodies, all in a transformative and disruptive scenario of the legal tradition, without any or very little legal norms. The imbrication of technology with the principle of due process, in a closer analysis, may reveal that the accumulated secular legal tradition no longer lends itself to the purpose of guaranteeing fair decisions, fraying and losing importance and effectiveness. The legal world needs to get closer to technology and computer science, to conform its application and not be conformed by them. On the other hand, computational technology can be very positive in expanding access to justice, if it is properly understood and used, especially to deal with repetitive demands and to bring the poorest people closer to access to just order. This occurs from the organization and improvement of the available legal information, even through the design of new forms, through the design of dispute solutions combined with computing, creating access routes like the ODR (Online Dispute Resolution). However, this same technology can cause harmful effects to the rule of law and fundamental rights if ignored and not regulated in time, tracing its limits, uses, conditions and responsibilities, at a speed equivalent to technological development, thus avoiding gaps of high destructive power, which will certainly be filled by economic and political interest.
Keywords: ACCESS TO JUSTICE; ADR; AI; Accès à la justice; Acesso à justiça; Alternative dispute resolution; Applied computing (Law); Artificial Intelligence; Automatisation; Civil Procedure; Computação aplicada (Direito); Devido processo legal; Direitos fundamentais; Due legal process; Estado de direito; Fundamental rights; Inteligência artificial; Intelligence Artificielle; Jurisdiction; Jurisdição; Mégadonnées; ODR; Online Dispute Resolution; Processo Civil; Rule of law

Capacity of the International Investment Arbitration Mechanism in Environmental Protection - Habibi Majandeh, Mohammad; Gholami, Afife (Public Law Researsh, 2021)
Environmental considerations have always been a challenge for foreign investment. The need to observe environmental minimums from the beginning to the end of the investment is also a concern of environmental law activists. In the meantime, the host state faces sometimes conflicting commitments. State dual obligations to foreign investors on the one hand, and the whole citizens on the other, has in many cases led to disputes, rooted in environmental norms. The main question is how the arbitration mechanism can take an active stand in the face of such disputes? The main purpose of this study is to examine the reflection of these conflicts in investment arbitration and the importance and role of arbitration in improving the environmental status. The authors of this paper believe that the arbitration system has tools that it can use in resolving disputes to balance these conflicting obligations. Some of these legal tools are directly or indirectly related to investment agreements, and others are beyond the treaty and based on international principles, rules, customs and practices. ملاحظات محیط زیستی همواره یکی از چالش های پیشروی سرمایه گذاری خارجی بوده است. لزوم رعایت حداقل های زیست‌محیطی از آغاز تا پایان سرمایه گذاری، از دغدغه های فعالان حوزه حقوق محیط زیست نیز می باشد. در این میان دولت میزبان با تعهداتی بعضاً متعارض روبروست. تعهدات دوگانه دولت در برابر سرمایه گذار از یک طرف و عموم شهروندان از طرف دیگر، در موارد متعددی به بروز اختلافاتی منجر شده که ریشه در هنجارهای محیط زیستی دارد. پرسش اصلی این است که سازوکار داوری در مواجهه با این نوع اختلافات، چگونه می تواند فعالانه موضع گیری نمایند؟ هدف اصلی این مطالعه بررسی بازتاب تعارض ها در رویه داوری سرمایه گذاری و اهمیت و نقش داوری در بهبود وضعیت محیط زیستی است. نویسندگان این نوشتار بر این باورند که سیستم داوری، ابزارهایی در اختیار دارد که می تواند از آنها در جریان حل اختلاف برای ایجاد تعادل میان این تعهدات متعارض استفاده کند. برخی از این ابزارهای حقوقی مستقیم یا غیرمستقیم با معاهدات سرمایه‌گذاری مرتبط است و دستهای دیگر فرامعاهده ای و ناشی از اصول، قواعد، عرف ها و رویه های بین المللی است.
Keywords: Arbitrage; Arbitragem; Arbitration; Bilateral Treaties; Environmental Protection; International Arbitration; Investment Disputes; Legal Instruments; ابزار حقوقی; اختلافات سرمایه‌گذاری; حمایت از محیط ‌زیست; داوری بین‌المللی; معاهدات دوجانبه

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Mediación y Cultura de Paz en los Objetivos de Desarrollo Sostenible 2030 - Gonzalo-Quiroga, Marta (Polo del Conocimiento, 2021)
El objetivo de la presente contribución es analizar el papel de la mediación como bisagra referencial entre dos de los Objetivos de Desarrollo Sostenible (ODS) para 2030: el núm. 4 -Educación- y el núm. 16 -Paz, Justicia, e Instituciones sólidas-. La metodología empleada parte de un estudio del panorama internacional para detenerse en la legislación española, tanto en mediación como en educación en cultura de paz, con las correspondientes novedades al respecto. Todo ello responde a una investigación analítica sobre distintas bases legislativas, documentales y bibliográficas que, como resultado, ha dado lugar a la creación de distintas tablas que resumen la investigación y, pretendemos, contribuyan a facilitar su difusión, en el marco de los ODS 2030. Se trata así de promover la mediación como una de las herramientas esenciales para fomentar la convivencia pacífica, la educación y la justicia en el contexto universal de la cultura de la paz.
Keywords: Cultura de Paz; Cultura de paz; Culture of Peace; Educación; Education; Educação; Justice; Justicia; Justiça; Mediación; Mediation; Mediação; Objetivos de Desarrollo Sostenible (ODS); Objetivos de Desenvolvimento Sustentável; Sustainable Development Goals

L’autonomie de la clause en droit privé - Tawk, Ghassan (Université de Montpellier, 2021)
L’autonomie un vocable recouvrant deux réalités : la « séparabilité » et « l’indépendance ». L’autonomie de la clause compromissoire se traduit par la SEPARABILITE de la clause et non pas par son indépendance puisqu’elle se trouve parmi les autres clauses du contrat de base. La séparabilité signifie que cette clause est différente des autres clauses dans son existence, son objet et sa portée et elle ne partage pas leur sort. Les effets de cette séparabilité se résument en une autonomie matérielle qui permet, d’une part, la survie de la clause compromissoire au contrat principal, l’absence de contagion des vices qui pourraient affecter le contrat et, d’autre part, elle l’autorise à être soumise à une loi différente de celle qui régit le reste du contrat et si les parties ont choisi la loi applicable à leur contrat, rien ne permet d’affirmer que cette même loi devrait régir la clause compromissoire, puisque celle-ci est fort différente dans son objet et sa nature du contrat qui la contient.En revanche, le principe de l’autonomie de la garantie autonome signifie L’INDEPENDANCE totale et ceci veut dire inopposabilité des exceptions contenu dans d’autres contrats ou instruments annexes s’y rapportant. Le mécanisme de la garantie autonome aboutit à la création d’une pluralité de rapports contractuels dont l’enchainement chronologique se présente par la création de deux contrats distincts et indépendants. L’appel de la garantie la rend irrévocable et exigible immédiatement sans contestations se rapportant au contrat de base et sans pouvoir lui opposer les exceptions qui pourraient s’appliquer à ce contrat.
Keywords: Arbitration clause; Autonomie; Autonomy; Clause compromissoire; Garantie autonome; Guarantees; Independence; Indépendance; Separability; Séparabilité; Sûretés (droit)

L'incidence de l'arbitrage et les situations triangulaires : Étude à la lumière de l'évolution du sort de la caution solidaire - El Hajj, Joyce (Université de Montpellier, 2021)
La Cour de cassation a mis fin aux controverses jurisprudentielles et doctrinales sur la qualité de la caution solidaire quant à la clause compromissoire, et cela en refusant l’application de la théorie de la représentation mutuelle des coobligés et en la qualifiant de « tierce personne », ouvrant par ce fait la porte à la tierce opposition. La transposition de la solution avancée par la Haute Cour, a été parfaitement appliquée à l’assureur non-signataire de la clause compromissoire insérée dans un contrat liant son assuré à une autre personne, même en présence de la clause de direction de procès dans le contrat d’assurance. Enfin, la possibilité de l’application de cette solution a été étudiée au cas par cas sur l’effet de la clause compromissoire statutaire à l’égard d’un futur ou ex- associé. The Court of Cassation put an end to the jurisprudential and doctrinal controversies on the quality of the joint and several sureties regarding the compromise clause, and this by refusing the application of the theory of mutual representation of the co-owners and by characterizing it as “third party”, thereby opening the door to the third-party opposition. The transposition of the solution proposed by the High Court was perfectly applied to the insurer who did not sign the arbitration clause inserted in a contract binding his insured person to another person, even in the presence of the trial management clause in the insurance contract. Finally, the possibility of applying this solution has been studied on a case-by-case basis on the effect of the statutory arbitration clause on a future or ex-partner.
Keywords: Arbitrage; Arbitragem; Arbitration; Assureur non-Signataire; Caution solidaire; Cautionnement; Clause compromissoire; Codébiteurs; Corporate law; Droit des sociétés; Joint and several sureties; Non-Signatory insurer; Third party; Tierce opposition; Tiers (droit)

Les centres d’arbitrage de l’espace OHADA face aux technologies de l’information et de la communication (TIC) - Ndongo Dimouamoua, Céline (Revue Juridique de la Sorbonne, 2021)
Depuis l’adoption de l’Acte uniforme relatif au droit de l’arbitrage, les centres d’arbitrage se sont multipliés dans la zone OHADA. Même si tous ces centres ne sont pas au même niveau de développement, les acteurs économiques leur confient de plus en plus le règlement de leurs différends. Toutefois, la fermeture des aéroports, la limitation des déplacements, l’impossibilité de se réunir, conséquences de la crise sanitaire mondiale apparue en mars 2020, ont perturbé le fonctionnement des centres d’arbitrage du monde entier, y compris ceux situés dans la zone OHADA. En abolissant les distances et les contraintes de temps, les technologies de l’information et de la communication (TIC) se sont révélées être des moyens efficaces de contournement des difficultés nées de la pandémie. En effet, les grands centres d’arbitrage en ont profité pour mettre en œuvre des solutions technologiques permettant de réduire l’impact de la crise sur les procédures arbitrales. Dans cet environnement hautement concurrentiel, la question de l’arbitrage en ligne dans les centres d’arbitrage de l’espace OHADA s’est alors de facto posée. La question de la place réservée aux TIC dans l’administration des procédures par ces centres et les moyens d’y développer l’arbitrage à distance est posée. Pour répondre à cette double interrogation, un état des lieux de l’arbitrage en ligne dans les centres d’arbitrage de la zone a été fait. Il en ressort que les règlements d’arbitrage des centres abordent le sujet de manière lacunaire. Bien plus, l’environnement économique et technologique dans lequel ils évoluent peut constituer un frein au recours aux TIC. La nécessité de compléter les règlements d’arbitrage sur des questions comme la cybersécurité, l’organisation des réunions virtuelles ou encore la signature électronique des documents est clairement apparue. Afin d’accélérer le développement de l’arbitrage en ligne, les centres d’arbitrage situés dans l’espace OHADA doivent aussi former leur personnel à l’usage des TIC, encourager les parties à signer des cyber-protocoles, et mettre à leur disposition des guides d’usage des TIC dans les procédures arbitrales. En pratique, la révolution numérique dans les centres d’arbitrage africains n’aura pas lieu sans les efforts combinés des centres, des parties et des arbitres. 22 ans après l’adoption de l’AUA, la compétitivité et la maturité des centres d’arbitrage de l’espace OHADA seront fonction de leurs capacités à intégrer les TIC dans leurs méthodes de travail.
Keywords: Arbitrage en ligne; Arbitrage institutionnel; Arbitration centres; Centres d’arbitrage; Cyber protocol; Cyber-protocole; Guides sur l’arbitrage en ligne; ICT; Institutional arbitration; OHADA; Online Dispute Resolution; Online arbitration guides; TIC; Vidéoconférence

La détermination du droit applicable à l’arbitrage - Lacreta, Isabela (Université Paris 10, 2021)
La détermination de la loi applicable à la résolution des crises juridiques entre les parties est la première étape de l’activité juridictionnelle dans les cas où un élément d’extranéité est présent. Il s’agit d’une étape essentielle pour assurer la protection juridictionnelle. Tout arbitrage est, du point de vue du système juridique du droit national, étranger à celui-ci. L’arbitre est l’autorité juridictionnelle du système juridique autonome de droit transnational, un système qui est déconnecté du système national, dans lequel le juge étatique est l’autorité juridictionnelle naturelle. L’État a le pouvoir de décider de la part de souveraineté à laquelle il souhaite renoncer en faveur de l’arbitre. En matière d’arbitrage, l’étendue de l’autonomie de la volonté des parties est largement reconnue, tant dans ses dimensions procédurales que matérielles. Rares sont les cas où les parties prévoient expressément les droits qui régiront leurs arbitrages. Droits, au pluriel, non seulement en raison de la nature transnationale des arbitrages, mais aussi en raison de la spécificité des questions soumises à la protection des arbitres. Chaque question doit être régie par son propre droit, conformément à la technique de dépeçage. Les méthodologies de conflit de lois propres au système juridique national, de nature interne et publique, ne sont pas adaptées et ne doivent pas être transposées en matière d’arbitrage. La multitude de questions pouvant être discutées dans un arbitrage exige une délimitation de l’objet de cette étude. Celle-ci est ainsi exclusivement consacrée au droit applicable à l’arbitrage, en particulier aux droits applicables à la convention d’arbitrage, au procès arbitral et à la validité et l’efficacité de la sentence arbitrale, en suivant les étapes classiques d’une procédure arbitrale. L’analyse de la détermination du droit applicable dans l’arbitrage, c’est-à- dire au fond, est exclue. Les conclusions de cette étude partent toujours du principe que l’arbitre est une autorité juridictionnelle non soumise aux règles d’organisation judiciaire et hiérarchique du système national ; ses actes sont soumis à un contrôle minimum d’internalisation, par le biais de conversations systémiques.
Keywords: Applicable law to arbitration; Arbitrage; Arbitragem; Arbitration; Autonomia da vontade; Autonomie (philosophie); Autonomie de la volonté; Conflict of laws; Conflit de juridictions; Conflit des lois; Conflito de leis; Direito applicável a arbitragem; Direito transnacional; Droit applicable à l'arbitrage; Droit transnational; Party autonomy; Soberania; Sociologia da arbitragem; Sociologie de l'arbitrage; Sociology of arbitration; Souveraineté; Sovereignty; Transnational law

L'arbitrabilité des litiges en droit des marchés financiers - Megam, Nadège Flore (International Multilingual Journal of Science and Technology, 2021)
Keywords: Arbitrage; Arbitration; Financial markets; Marchés financiers

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

Le repli par les juridictions étatiques de leur jurisdictio - Bouhenic, Marcel-Gérard (Université Paris-Saclay, 2021)
Les juridictions étatiques rétractent volontairement leur jurisdictio pour favoriser les Modes Alternatifs de Règlement des Conflits (MARC) - notamment la médiation et l'arbitrage - et tendent ainsi à devenir un mode subsidiaire de règlement des litiges.Les techniques juridiques qui fondent la rétractation de la jurisdictio des juridictions étatiques au profit des MARC ont pour particularité d'être de source prétorienne et issues de raisonnements construits sur un a priori systématiquement favorable aux MARC, a priori qui n’est pas uniquement le reflet d’un système économique mais résulte de multiples influences idéelles (philosophiques, religieuses, sociétales).De fait, la subsidiarité des juridictions étatiques entraîne la subsidiarité de la loi en tant que norme de règlement des litiges. Parallèlement, les normes a-légales retenues par les MARC acquièrent une autorité assise sur la satisfaction tant des parties qui en font l'expérience que des juges étatiques qui constatent que la rétractation de leur jurisdictio ouvre le passage du juste général au juste particulier.Ainsi, progressivement, les institutions privées de MARC acquièrent un pouvoir politique en émettant des normes qui influent à la fois sur les règles que retiennent les juridictions étatiques et sur la stratégie des parties dans la défense de leurs intérêts.Au-delà de leur tendance à rétracter leur jurisdictio à l'égard des conflits privés en laissant se développer sous leur contrôle les MARC et les normes a-légales pour les conflits entre particuliers, les juridictions étatiques, en ce début du XXIè siècle, redéployent toutefois leur jurisdictio en endossant, le cas échéant, un rôle politique de création de normes et de suppléant du législateur lorsque les conflits s'expriment sous forme d'affrontements de Grands Principes, notamment lorsque les règles légales sont insuffisantes pour répondre à l'évolution de la société. State courts voluntarily retract their jurisdictio to favour Alternative Dispute Resolution (ADR) - notably mediation and arbitration - and are thus tending towards becoming a subsidiary means of dispute resolution.The legal techniques, on which the withdrawal of the jurisdictio of the State courts in favour of ADR is based, have the particularity of being of praetorian origin and the result of reasoning based on an a priori systematically favourable to ADR, an a priori that is not only the reflection of an economic system but the result of multiple "ideal" influences (philosophical, religious, societal). The subsidiarity of State jurisdictions leads de facto to the subsidiarity of the law as a standard for dispute settlement. In parallel, the non-legal standards adopted by ADR acquire an authority based on the satisfaction of both the parties to whom they are applied and the State judges who consider that the withdrawal of their jurisdictio opens the passage from what is just in general to what is just in particular. Thus, gradually, private ADR institutions are acquiring political power by issuing standards that influence both the rules adopted by State courts and the defense strategies of the parties.Beyond their tendency to retract their jurisdictio by allowing ADR and non-legal standards to develop under their control with regard to conflicts between private individuals, State courts, at the beginning of the 21st century, are nevertheless redeploying their jurisdictio by adopting, where appropriate, a political role as standard-setters and substitute legislators where conflicts take the form of confrontations between Great Principles, particularly where legal rules prove unable to respond to changes in society.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Consensualism; Consensualisme; Juridictio; Jurisdictio; MARC ( mode alternatif de réglement des conflits ); MARD; Mediación; Mediation; Mediação; Médiation; Médiation internationale; Repli; Règlement de conflits; Règlement pacifique des conflits internationaux; Withdrawal

Normas de aplicação imediata e arbitragem trabalhista: entre pluralismo e transnacionalidade - Guedes, Henrique Lenon Farias (Universidade de São Paulo, 2021)
O tema desta pesquisa é a lei aplicável ao mérito da arbitragem trabalhista com elementos estrangeiros, tendo, como problema, a determinação das normas brasileiras de aplicação imediata. Considerando que o direito do trabalho tem uma normatividade híbrida, dependendo tanto da produção legislativa estatal quanto da atividade normativa dos sindicatos, a hipótese é: o padrão normativo de aplicação imediata, em matéria trabalhista, deve ter critério pluralista, integrando regulamentos públicos e privados, ou melhor, produzidos pelo Estado, pelo sindicato e pelas empresas, de modo que as normas de aplicação imediata se encontrariam no direito transnacional. A pesquisa se insere em debates muito recentes na Academia e na sociedade civil estrangeiras, que tem proposto cláusulas e regras modelos para arbitragem nas cadeias produtivas; por outro lado, temas específicos de direito do trabalho não têm encontrado ressonância na doutrina brasileira de DIP, o que reforça a justificativa e a pertinência da pesquisa. Nesse sentido, a contribuição à ciência brasileira pretende-se original na articulação do marco teórico utilizado, a análise econômica do direito, ainda pouco explorada nos estudos brasileiros de direito internacional, com o ambiente decisório especial da arbitragem. A pesquisa será bibliográfica, normativa, jurisprudencial e documental, com uso do método hipotéticodedutivo. Para tanto, a tese é dividida em cinco capítulos. O primeiro oferece um resgate histórico da ideia de arbitragem comercial, opondo-o à evolução do direito internacional do trabalho e identificando uma dificuldade apriorística de se aproveitarem os conceitos da primeira na aplicação do segundo, especialmente diante de tratados de direitos humanos. O segundo identifica, na doutrina e na jurisprudência trabalhistas, que essa incompatibilidade é processada com razões que parecem equivocadas, isto é, com o uso hiperbólico ou inadequado dos conceitos de publicização e de ordem pública. O terceiro, portanto, identifica a potencial conveniência do conceito de normas de aplicação imediata, supostamente protetivo do trabalhador, mas o questiona no contexto de uma análise econômica do direito internacional, isto é, verifica sua sustentação à luz dos incentivos institucionais à captura dos fins do direito pelos Estados, ainda que estes sejam partes de tratados de direitos humanos. Funda-se, assim, um ceticismo quanto à qualificação de preceitos da legislação trabalhista nacional como normas de aplicação imediata. Ciente dessa limitação, o quarto tenta identificar as normas nacionais que verdadeiramente se deveriam aplicar, de forma imediata, ao mérito de uma disputa trabalhista plurilocalizada, com atenção transcultural à Convenção 169 da OIT. Estabelecidos os parâmetros do direito brasileiro, o quinto revisita a doutrina de Georges Scelle, para compreender a arbitragem como desdobramento funcional do direito internacional do trabalho e nela indicar um caminho mais adequado: as normas de aplicação imediata se encontrariam diretamente no regime transnacional do direito do trabalho. Assim, além da justificativa econômica para o afastamento de normas de aplicação imediata, especificamente nacionais, destaca-se uma proposta jurídica de reaproveitamento operacional desse conceito. O capítulo final faz a distinção entre os tipos de arbitragem que se relacionam com o direito da OIT (normativa) e com o direito transnacional (positiva).
Keywords: Arbitrage; Arbitragem; Arbitration; Direito Internacional Privado (análise econômica); Direito do Trabalho; Direitos Humanos; Droit du travail; Labour arbitration; Labour law; Legal pluralism; Overriding mandatory provisions; Pluralismo jurídico; Public policy; Transnational Law

L'arbitrage à l’épreuve des procédures collectives et de l’intervention du juge en droit de I’OHADA. - Kante, Souleymane (Université Jean Lorougnon Guédé, 2021)
Si l’on définit l’arbitrage simplement comme un mode de règlement des différends administré par les particuliers non investis de leur mission par l’Etat. Il n’en demeure pas moins que ce mode de règlement des différends ne saurait évoluer seul. C’est ainsi que l’ordre public des procédures collectives et l’intervention du juge étatique impact tant l’arbitrage. Il a paru important de jauger leur impact sur l’arbitrage. L’analyse effectuée à travers une méthode exégétique des textes communautaires et internationaux a permis de constater que les procédures collectives et l’intervention du juge étatique sont facteurs de désordre dans l’arbitrage. Toutefois, il convient de relever une certaine survie de l’arbitrage face aux procédures collectives et à l’intervention du juge étatique.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Juge étatique; OHADA; Procédures collectives; Survie

El principio de proporcionalidad en el derecho international económico - Reyes Sarmiento, Lina (Université Paris 10, 2021)
Le principe de proportionnalité a été récemment reconnu dans les traités et les accords internationaux du commerce et des investissements avec l’État. Cependant, peu d'études se concentrent sur la nature juridique, le contenu, la portée et les fonctions de ce principe dans le droit économique international. Cette thèse présente une analyse actuelle et détaillée sur ces questions.
Keywords: Arbitrage international; Arbitraje internacional; Dispute resolution; Droit international économique; International Arbitration; Inversiones; Investissements; Investments; OMC; Principes; Principios; Principles; Proporcionalidad; Proportionality; Proportionnalité; Proportionnalité (droit); Règlement des différends; Solucion de diferencias; WTO

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Le réglement de litiges commerciaux en Afrique de l'Ouest - Traoré, Mandiou (Université Jean Moulin Lyon 3, 2021)
L’organisation du règlement des litiges commerciaux en Afrique de l’ouest notamment dans les États Parties au Traité OHADA est marquée à la fois par l’intervention des juridictions nationales d’instance et d’appel et de la Cour commune de justice et d’arbitrage. En effet, la mise en place d’une législation commune en matière de droit des affaires a nécessité l’institution d’une Cour de cassation unique pour unifier la jurisprudence. L’uniformisation de la jurisprudence a conduit à la mise à l’écart des juridictions nationales supérieures de tout enjeu de règlement de litiges liés à l’application du droituniforme excepté les décisions appliquant des sanctions pénales. Dès lors, les relations entre les deux ordres de juridictions supérieures sont plus empreintes de conflits que basées sur un véritable dialogue des juges. Eu égard à ce qui précède, pour assurer aux opérateurs économiques un meilleur règlement de leurs litiges en évitant les difficultés liées au règlement judiciaire, il convient de promouvoir d’autres outils alternatifs de règlement des litiges. Dès lors, l’adoption des actes uniformes relatifs à l’arbitrage et à la médiation ont permis de donner aux opérateurs économiques, d’autres lieux alternatifs pour régler leurs litiges. En outre, le développement des centres d’arbitrage, de médiation et de conciliation semble être une alternative aux juridictions judiciaires. Au regard, des multiples saisines du centre d’arbitrage, de médiation et de conciliation de Ouagadougou par les banques et établissements financiers, les sociétés d’assurances, de transports et de télécommunications, les entreprises minières et énergétiques, l’on peut en déduire que ce centre joue un rôle important dans le règlement alternatif des litiges commerciaux en Afrique de l’ouest. The organization of the settlement of commercial disputes in West Africa, particularly in the States Parties to the OHADA Treaty, is marked by the intervention of national courts of instance and appeal and the Common Court of Justice and Arbitration. Indeed, the establishment of common business law legislation has necessitated the institution of a single Court of Cassation to unify jurisprudence. The standardization of jurisprudence has led to the exclusion of the higher national courts from any dispute resolution issues related to the application of uniform law, except for decisions applying criminalsanctions. Consequently, relations between the two orders of higher courts are more marked by conflict than based on a genuine dialogue between judges. In order to ensure that economic operators have a better settlement of their disputes by avoiding the difficulties associated with judicial settlement, alternative dispute resolution tools should be promoted. Consequently, the adoptions of the Uniform Acts on Arbitration and Mediation have made it possible to give economic operators other alternative places to settle their disputes. In addition, the development of arbitration, mediation and conciliation centers seems to be an alternative to judicial jurisdictions. In view of the numerous referrals to the Ouagadougou Arbitration, Mediation and Conciliation Center by banks and financialinstitutions, insurance, transport and telecommunications companies, mining and energy companies, it can be deduced that this center plays an important role in the alternative settlement of commercial disputes in West Africa.
Keywords: ADR; Aide juridictionnelle; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Cassation; Development of arbitration, mediation and conciliation centers; Droit des affaires (régularisation); Développement des centres d’arbitrage, de médiation et de conciliation.; Judicial settlement of disputes; MARD; Mediación; Mediation; Mediação; Médiation; Organisation pour l'harmonisation en Afrique du droit des affaires; Règlement alternatif des litiges; Règlement de conflits; Règlement judiciaire des litiges; Standardization of jurisprudence; Uniformisation de la jurisprudence

L'Arbitrage familial international - Delobre, Anne-Sophie (Université Jean Moulin Lyon 3, 2021)
Comment évoquer un tel sujet sans s’émouvoir d’un antagonisme certain ? Les spécialistes du droit de la famille, conscients de l’importance de l’indisponibilité des droits, de la place de l’ordre public en la matière, des enjeux de protections des personnes concernées, sont souvent réticents à penser au concept de l’arbitrage familial international. A l’inverse, les spécialistes de l’arbitrage, habitués aux vertus du système, s’empressent de promouvoir « l’arbitrage pour tous » afin de conquérir un nouveau marché et répondre à une nouvelle demande. Ainsi, un dilemme naît : les litiges familiaux internationaux sont-ils arbitrables ? Dans une telle hypothèse comment pourrait être mis en œuvre l’arbitrage familial international ? C’est un sujet d’actualité, controversé, qui repose sur une idée qui n’est pas novatrice : sa vulgarisation sur la scène internationale ne serait pas une révolution. Il n’en demeure pas moins qu’une prudence s’impose dans une matière aussi sensible que le droit international de la famille. Face à la contractualisation croissante du droit de la famille, une voie médiane, pragmatique, d’un arbitrage familial international pourrait s’organiser par l’insertion d’une convention d’arbitrage dans les contrats internationaux de droit de la famille avant tout litige pour anticiper, organiser, les points épineux et éviter de douloureux procès. This dissertation addresses an issue that cannot be discussed without provoking concerns stemming from an indubitable antagonism. Family law specialists, who are aware of the importance of the unavailability of family-related rights, of the role of public policy rules in this area, and of the challenges involved in the protection of the persons concerned, are often reluctant to consider the concept of international arbitration in family matters. Conversely, arbitration specialists, who are familiar with the virtues of this procedure, are keen to promote “arbitration for all” in order to enter a new market and address a new demand. This gives rise to a dilemma: can family-related disputes be subject to arbitration? If so, how could arbitration procedures be implemented in this area? This is a current and topical issue, relying on an idea that is not novel: its general application on the international scene would not amount to a revolution. It remains however that caution must prevail in an area as sensitive as international family law. While family law is increasingly dominated by a contractual approach, a median and pragmatic solution might favour international family arbitration through the insertion of an arbitration clause in international family law contracts prior to any dispute in order to anticipate any thorny issue that might arise and organise its resolution, thus avoiding painful litigation.
Keywords: Arbitrability; Arbitrabilité; Arbitrage; Arbitrage international; Arbitragem; Arbitral court; Arbitration; Arbitration Agreement; Arbitration decision; Convention d'arbitrage; Disponibilité (droit); Droits indisponibles; Familial; Famille; Famille (droit); Family; International; Internationality; Internationalité; Litigation; Litige; Ordre public; Ordre public (droit international); Public policy; Sentence arbitrale; Tribunal arbitral; Unavailable rights

Les paradoxes de l'arbitrage institué par la Conférence Interafricaine des Marchés d'Assurances (CIMA) - Sindjui Siani, Brice Carlin (International Multilingual Journal of Science and Technology, 2021)
La constance dans l’arbitrage est sans doute la volonté dans le recours à ce mode de résolution de conflits. C’est parce que les parties trouvent un intérêt à l’arbitrage, qu’elles décident d’échapper à la compétence de principe des juridictions étatiques. Or, ce bel édifice est remis en cause par le législateur CIMA à l’article 276 par l’instauration d’une Commission Nationale d’arbitrage au sein des États membres dont les assureurs sont obligés de saisir lorsque nait un différend dans l’exercice des recours subrogatoires entre eux. Le paradoxe arbitral ainsi analysé comme ce qu’il est convenu d’appeler l’ « arbitrage forcé » n’empêche pas toute fois d’entrevoir dans ledit arbitrage institutionnel, un instrument au service de la justice et des assureurs tant les vertus sont variées.
Keywords: Arbitrage; Arbitration; Assureurs; CIMA; Commission Nationale d’Arbitrage; Insurers; National Commission of Arbitration; Recours subrogatoire; Recourse of subrogation

Proceedings of 2021 UNCITRAL Working Group III inter-sessional meeting: the use of mediation in ISDS - Asian Academy of International Law Limited (AAIL) (Asian Academy of International Law Limited, 2021)
Keywords: Dispute settlement; Investment disputes; MARD; Mediación; Mediation; Mediação; Médiation; UN Commission on International Trade Law; UN Convention on International Settlement Agreements resulting from Mediation (2018)

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

Le financement de l’arbitrage par les tiers - Makhlouf, Amel (Revue internationale de droit comparé, 2021)
ruit de la pratique anglo-saxonne, le financement de l’arbitrage par un tiers financeur connaît un essor significatif tant à l’échelle nationale qu’internationale. Intervenu en France ces dernières années, ce mécanisme permet à un tiers (fonds d’investissement, société de financement spécialisée…) de financer une partie ou la totalité des frais relatifs à une procédure arbitrale tels que les frais d’avocats, d’experts, de témoins, d’arbitres ainsi que ceux liés à l’exécution de la sentence arbitrale. En cas de succès, le tiers financeur perçoit en contrepartie un pourcentage sur les dommages et intérêts alloués par la sentence arbitrale à la partie financée . Bien que dans une large majorité des cas le tiers financeur intervienne en faveur de la partie demanderesse, il peut aussi intervenir en faveur du défendeur ayant formulé une demande reconventionnelle. Le tiers financeur assume seul les risques financiers liés à la procédure. Si la partie financée n’obtient pas gain de cause à l’issue de la procédure arbitrale, le tiers ne percevra donc aucune rémunération et ne sollicitera auprès de son client aucun remboursement des frais qu’il aura avancés pour lui.

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future (Publications of the Masaryk University, theoretical series, editions Scientia, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

Yönetim kurulu krizleri ve çözüm yolları - Meti̇n, Umut (Kadir Has Üniversitesi, 2021)
YK farklı sorunlar veya uyuşmazlıklarla yüzyüze gelebilir. Sorunlar veya uyuşmazlıklar kriz halini alarak YK'nın işleyişine olumsuz etki edebilmektedir. Kriz derinleştikçe, YK işlevini yerine getirmekte zorlanabilir. Krizin bir adım ötesinde ise YK kilitlenebilmektedir. Pay sahipleri arasındaki menfaat çatışmaları, YK kriz ve/veya kilitlenmesinin en sık rastlanan temel nedenidir. Kilitlenme durumunda, YK toplantı yapamamakta veya karar alamamaktadır. Oysa ki, YK her daim çalışabilmesi gereken bir organdır. YK'nın kilitlenmesi, şirketin de kilitlenmesi sonucu doğurabilir. Bu durum öyle risklidir ki, şirketin feshi/tasfiyesi yakın bir ihtimal olabilmektedir. Bu aşamada kilidin olabildiğince hızlı açılması şirketten menfaati olan herkes için (pay sahipleri, YK üyeleri, çalışanlar, alacaklılar, kamu vb.) hayati önemdedir. Bu nedenle, şirket esas sözleşmesinde YK kriz ve kilitlenmelerine karşı önlemler planlanmalıdır. Tek kişiden ibaret YK modeli ve YK'ya danışma kurulu desteği kilitleme riskine karşı önerdiğimiz modeldir. Pay sahipleri sözleşmesi, aile şirketleri için aile anayasası gibi hukuki metinler kriz ve/veya kilitlenmeye ilişkin tedbirler içermelidir. Önlemlere, rağmen kilitlenme gerçekleşir ise, öncelikle YK içi ve şirket içi çözümler uygulamaya konulmalıdır. Bu tür yöntemler yeterli olmazsa, AUÇY'nin tatbiki, şirket dışından gelen çözümün ilk aşaması olarak kabul edilmelidir. Arabuluculuk ile YK kriz ve kilitlenmelerine karşı etkin, hızlı ve kalıcı çözümler sağlanabilmektedir. "Med-arb" veya "Arb-med" gibi yöntemlerden de faydalanılabilir. Tahkim de bir çözüm yoludur. Bu yolda "seri tahkim usulü" YK kilitlenmeleri için daha uygundur. Son çare olarak nitelediğimiz, dava yolu ise, bazı durumlarda içinde şirketin fesih ve tasfiye riskini barındırdığı için kilidi açmak ve hatta kilidi kırmak için uygulamaya konulabilir. Mahkemelerde, organ yokluğuna dayalı fesih davası ve özellikle haklı sebeple şirketin feshi davası çözüm sağlayabilecek dava tipleridir. Özellikle, haklı sebeple şirketin feshi davası, kriz ve kilitlenmelere daha uygun olup, stratejik sonuçlara da imkân vermektedir. Bunlar yanında, YK işleyişinde yapay zekâdan faydalanmanın mümkün olup olmadığı, yapay zekâya YK üyesi olarak kişi statüsü verilip verilemeyeceği, bu meselenin YK üyelerinin sorumluluğuna etkisi incelenmiştir. Board of Directors may face various disputes or disagreements. These disputes or disagreements may turn into crises which negatively affect the normal functioning of the board. As the crisis deepens, Board of Directors could have difficulties in fulfilling its function. Moreover, a step further from the crisis, Board of Directors might even be locked up. Conflicts of interest among shareholders are known as the most common cause of the board of directors crisis and/or deadlock. In event of a deadlock, Board of Directors, a body should always be able to function, cannot hold meetings or make decisions anymore. The deadlock of board of directors, may lead the entire company to be locked down whereas the company may encounter the possibility of dissolution and liquidation. At this point, unlocking the crisis as quickly as possible is vital for relevant competent persons of the company. Therefore, measures should be taken in the company's articles of association against Board of Director crisis and/or deadlock. One-person Board of Directors model and support of Advisory Board to Board of Directors is the model we recommend against the risk of locking. Legal texts such as shareholder agreements and family constitutions for family companies should include measures regarding deadlock. If a deadlock has occurred in spite of precautions, first of all, Board of Directors and internal remedies should be implemented. If such methods are not sufficient enough, Alternative Dispute Resolution (ADR) methods should be regarded as the first stage of external intervention. Effective and rapid solutions can be achieved against deadlocks via mediation. "Med-arb" or "Arb-med" could be also utilised. Arbitration is also a way and in this way; "expedited (fast-track) arbitration" procedure is more suitable for corporate deadlocks. Litigation, as the last possibility that we propose, could also be applied to unlock or even break the lock, since it contains the risk of dissolution and liquidation of company in some cases. In courts, termination action based on the absence of organs and especially termination of the company with a valid reason are the types of cases that may provide a solution. Especially termination of the company with a valid reason is more suitable for crisis and deadlocks, and also grants strategic results. In addition to these, it has been questioned in this study whether Board of directors possibly benefit from artificial intelligence in the operations and whether AI can be attributed a person-status as a member of Board of Directors. The effects of this issue on the responsibility of the members of Board of Directors have been analysed.
Keywords: Absence of body; Arabuluculuk; Arbitration; Artificial Intelligence; Board directors; Conseil d'administration; Crisis; Deadlock; Inteligência artificial; Intelligence Artificielle; Kilitlenme; Kriz; Mediation; Members of the board directors; Médiation; Organ yokluğu; Tahkim; Yapay zeka; Yönetim kurulu; Yönetim kurulu üyeleri

The prospective evolution of international commercial arbitration - Purqurian, Lily Leila (Revue libre de Droit, 2021)
“It is a curious fact that the Americanization of international arbitration is a topic that is often felt but is rarely discussed.” Roger P. Alford Similar to Alford’s sentiments, the shift towards arbitration in the United States alone is a phenomenon often felt, but feebly interrogated. Law schools across the nation continue to operate under the premise of judicial decision-making grounded in “rights protection.”[1] Yet, there is a clear shift towards arbitration as the preferred procedural process, with over 303,999 cases resolved by way of arbitration in 2019 alone.[2] While this brief note does not seek to interrogate the shift towards arbitration as much as it intends to examine the impact of American arbitration on international commercial arbitration generally, that shift, as you will see, looms in the background of any and all analysis of arbitration in the United States. I will begin by briefly noting the origins- and current regime of international commercial arbitration in the United States so to address the impact of its arbitration law and arbitral institutions on arbitration globally. I will then offer thoughts on the prospective evolution of international arbitration in the United States and how that may change the directions of legal procedural processes both in the United States and abroad. I. ORIGINS- AND CURRENT REGIME OF INTERNATIONAL ARBITRATION IN THE USA As arbitration flourishes as the choice for commercial disputes, there is no doubt that the United States has become a newfound hub for arbitration. It was not always this way, however. The Federal Arbitration Act (FAA) of 1925 established a steady road to an increasingly pro-arbitration policy, in three chapters, that shows itself in case-law as: when in doubt, favor arbitration.[3] The first chapter of the FAA establishes the framework for arbitration seated in the U.S. and provides the grounds for enforceable arbitration agreements and awards, while the second and third chapters implement the 1958 New York Convention and 1975 Panama Conventions, respectively. The strictly pro-arbitration policy does not lack in its own confusion, however, because of its basis in an otherwise federalist system. The FAA has largely remained unchanged since its nascence and has thus, left a substantive amount of discretion in interpreting arbitration law in the United States to the Supreme Court. One such source of confusion in U.S. arbitration law due to a lack of amendment lies in the term “arbitrability.” Arbitrability is the susceptibility of a case to be resolved by way of arbitration. In order to define the parameters of this susceptibility, the Supreme Court has distinguished between “procedural” and “substantive” arbitrability, wherein the former concerns itself with “prerequisites such as time limits, notices, laches, estoppel, and other conditions” and the latter, with a court’s decision.[4] The benefits to arbitration remain unmatched for commercial entities, however, which inspires the aforementioned pro-arbitration policy despite any real judicial framework. Arbitration allows parties to customize their dispute resolution by choosing the venue, applicable procedural law, and an expert adjudicator who may be more familiar with the intricacies of the dispute, among other benefits. There is a commitment to secrecy that is not found in the common court and the single, binding, and final resolution of a dispute through arbitration is the precise source of criticism that inspires the flock towards arbitration. Without the federal rules of civil procedure that would otherwise govern litigation, arbitration is governed by the procedural rules that each side agrees upon. The FAA paved the way for case law in the United States that would eventually shape a stronger pro-arbitration policy than ever—counseling against “even the mildest interference by courts in the conduct of U.S.-seated arbitrations.”[5] II. THE IMPACT OF U.S. ARBITRATION LAW AND U.S. ARBITRAL INSTITUTIONS IN THE WORLD OF ARBITRATION Assessing the impact of U.S. arbitration law begins by assessing what characterizes U.S. law: civil procedure. The adversarial form of litigation in which procedural tools are employed by advocates to advance arguments in a distinct style distinguishes the United States from other countries—and this feature inevitably slipped, in some capacity, into global arbitral institutions. Because the Rules of Arbitration for the International Chamber of Commerce are so brief,[6] American lawyers had tremendous flexibility in bringing American trial procedures with them. This came specifically in the form of document production for discovery and cross-examinations “to confront adverse witnesses.”[7] Critics refer to these added procedures as costly in both time and expense, defining them as the source of the “Americanization” of arbitration. Yet, while there is truth to such criticism, it may be more accurate to acknowledge the incorporation of aspects of American trial procedure as one country’s influence on arbitration. Far from inheriting solely American practice, global arbitral institutions maintain classic procedural tools while assimilating facets of each major country’s influence on arbitration.[8] III. THE PROSPECTIVE EVOLUTION OF INTERNATIONAL ARBITRATION IN THE USA Apart from being a source of revenue,[9] international arbitration is the natural response to the increase in “trade, investment, and supply-chain relationships” that hope to live free of potential biases from domestic fora.[10] The California Supreme Court may have briefly lost sight of this when deciding Birbrower, wherein attorneys not admitted to the bar of a certain state are not only ineligible to recover attorney’s fee but also, may be fined for unauthorizing practice of law.[11] Since Birbrower over two decades ago, however, the California Legislature unanimously passed Senate Bill 766. Under SB 766, non-California lawyers are able to represent parties in international arbitration proceedings in California, bringing California to the arbitration table. As home to Silicon Valley – and even aside from big technology, home to some of the largest companies in the world – California’s SB 766 will bring a swath of arbitration proceedings to its terrain. While California may certainly work in tandem with New York as the home to arbitration for technology and privacy concerns, reserving trade and investment disputes for New York, California may very well be the next major hub of arbitration. Already, it has received massive interest in being an arbitration destination. SB 766 will transform that interest into a revenue. It thus becomes all the more important, internationally, to understand and confront the ways in which the Americanization of arbitration would take place. [1] See, e.g. Thomas E. Carbonneau, Revolution in Law Through Arbitration, The Eighty-Fourth Cleveland-Marshall Fund Visiting Scholar Lecture, 56 Clev. St. L. Rev. 233, 233 n.3 (2008), available at https://engagedscholarship.csuohio.edu/clevstlrev/vol56/iss2/3 (“judicial decision-making has shifted from rights protection to guaranteeing access to some form of adjudication. As a result, law and adjudication have become less sacramental.”) [2] See American Arbitration Association, Adr.Org, https://adr.org/ (last visited Dec. 28, 2019). [3] See, e.g., Moses H. Cone Memorial Hosp. v. Mercury Construction Corp., 460 U.S. 1, 24-25 (1983) (“[A]ny doubts concerning the scope of arbitrable issues should be resolved in favor of arbitration …”). [4] See Howsam v. Dean Witter Reynolds, Inc., 537 U.S. 79, 85 (2002) (distinguishing between “issues of substantive arbitrability [which] are for a court to decide and issues of procedural arbitrability, i.e., whether prerequisites such as time limits, notice, laches, estoppel, and other conditions precedent to an obligation to arbitrate have been met, [which] are for the arbitrators to decide.”) (citations omitted). [5] See Laurence Shore, Tai-Heng Cheng, Jenelle E. La Chuisa, Lawrence Schaner, and Mara V.J Senn, International Arbitration in the United States 1, 320 (2018). [6] George M. von Mehrem and Alana C. Jochum, Is International Arbitration Becoming Too American?, 2 Global Bus. L. Rev. 47, 51 (2011) available at https://engagedscholarship.csuohio.edu/gblr/vol2/iss1/6. [7] Id. [8] Philip J. McConnaughay, Introduction to International Commercial Arbitration in Asia 1, xxix (2002). In support of his assertion, McConnaughay reports that from 1995 to 2000, China’s leading international arbitration commission, CIETAC, received 4,200 new international commercial arbitrations and the Hong Kong International Arbitration Centre (HKIAC) received 1,394, totaling 5,594. Id. Note: interrogatories and depositions are not included. [9] See ICC (International Chamber of Commerce), ICC Arbitration Figures Reveal New Record for Awards in 2018, https://iccwbo.org/media-wall/news-speeches/icc-arbitration-figures-reveal-new-record-cases-awards-2018/. [10] Daily Journal, International Arbitration Finally Comes to California, Howard B. Miller, https://www.dailyjournal.com/mcle/330-international-arbitration-finally-comes-to-california. [11] See generally, Birbrower, Montalbano, Condon & Frank v. Superior Court, 17 Cal. 4th 119 (1998).
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; International Arbitration

L'arbitrage en droit aérien et spatial - Soliveres, Théo (Aix-Marseille Université, 2021)
Keywords: Arbitrage; Arbitration; Droit aérien; Droit spatial

UNCITRAL Expedited Arbitration Rules - UNCITRAL (United Nations, 2021)

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)

مراكز التحكيم البحري - بلقاسم, حبيب (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
"Les centres d’arbitrage maritime." Résumé : Le sujet des centres d'arbitrage maritime concerne le processus de résolution des contentieux maritimes quand leurs parties optent pour soumettre leur différend à des instances d'arbitrage comme voie alternative. Les centres d'arbitrage maritime appliquent le règlement arbitral et ses règles dans le cas où le choix est fait en fonction de la clause compromissoire qui inclut ce choix ainsi que la loi applicable. Lacompétence de cet instance d'arbitrage convenue débute à la date de la soumission de la demande d'arbitrage, afin de lui confier le suivi des procédures d'arbitrage et de tout ce qui touche au litige arbitral et jusqu' à ce que la sentence (décision) arbitrale soit rendue. "Maritime arbitration centers." Summary: The subject of maritime arbitration centers concerns the process of resolving maritime disputes when their parties opt to submit their dispute to the arbitral tribunal as an alternative solution, and maritime arbitration centers apply arbitration regulations and its rules in case where the choice is made according to the arbitration clause which includes this choice as well as applying the law on all disputes. The arbitral tribunal function starts from the date of submitting the arbitration request to it to be entrusted with following up the arbitration procedures and everything related to the arbitration dispute and until the arbitral award is issued. : الملخص يتعلق موضوع مراكز التحكيم البحري بعملية فض المنازعات البحرية التي يختار أطرافها عرض النزاع على هيئات التحكيم كطريق بديل، و مراكز التحكيم البحري تعمل على تطبيق لوائح التحكيم و نظامها التحكيمي في حال وقوع الاختيار عليها وفقا لشرط التحكيم الذي يتضمن هذا الاختيار، إلى جانب القانون الواجب التطبيق على النزاع. و يبدأ اختصاص هذه الهيئة في التحكيم المؤسسي من تاريخ تقديم طلب التحكيم إليها، ليوكل لها متابعة إجراءات التحكيم و كل ما يتعلق بالمنازعة التحكيمية و إلى غاية صدور الحكم التحكيمي.
Keywords: Application for arbitration; Arbitral Awards; Arbitration; Centres d'arbitrage maritime; Clause d'arbitrage maritime; Demande d'arbitrage; Décision d'arbitrage; Maritime arbitration centres; Maritime arbitration clause

رقابة القضاء على أعمال المحكمين - غزيزات, دليلة (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
رقابة القضاء على أعمال المحكمين من بين أوجه الرقابة التي أقرتها التشريعات الحديثة وقوانين التحكيم الوطنية و الإتفاقيات الدولية وكذا نظام التحكيم في ظل تطور الثقافة التحكيمية في الوقت الراهن. كما تعد ضمانا وحماية للمصالح وحقوق الأفراد والشركات التجارية من جهة وتُمكن القضاء من السيطرة على تصرفات المحكمين وحماية شخصهم في الدعوى التحكيمية لتحقيق فاعلية نظام التحكيم من جهة ثانية. Le contrôle des actes des arbitres est établi par les législations récentes et par la législation arbitrale nationale, ainsi que par les conventions internationales en la matière. Il participe à l’évolution de la culture arbitrale et constitue une garantie et une protection des intérêts des individus et des sociétés commerciales. Il permet d’avoir une vue sur les travaux des arbitres d’une part, et sur leur protection d’autre part, pour assurer l’efficacité de l’arbitrage. The review of the acts of the arbitrators shall be established by recent laws and national arbitral legislation and international conventions on the subject. It contributes to the evolution of the arbitral culture and constitutes a guarantee and protection of the interests of individuals and commercial company’s .It allows having a view on the work of the arbitrators on the one hand, and on their protection to ensure the effectiveness of arbitration
Keywords: Arbitral proceedings; Arbitration; Arbitrator; Arbitre; Contrôle; Judge; Juge; Procédure arbitrale

国际商事仲裁费用构成及合理控制仲裁费用探索 - 侯, 进才 (Journal of Oil and Gas Technology, 2021)
仲裁作为解决国际商事争议的主要方式之一，受到国际工程承包企业的青睐，然而当事人在决定一个案件是否要提起仲裁时，常会把仲裁费用作为一个重要考量指标，高昂的仲裁费用可能会限制国际商事仲裁制度的健康发展。本文以2017版国际商会仲裁规则下的收费标准为基础，从仲裁费用的构成、计算方法入手，探讨了仲裁费用影响因素，并给出了控制仲裁过程费用的合理化建议。 Arbitration, as one of the main ways to resolve international commercial disputes, remains a popular choice for international engineering company. The arbitration fees will be an important evaluating indicator when the parties considering apply for arbitration. Expensive arbitration fees may restrict the healthy development of international commercial arbitration system. Based on the arbitration cost and fees under the arbitration rules of the 2017 edition of the International Chamber of Commerce, characteristics, composition and calculation method of the arbitration fees are showed in this paper firstly; then, its influencing factors are discussed. Reasonable suggestions for controlling the arbitration fees are given in the end of this paper.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Fees; Composition of Arbitration Fees; Controlling the Arbitration Fees; International Commercial Disputes; 仲裁费用; 国际商事; 控制费用; 费用构成

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

La portée de la conciliation préalable en matière de procédures simplifiées de recouvrement de l'OHADA dans la réalisation des droits du créancier - Tonda, Franck (International Multilingual Journal of Science and Technology, 2020)
Keywords: Conciliation; Créancier; MARD; Procédure simplifiée; Recouvrement de créances

L'arbitrage international et les contrats de transfert de technologie en droit comparé : France, Syrie, Égypte - Al Youssef, Omar (Aix-Marseille Université, 2020)
La France en tant qu’un pays développé possède une richesse juridique et judiciaire à propos de l’arbitrage et des contrats de transfert de technologie. Alors que la Syrie n’a pas jusqu’à ce moment un système juridique spécial à ces contrats. En plus, la loi syrienne de 2008 sur l’arbitrage a besoin d’être modifiée en raison des erreurs juridiques massives commises dans cette loi. S’agissant de l’Égypte, la loi de 1999 sur le commerce a mis en place un système juridique solide pour régir les contrats de transfert de technologie et l’arbitrage. Il faut mentionner que la jurisprudence égyptienne est très développée par rapport à la jurisprudence syrienne, ce qui me permet de faire une comparaison entre la France et les deux pays en développement. France as a developed country has a wealth of legal and judicial matters relating to arbitration and technology transfer contracts. While Syria does not yet have a special legal system for these contracts. In addition, Syria's 2008 arbitration law needs to be amended due to massive legal errors in that law. In Egypt, the 1999 trade law established a strong legal system to govern technology transfer contracts and arbitration. It should be mentioned that Egyptian case law is very developed compared to Syrian case law, which allows me to make a comparison between France and the two developing countries.
Keywords: Approche comparée; Arbitrage; Arbitrage international; Arbitragem; Arbitration; France; Syrie; Transfert de technologie; Égypte; Étude comparative

Limites da jurisdição e das decisões jurisdicionais estatais no âmbito da internet - Laux, Francisco de Mesquita (Universidade de São Paulo, 2020)
A tese tem como objetivo desenvolver as relações entre o exercício da jurisdição - especialmente, a limitação territorial de eficácia das decisões - e os conflitos vinculados à postagem de manifestações infringentes na internet. A hipótese central defendida pela tese é a de que a jurisdição e as decisões judiciais estatais, quando direcionadas a remover postagens na internet, têm seu espectro de eficácia limitado ao território do Estado em que proferidas. Isso significa dizer que pessoas que se conectam à internet a partir de outros Estados não podem ser diretamente impactadas pelo comando. A tese busca demonstrar, ainda, que o modelo de reserva de jurisdição estatal não é efetivo, independentemente de critérios de eficácia territorial, para solução de problemas especialmente vinculados à disseminação em massa de manifestações danosas. A tese foi dividida em três capítulos. No primeiro, o objetivo será o de estabelecer os princípios e regras vinculados às ideias de jurisdição internacional de acordo com a legislação brasileira de direito processual civil e direito internacional privado. Na segunda parte, será a vez de abordar os temas em referência a partir das perspectivas trazidas por ordenamentos jurídicos estrangeiros, especialmente recentes pronunciamentos advindos dos Estados Unidos da América e do Tribunal de Justiça da União Europeia a respeito dos limites territoriais de decisões judiciais destinadas a produzir efeitos na internet, além da apresentar uma breve contextualização de como outros países - como China, Brasil, Argentina e México - encaram fenômenos vinculados ao ambiente virtual. No terceiro e último capítulo, tais soluções serão compatibilizadas de modo a delimitar a amplitude territorial da jurisdição e das decisões jurisdicionais estatais nos casos que envolvem conflitos para retirada de postagens na internet. O capítulo abordará, também, a perspectiva de processos e decisões não estatais, adotados por gestores de redes sociais ou tribunais privados em um ambiente de autorregulação regulada, e de que modo isso pode ter reflexos no direito processual sob a ótica das noções de online dispute resolution (ODR). The thesis aims to reveal the relationship between jurisdiction (more specifically, its territorial scope/range) and the conflicts linked to posting abusive or illegal statements on the internet. The main hypothesis of the thesis is that jurisdiction and decisions rendered by the Judiciary, when directed to remove posts on the internet, have their scope/range limited to the territory of the State in which they are rendered. This means that people who connect to the internet from other States cannot be directly impacted by the decision. The thesis also seeks to demonstrate that the state jurisdiction reserve model is not effective, regardless of territorial effectiveness criteria, for solving problems especially linked to the mass dissemination of harmful manifestations. The thesis was divided into three parts. Part 1 aims to establish the principles and rules linked to the ideas of international jurisdiction in accordance with Brazilian legislation on civil procedural law and private international law. Part 2 discusses the issues in reference from the perspectives brought by foreign legal systems, especially recent pronouncements from the United States of America and the Court of Justice of the European Union regarding the territorial scope/range of judicial decisions aimed at produce effects on the internet, in addition to presenting a brief contextualization of how other countries - such as China, Brazil, Argentina and Mexico - face phenomena linked to the virtual environment. In the third and last part, such solutions will be compared in the objective of delimiting the territorial scope of the jurisdiction and of the state jurisdictional decisions in cases involving conflicts for the removal of posts on the internet. The chapter will also address the perspective of non-state processes and decisions, adopted by managers of social networks or private courts in an environment of "regulated self-regulation", and how this may have an impact on procedural law from the perspective of notions of online dispute resolution (ODR).
Keywords: Argentina; Brasil; Chile; China; Competência territorial; Direito Comparado; Direito Processual; Estados Unidos; Europa; Internet; Jurisdiction; Jurisdição; Jurisdição internacional; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Médiation; México; Mídias sociais; ODR; Online Dispute Resolution; Regulated selfregulation; Scope of jurisdiction; Social networks; Territory

International Commercial Arbitration - Kizi, Boratova Ziyoda Sobir (International Journal of Trend in Scientific Research and Development, 2020)
This article is devoted to the complex analysis of the English legislation of the international commercial arbitration. The author analyzed the commercial disputes and the bodies that proceed these disputes in England as well as main statutes regulating the international commercial arbitrations of England. The international commercial practices of the London International Court of Arbitration are described. Moreover, the author represents the main conclusions formed on the basis of the provisions of the national legislation on commercial arbitration and the regulations of the most well-known international arbitrations in England.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Act 1996; Arbitration institution; Commercial disputes; International commercial arbitration; The LCIA Rules; The London International Court of Arbitration (LCIA)

O recurso à arbitragem no âmbito das sociedades comerciais : os conflitos societários internos - Vaz, Juliana Touro Cerejo Rabaça (Universidade Católica Portuguesa, 2020)
A presente dissertação tem como objetivo analisar, à luz do ordenamento jurídico português, a possibilidade e adequação do recurso ao instituto da arbitragem como meio de resolução dos litígios intrassocietários, isto é, os litígios emergentes das relações entre os sócios de uma sociedade, os resultantes das relações entre os sócios e a própria sociedade, ou ainda no âmbito das relações entre os sócios ou a sociedade per si e os titulares dos órgãos de administração ou de fiscalização da mesma. Para tal, foi inicialmente adotada uma perspetiva comparatística com outros ordenamentos jurídicos. Posteriormente, foi adotada uma abordagem expositiva, do instituto da arbitragem em Portugal, analisando inicialmente de um modo geral, especificando depois o propósito principal da presente dissertação – a arbitrabilidade dos litígios intrasocietários, nomeadamente o regime da convenção de arbitragem, do tribunal arbitral e da própria sentença arbitral. Avaliadas as vantagens e os inconvenientes do recurso à arbitragem enquanto meio de resolução alternativa de litígios, e a sua aplicabilidade aos litígios intrassocietários, tomando como referência a escassa regulamentação deste instituto neste domínio no nosso ordenamento jurídico, conclui-se a presente dissertação com uma proposta de regulamentação legal e outra estatutária da arbitragem dos referidos litígios intrasocietários.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Entreprises commerciales; Litige interne

التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.

Le rôle de la confidentialité dans la procédure préventive de conciliation de l’OHADA - Nkouamo Ngnegue, Luc Norbert (International Multilingual Journal of Science and Technology, 2020)
La procédure de conciliation est l’une des innovations de la réforme de l’Acte Uniforme relatif aux procédures collectives d’apurement du passif. Le législateur OHADA l’a institué dans l’objectif de mieux gérer la prévention de la cessation des paiements des entreprises en difficulté financière. La conciliation est entrée dans la sphère des procédures collectives de l’OHADA avec un principe clé à savoir la confidentialité. Le principe de confidentialité constitue une pierre angulaire de la conciliation au regard de la place qu’elle occupe dans le dénouement de celle-ci. Le législateur communautaire fait intervenir ce principe dans tout le dénouement de la conciliation. La confidentialité se présente ainsi comme un aspect phare de la procédure. Cet état de chose nous a alors amené à s’interroger sur le rôle que peut bien jouer cette confidentialité qui anime l’ensemble de la procédure préventive. Selon notre point de vue, la confidentialité joue un double rôle dans la procédure de conciliation. Elle favorise d’une part la protection du débiteur soumis à la procédure en lui assurant la préservation de son crédit ainsi que les informations divulguées et d’autre part, facilite l’efficacité de la procédure à travers son imposition générale même si elle est un peu fragilisée par certaines atteintes. The procedure of conciliation is an innovation of the uniform Act organizing the legal treatement enterprises difficulties. The OHADA lagislator has institute it with the objective for the better manage in the suspension of payments prevention for enterprises in financial difficulty. The conciliation procedure has come in the sphere of OHADA legal treatement enterprises difficulties with a main principle which is confidentiality. The principle of confidentiality constitute a cornerstone of the conciliation procedure ending according to the Sport place it occupe. The Community legislator makes this principle to intervene in all the conciliation procedure. The confidentiality is present as a main aspect of the procedure. This situation brought us to question the role of the confidentiality witch lead all the preventive procedure. According to our point of view, the confidentiality plays a double role in the conciliation procedure. It favours firstly the protection of the debtor submit to the procedure insuring the preservation of his credit as well as divulgates informations and secondly, it facilitate the effectiveness of the procedure by his general using even it is fragilize by certains attacks.
Keywords: Cessation des paiements; Conciliation; Confidentiality; Confidentialité; Debtor protection; Efficacité de la procédure; Procedure effectiveness; Protection du débiteur; Suspension of payments

The Changing Paradigm of International Tax Dispute Settlement: What Are the Promises and Challenges of Mandatory Arbitration for China? - Ji, Xueliang (Oregon Review of International Law, 2020)
Through comparing dispute resolution methods under bilateral investment treaties (BITs) and bilateral tax treaties, this Article critically discusses the advantages of incorporating mandatory arbitration in bilateral tax treaties and demonstrates that national sovereignty will not be decreased by it. As a result, the Article argues that it would, in fact, be beneficial for China to adopt the mandatory arbitration method, which would further strengthen the global reform initiated by the OECD.
Keywords: China; Dispute resolution; International tax law

Reimagining the Framework for Resolving Intra-African Commercial Disputes in the Context of the African Continental Free Trade Area Agreement - Onyema, Emilia (World Trade Review, 2020)
This article examines the effectiveness of the framework for the resolution of intra-African cross-border commercial disputes, arising from the projected increase in intra-African trade in goods, services, and investments under the African Continental Free Trade Area. It examines the peculiar nature of intra-African trade and of the participating entities to provide the context to discuss the three major processes adopted in commercial dispute resolution (litigation, mediation, and arbitration) in Africa. It then argues for the promotion of arbitration as the dispute resolution process of choice for such disputes. It reimagined the framework for arbitration at the continental level and made two proposals targeted at the greater efficiency of the process: the designation of Regional Arbitration Centres across the African Union's eight recognized Regional Economic Communities, to administer such references; and the establishment of an African Commercial Court as a one-stop court for the enforcement or annulment of the final award.
Keywords: AfCFTA; Arbitrage; Arbitragem; Arbitration; Commercial dispute; Dispute Resolution; Litigation

Dos efeitos da falência sobre a arbitragem - Deccache, Antonio Carlos Fernandes (Universidade de São Paulo, 2020)
Esta tese analisa os efeitos da falência sobre a arbitragem. A falência constitui um regime complexo, formado por regras materiais e processuais, criado para lidar com o problema da insolvência empresarial. Tem natureza de execução coletiva, reunindo todos os credores do falido e todos os seus bens, que devem ser liquidados a fim de pagar os credores. Para a consecução dos seus objetivos, a decretação da falência opera efeitos diretos sobre a pessoa do devedor, seus bens, seus contratos e seus processos. O processo falimentar realiza-se mediante procedimento administrado pelo Poder Judiciário, centralizado, público, com a finalidade de lidar com os diversos interesses envolvidos. Diversamente, a arbitragem é meio privado de solução de controvérsias pelo qual partes capazes elegem um terceiro, da sua confiança, para resolver litígio versando sobre direitos patrimoniais disponíveis. Tem natureza jurisdicional e caracteriza-se por constituir alternativa privada, rápida, flexível e especializada de dirimir demandas que admitem transação. Seu procedimento tem natureza de processo de conhecimento, terminando com a prolação de sentença, e constitui processo descentralizado, privado, usualmente sigiloso, no qual as partes têm ampla liberdade para definir as regras materiais e processuais aplicáveis. Enquanto a falência constitui sistema que visa lidar com interesses de ordem pública -- sendo, portanto, controlado pelo Estado, centralizado, público e coletivo --, a arbitragem pauta-se na autonomia da vontade, na descentralização do sistema de resolução de litígios, lida com interesses privados e é usualmente sigilosa. Considerando as relevantes diferenças entre os dois institutos, questiona-se em que condições a falência e a arbitragem podem coexistir. O que se propõe neste trabalho é, portanto, analisar quais são os efeitos que a falência opera sobre a arbitragem e como esses efeitos impactam na convivência entre os dois institutos. Para tanto, este estudo organiza-se em duas partes: parte I, na qual são apresentadas noções introdutórias da falência e da arbitragem, que servem para assentar as premissas utilizadas na análise; e parte II, na qual são analisados os efeitos propriamente ditos da falência sobre a arbitragem. A parte I está dividida em dois capítulos, nos quais se trata, sucessivamente, da falência e da arbitragem. Já a parte II está dividida em três capítulos, nos quais se trata, sucessivamente: (i) dos efeitos da falência sobre a convenção de arbitragem; (ii) dos efeitos da falência sobre o procedimento arbitral; e (iii) dos efeitos da falência sobre a sentença arbitral. Ao final, conclui-se que, apesar de a falência operar efeitos sobre alguns aspectos da arbitragem, impondo-lhe limites no contexto falimentar, isso não as torna incompatíveis. Aduz-se que a falência não invalida a convenção arbitral celebrada antes da falência, nem impede sua celebração pelo administrador, que, entretanto, depende de autorização judicial. Comprovase, também, que o advento da falência não atrai nem suspende os procedimentos arbitrais, mas impõe condições para que o processo possa se desenvolver. Por fim, evidencia-se que a sentença arbitral, uma vez proferida, deve ser submetida a verificação no processo falimentar.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Arbitration Award; Arbitration Proceeding; Bankruptcy; Direito falimentar; Falência; Insolvency; Juízo arbitral; Procedimento especial

The Applicability of Mediation as an Alternative Dispute Resolution Mechanism under OHADA Law - Leinyuy, Kifemmabuh Antonia (Scholars International Journal of Law Crime and Justice, 2020)
Almost 20 years after it adopted the Uniform Act on Arbitration, OHADA revised its Uniform Act on Arbitration and adopted a new Uniform Act on Mediation along with the fresh set of arbitration rules of the Common Court of Justice and Arbitration in Abidjan. These three texts were revised with the assistance of consultants. Among other changes, with the 2018 Uniform Act on Mediation, a solid platform for the use of mediation in the region is now in place. The ability of mediators to carry out their adjudication function with judicial intervention remains a major challenge by parties under the OHADA zones. In this light, the worry which this article seeks to uncover is how the new mediation law is applicable and facilitates the amicable settlement of investment disputes. The article also highlights the legal basis regulating the mediation process as a whole. In attaining these objectives, we employ doctrinal research methodology. The article conclude with vigorous recommendations which if effectively implemented will go a long way to enhance business (investment) security.
Keywords: ADR; Alternative dispute resolution; Applicability; Dispute resolution mechanism; MARD; Mediación; Mediation; Mediação; Médiation; OHADA Uniform Act

Letztwillige Schiedsverfügungen : Geltungsgrund und Geltungsgrenzen - Gleim, Jakob (Studien zum ausländischen und internationalen Privatrecht, 2020)
Nach §1066 ZPO gelten die Vorschriften über vertraglich vereinbarte Schiedsgerichte entsprechend für "Schiedsgerichte, die in gesetzlich statthafter Weise durch letztwillige [...] Verfügungen angeordnet werden". Während solche letztwilligen Schiedsverfügungen im 20.Jahrhundert sehr selten waren, beschäftigen sie heute die deutschen Gerichte mit gewisser Regelmäßigkeit. Mit Zunahme der praktischen Relevanz rücken auch die dogmatischen Grundlagen letztwilliger Schiedsverfügungen in den Fokus: Warum darf der Erblasser nicht nur materielle, sondern auch prozessuale Verfügungen von Todes wegen treffen? Wie weit reicht die Zuständigkeit des letztwillig eingesetzten Schiedsgerichts? Und welches Recht ist anzuwenden, wenn der Erbfall grenzüberschreitende Bezüge aufweist? Jakob Gleim beantwortet diese Fragen und bezieht dabei im Rahmen eines Rechtsvergleichs auch das US-amerikanische Recht ein. Fürdie vorliegende Dissertation wurde Jakob Gleim mit der2020 der Max-Planck-Gesellschaft ausgezeichnet. Is it possible for the testator to mandate unilaterally that all disputes concerning the estate are to be arbitrated instead of litigated? While such a testamentary arbitration clause is an expression of the decedent’s freedom of disposition, it contradicts the beneficiaries’ right of access to a public court. In his dissertation, Jakob Gleim examines the tension between the decedent’s freedom of disposition and the rights of the beneficiaries, balancing these two positions against one another and thereby identifying the reasons and the limitations of the validity of testamentary arbitration clauses. While such clauses were rather rare in the 20th century, German courts have to deal with them more regularly nowadays. In his dissertation, Gleim explores the practical significance of testamentary arbitration clauses as well as their advantages and disadvantages. The author also addresses the questions of how far the jurisdiction of the arbitral tribunal extends and which law is to be applied in cross-border cases. The inquiry also includes insights gained from a comparative analysis of US-American law.
Keywords: Arbitaje; Arbitrage; Arbitragem; Arbitration; Arbitration clause; Bankruptcy; Clause d'arbitrage; Insolvency; Mediation; Negotiation

The Standards for Proving Damages and Its Amount: A Comparative Study under Transnational Instruments and International Arbitration Awards - Shoarian, Ebrahim; Sahebjam, Sara (Public Law Researsh, 2020)
Defining the applicable standards for proving and measurement of damages constitute one of the most significant issues under the law of damages. In principle, an aggrieved party, who claims compensation for damages based on contractual liability is responsible for showing the existence and the amount of losses suffered or to be suffered. Due to great importance of the issue, transnational instruments of contract law, such as UNIDROIT Principles of International Commercial Contracts (UPICC), Principles of European Contract Law (PECL) and Draft Common Frame of Reference (DCFR) have set out, explicitly or implicitly, special standards such as reasonable certainty, reasonably likely to occur and so on for proving damages; By contrast, the Iranian laws and regulations including the Civil Code do not set out such standards. The legal scholarship and jurisprudence have also failed to address the issue. Therefore, a comparative study of the issue with particular look at international instruments and arbitral awards could provide a reliable source of guidance. This paper analyzes the general and specific standards for proving damages and those situations that fall outside of ambit of the standards such as late payment damages. By doing so, the paper tries to open the debate in Iranian law. یکی از موضوعات قابل توجه در حوزه حقوق خسارت، تعیین استانداردهای قابل اعمال برای اثبات خسارات و میزان آنها است. علی القاعده، زیان‌دیدهای که به استناد مسئولیت قراردادی برای مطالبه خسارت اقامه دعوی میکند، بایستی اصل و میزان خسارتی را که متحمل شده یا خواهد شد، به اثبات برساند. نظر به اهمیت موضوع، اسناد فراملی مربوط به حقوق قراردادها از جمله اصول قراردادهای تجاری بینالمللی، اصول حقوق قراردادهای اروپا و پیشنویس طرح مشترک مرجع، به صورت صریح یا ضمنی، استانداردهای مشخصی مانند قطعیت متعارف، وقوع محتمل متعارف و غیره را برای اثبات خسارت پیشبینی کردهاند. در مقابل، مقررات موضوعه ایران از جمله قانون مدنی؛ چنین استانداردهایی را تنظیم ننموده و موضوع نیز مورد بررسی حقوقدانان و رویه قضایی قرار نگرفته است. بنابراین، مطالعه تطبیقی موضوع با نگاهی ویژه بر اسناد بینالمللی و آرای داوری می‌تواند منبع قابل اتکایی برای طرح بحث باشد. این مقاله، استانداردهای عام و خاص اثبات اصل خسارت و میزان آن و نیز مواردی مثل خسارت تأخیر تأدیه را که خارج از قلمرو شمول این استانداردها هستند، مورد تحلیل قرار میدهد و در نهایت تلاش دارد تا باب بحث را در حقوق ایران بگشاید.
Keywords: Arbitral Awards; Reasonable Certainty; Reasonably Likely to Occur; Standard for Proving Damages; Transnational Instruments; آرای داوری; استاندارد اثبات خسارت; اسناد فراملی; قطعیت متعارف; وقوع محتمل متعارف

Fall of Last Safeguard in Global Dejudicialization: The Problem of Protecting Public Policy in Private Business Disputes - Ghodoosi, Farshad (Oregon Review of International Law, 2020)
The importance of courts is shrinking. This is largely due to global dejudicialization: the process of outsourcing disputes to private dispute resolution. In the last several decades, along with the triumph of neoliberalism, privatization of the resolution of disputes has become the gospel of modern judiciaries. Courts have been pushed to the tail end of the private adjudication process and are used only as the last resort. The courts’ warm embrace of this structure along with practitioners’ push has led to a staggering expansion of private dispute resolution. The world therefore has witnessed an unprecedented growth of arbitration—the primary mode of private dispute resolution.
Keywords: Business law; Dejudicialization; Dispute resolution; Déjudiciarisation; Privatization; Public policy

La protection des secrets commerciaux dans l'arbitrage commercial international - Bitho, Théodore-Alexandre de Nika (Université Paris 1, 2020)
L'importance des secrets d'affaires dans l'essor de l'économie mondiale n'est plus à démontrer. Ils sont, selon les indicateurs les plus fiables, la partie la plus importante du patrimoine des sociétés qui détiennent les plus grandes fortunes du monde. Mais force est de constater que leur protection dans l'arbitrage commercial international est peu effective. Ils sont victimes de divulgations licites ou illicites qui les exposent. Pour une meilleure protection des secrets d'affaires durant une procédure arbitrale, des mesures correctives sont nécessaires. Ces mesures doivent concourir à redéfinir un cadre juridique pratique dont le fondement et la justification est la protection de l'information qui a une valeur commerciale et économique. Pour ce vaste chantier, la contribution des usagers et praticiens de l'arbitrage commercial international est indéniable mais celle des États est indispensable.
Keywords: Arbitrage; Arbitrage commercial international; Arbitrage international; Arbitragem; Arbitration; Confidentiality; Confidentialité; Discovery; Droit commercial (droit international); International Arbitration; Preuve (administration); Protection des secrets; Protection of secrets; Rôle de l'arbitre; Secret commercial; Secret d'affaires; Secrets d'entreprises; Trade secret

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Les suites de l’accord amiable en afrique - Blanc, Gérard (L'accord amiable, 2020)

Guide de l'arbitrage de l'OMPI - Centre d’arbitrage et de médiation de l'OMPI (OMPI, 2020)

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

Arbitration related lessons: Insights from the supreme courts around the world - Nigmatullina, Dilyara; Vanlerberghe, Beatrix (b-Arbitra : Belgisch tijdschrift voor arbitrage, 2020)
In international arbitration, arbitrators have procedural powers that allow them to manage and conduct the arbitration proceedings in a fair and efficient manner. These powers are typically set out in the arbitration rules that the parties have agreed to, such as the International Chamber of Commerce (ICC) rules or the United Nations Commission on International Trade Law (UNCITRAL) rules. Arbitrators have the authority to determine the procedure to be followed in the arbitration, including the admissibility, relevance, materiality, and weight of the evidence presented. They can also decide on the language to be used in the arbitration and the location of the hearings. In addition, arbitrators can issue orders and directions as needed to ensure the fair and efficient conduct of the proceedings. This may include ordering the production of documents or witness testimony, or setting time limits for the submission of evidence. The present paper critically examines the lex arbitri, the law that governs the arbitral proceedings, and makes out a case that lex arbitri cannot be challenged in court, as the parties to the arbitration have agreed to resolve their disputes through arbitration rather than through the courts. However, if the tribunal exceeds its powers or acts in a manner that is inconsistent with the lex arbitri, the parties may have grounds to challenge the tribunal's decision on the grounds of lack of jurisdiction or due process. The paper summarises some key judgments in which Courts have upheld or quashed the Tribunals procedural orders. It will be concluded that the procedural powers of arbitrators in international arbitration are real and not perfunctory, though bounded within powers extended by Parties to the arbitral tribunal.
Keywords: Arbitrage; Arbitragem; Arbitration

Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti

The Use of Mediation in ISDS - UNCITRAL Working Group III Virtual Pre-Intersessional Meeting (Asian Academy of International Law Limited, 2020)
Keywords: ISDS; Investor-State Dispute Settlement; Mediation; Médiation

La regulación del convenio arbitral y su implicancia en la institucionalidad del arbitraje comercial en el Perú - Vidal Ramos, Roger Pavletich (Universidad Nacional Mayor de San Marcos, 2020)
Estudia la regulación y los aspectos vulnerables del convenio arbitral, con énfasis a la necesidad de alcanzar una mejor institucionalidad del arbitraje comercial en el Perú. Determina los principios que fundamentan el arbitraje comercial. Identificar los supuestos de afectación al convenio arbitral. Analiza diversas sentencias de anulación de laudo respecto a la inexistencia de convenio arbitral. Analiza los diversos estudios teóricos y normativos en sede nacional e internacional respecto a los alcances del convenio y práctica arbitral. Identifica las instituciones jurídicas que brinden una protección del convenio en vía arbitral y judicial..
Keywords: Arbitrage; Arbitragem; Arbitraje industrial; Arbitraje y laudo; Arbitration; Convenios de arbitraje comercial; Convention d'arbitrage

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration

基于国际商会仲裁规则下的国际工程项目仲裁管理 - 侯, 进才 (Journal of Oil and Gas Technology, 2020)
随着世界经济全球化，国内外企业之间的商贸往来迅猛发展，出现商事争议与纠纷的案件也呈现上升趋势，仲裁以其高效、快速等优点成为解决国际商事纠纷的最终方式之一。本文从仲裁的优点入手，首先阐述了完整仲裁过程中各个关键环节及注意事项，然后用流程图和横道图两种形式体现了一个完整的仲裁过程，最后就国际工程项目仲裁管理给出了具体建议。 With the globalization of the world economy, the commercial exchanges between domestic and foreign enterprises are developing rapidly, and the number of commercial disputes cases is growing quickly. Considering its advantages of high efficiency and speed, arbitration has become one of the final ways to solve international commercial disputes. This paper firstly presents the advantages of arbitration, then expounds the key stages and attention during the whole arbitration process. Flow chart and Gantt chart are drawn to show logics of the process. Specific suggestions on the arbitration management of international projects are given at the end of the article.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Management; Arbitration Process; International Project; 仲裁程序; 仲裁管理; 国际工程